VOCs over the Himalayan-Tibetan Plateau: A review of observations, sources, and atmospheric processes - Danying Shan; Xin Wan; Jing Lai; Duo Bu; Ting Zhang; Likun Xue; Kirpa Ram; Zhenhao Ling; Shuzheng Guo; Chunxiang Ye; Shuo Yang; Zhiyuan Cong (Atmospheric Research, 2026)

IFI6 is associated with interferon activation and complement-associated immune responses in primary Sjögren’s disease - Yibing Han; Yikun Mei; Xiaoqin Meng; Minjv Zhang; Shuo Yang; Weizhi Wang; Wen Qiu; Zuoqing Dong (Functional & Integrative Genomics, 2026)

Genome-wide identification and expression analysis of IDD gene family in Gossypium hirsutum L - Shuo Zhang; Huixin Jiao; Dongyun Zuo; Qiaolian Wang; Limin Lv; Youping Zhang; Yi Yang; Guoli Song; Hailiang Cheng (Functional & Integrative Genomics, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

A high proportion of A2 β-casein in β-casein impairs the gel properties of fermented milk by affecting protein aggregation following heat treatment - Qian Su; Shuo Yang; Miao Wen; Liang-Yu Ma; Xiang-Chen Meng; Wei Yu (Food Hydrocolloids, 2026)

Insights into the role of TLR21 in innate immunity of Japanese flounder (Paralichthys olivaceus) - Yuting Song; Yuanxin Yang; Shuo Zhang; Songlin Chen; Guobin Hu (Fish & Shellfish Immunology, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Dual-tailoring of microenvironment and electronic structure in tandem catalysts for highly selective CO2-to-ethanol electroreduction - Shuo Cui; Cheng Yang; Tingting Tang; Xinjie Liu; Xinlong Huang; Junyang Li; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2026)

Valorization of blue honeysuckle residue for nitrogen retention in composting: Microbial synergy mediated by differentiated electron transfer regulation - Xuan Tang; Yuhao Guo; Yueyi Liu; Zhenchao Wu; Hao Zhang; Xiujun Tu; Liangyang Mao; Weige Yao; Ying Yang; Shuo Li; Tong Yang; Tingting Xu; et al. (Biomass and Bioenergy, 2026)

Isolation and pathogenicity of Actinobacillus pleuropneumoniae Serovar 19 in pigs - Bo Hong; Guangyuan Yi; XvDong Lin; YingXuan Ye; XiaoLi Liu; Ahmed H. Ghonaim; Yang Zeng; Shuo Zhang; Ping Bai; Wentao Li; Xuexiang Yu; Qigai He (Veterinary Microbiology, 2026)

Leveraging yeast as cell factories to empower next generation food innovation - Zifan Dou; Jingyao Zhu; Ruyi Song; Ruixue Liu; Haonan Huang; Xinna Qiu; Shuo Ren; Demei Meng; Yuyu Zhang; Rui Yang (Trends in Food Science & Technology, 2026)

Do electric vehicles increase driving? Behavioral and spatial evidence of rebound effects from causal and spatial machine learning - Shuo Yang; Leyu Zhou; Yucheng Wang; Hui He; Xiaoli Sun; Liang Guo; Frank Witlox (Journal of Transport Geography, 2026)

Diverging hydrometeorological drivers of flashier floods in a warming climate - Fengjia Zhou; Shuo Wang; Louise Slater; Peirong Lin; Hanbo Yang; Sijie Tang; Amir AghaKouchak (Journal of Hydrology, 2026)

Differential response of floods to climate change and human activities in the Yalu River over the past two millennia: insights from hydrological modeling - Shengjing Liu; Yong Shi; Tao Liu; Tao Jiang; Chipeng He; Jixuan Lyu; Afei Hou; Guang Yang; Yang Yang; Xiaomei Xu; Shuo Zhang; Jianhua Gao (Journal of Hydrology, 2026)

Mussel-inspired construction of superhydrophilic/underwater superoleophobic PTFE membranes using a novel ε-polylysine-based modification for efficient oil-water separation - Xin Wu; Chenyang Li; Shuiling Hong; Ang Gao; Haoming Duan; Wei Li; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

Persistent free radical-mediated Z-scheme charge transfer in ZnO-ZnS@Biochar: Bypassing redox potential compromise for efficient photocatalytic degradation - Hao Cai; Tianyuan Guan; Shuo Yang; Changyu Lu; Zhijia Miao; Aifang Gao; Zichuan Ma (Journal of Environmental Chemical Engineering, 2026)

Synergistic TP/APTES coating on PBT membrane enables superhydrophilicity and efficient oil-water separation - Shuiling Hong; Chenyang Li; Xin Wu; Ang Gao; Haoming Duan; Man Liu; Sijia Zhang; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

Effect of liquefaction solvent, catalyst sulfidation method and H2S on mild liquefaction behaviors of Jiangna coal over Fe-based catalysts - Jiaqi Yu; Yuxin Wen; Shuo Wang; Rui Zhang; He Yang; Yang Li; Xingxing Xiao; Yining Guan; Haoquan Hu; Lijun Jin (Fuel, 2026)

Cepharanthine-mediated photodynamic inactivation and active gelatin packaging for pork preservation - Lin Yang; Kaiyuan Su; Zhuoran Guo; Bingzhi Li; Yajie Wang; Zhenqing Guo; Jianlong Wang; Shuo Shi; Shusen Li; Shengpeng Su; Wentao Zhang (Food Research International, 2026)

Extraction-driven structural transitions and functional enhancement of mycelial protein concentrates under homogenization pressure and alkaline conditions - Houle Xiang; Shuo Zhang; Yuqing Zhang; Pengpeng Yang; Wei Zhuang; Jinglan Wu; Yong Chen; Hanjie Ying (Food Research International, 2026)

Royal jelly enhances ovarian function by modulating taurocholic acid metabolism and attenuating oxidative stress in D-galactose-induced POI mice - Xiaoxue Zheng; Peihao Sun; Changjiu He; Mingxiao Liu; Jieruo Qiu; Zhiming Ding; Yingying Zhang; Shuo Zhou; Ji Zhou; Jingzhe Sun; Wenwen Feng; Lu Zhang; et al. (Food Research International, 2026)

Three-birds-with-one-stone: MIP-decorated MOF/COF hybrid nanoplatform for multifunctional PEC sensing, adsorption, and photocatalytic degradation of patulin - Wenyan Yan; Shuyue Li; Baoqing Bai; Ying Zhang; Jinhua Zhang; Tao Bo; Qinghua Wang; Ying Gu; Yukun Yang; Shuo Wang (Food Chemistry, 2026)

Surface-engineered Au@Pt nanoparticles-based colorimetric/fluorescent dual-mode three-channel sensor array: Discrimination of light aroma-type Baijiu with variable qualities - Yukun Yang; Jian Liu; Rong Guo; Baoqing Bai; Tao Bo; Jinhua Zhang; Ligang Yu; Huilin Liu; Ying Zhang; Shuo Wang (Food Chemistry, 2026)

Differential regulation of exercise fatigue by Spirulina peptides: energy metabolism and antioxidant defense mechanisms mediated in a comparative swimming model - Tao Ding; Zhaoxin Li; Rui Duan; Junjie Zhang; Lihong Xing; Xiaojie Sun; Fang Zhang; Qingyan Wang; Shuo Qie; Yi Yang; Cuiping Song (Food Chemistry, 2026)

Dual-functional UIO-66 composite films for smart packaging: Antibacterial and freshness-indicating - Min Yang; Chenlu Wang; Shuo Chen; Xiaoqi Fang; Yanan Sun (Food Control, 2026)

Straw return enhances soil multifunctionality and maize yield through shifts in bacterial community structure - Shijie Deng; Yang Yu; Yubo Hao; Yubo Jiang; Guoyi Lv; Yiteng Zhang; Linjing Han; Meng Cheng; Shuo Zhang; Chunrong Qian (Field Crops Research, 2026)

Terrestrial expression of the Jenkyns Event: Integrated records from the Eastern Tethys, China - Xiaowei Liu; Ran Gao; Kai Zhou; Shuo Zhang; Jing Lu; Rongtao Guo; Zhiming Yan; Peixin Zhang; Xiaotao Xu; Wanqing Wang; Minfang Yang; Longyi Shao; et al. (Earth-Science Reviews, 2026)

Emerging sensing strategies for simultaneous discrimination and detection of viable and non-viable foodborne pathogens - Jie Wu; Wenyan Yan; Ying Zhang; Yukun Yang; Shuo Wang (Current Opinion in Food Science, 2026)

Microstructured flexible hydrogel sensors with synergistic conductive networks for intelligent handwriting interaction systems - Jianfeng Chen; Na Yang; Shuo Guo; Zhengfu Jiang; Xiaoshan Jin; Yichuan Dai; Ben Huang; Xiaoxiao Chen (Chemical Engineering Journal, 2026)

S-scheme heterojunctions for overall water splitting - Yang Yang; Zhao Liang; Shuo Wang; Weiyou Yang; Blaž Likozar; Huilin Hou (Chemical Engineering Journal, 2026)

Aligned-to-random bilayered collagen nerve conduit enhances pain relief and nerve repair following surgical decompression in diabetic entrapment neuropathy - Shuo Li; Chenlong Liao; Yue Zhang; Chun-Yi Yang; Zheng Cao; Yayuan Tian; Xiumei Wang; Wenchuan Zhang (Chemical Engineering Journal, 2026)

A 5-HT-loaded coacervate biomaterial synergizing anti-inflammatory, antimicrobial, and antioxidant functions for accelerated infected wound healing - Zhengnan Zhao; Yinxuan Xu; Chengzhen Chu; Xueyang Li; Yang Shen; Xiaohan Liu; Xuesheng Zhang; Xincheng Tang; Tao Li; Shuo Chen; Chuanglong He; Wenhui Liu; et al. (Chemical Engineering Journal, 2026)

Vegetation restoration induces the co-evolution of red soil structure and organic carbon on steep terraced slopes - Jin Wu; Haiqun Yuan; Shuo Gu; Xinjie Li; Mengqin Yang; Jian Gu; Yaojun Liu (CATENA, 2026)

Enhanced phenanthrene degradation in microalgae-bacteria systems: Mechanistic roles of exogenous and indigenous degraders - Mengying Wang; Han Wang; Xuetao Liang; Jingran Li; Chen Wang; Longyan Cui; Shuo Yang; Jiaxuan Lin; Qi Yang; Zhilin Yang (Bioresource Technology, 2026)

Built environment constraints on well-being in resource-based cities - Shuo Lu; Feilong Yang; Jianhui Yu; Wenzhong Zhang (Building and Environment, 2026)

Rapid colorimetric assay-guided discovery of α-glucosidase inhibitors from natural products using a MOF-818@Pt nanozyme - Baiting Zhang; Mu Chen; Yang Huang; Siyi Mou; Shulei Qin; Shuo Yang; Zhengjin Jiang; Shengfeng Huang (Analytica Chimica Acta, 2026)

A vision-based time-delay modeling and control method for target-oriented trenching fertilization in spindle-shaped orchards - Kang Zheng; Liping Chen; Yan Gong; Senlin Song; Zhichong Wang; Wei Zou; Shuo Yang; Changyuan Zhai (Computers and Electronics in Agriculture, 2026)

Do electric vehicles reduce transit use? Environmental-behavioral insights from causal machine learning - Shuo Yang; Leyu Zhou; Junren Wang; Liang Guo; Xiaoli Sun; Frank Witlox (Transportation Research Part D: Transport and Environment, 2026)

Hydro-mechanical behavior and modeling of fouled ballast under coupled water immersion and cyclic loading - Zhihao Yang; Hengwen Liu; Huaiping Feng; Shiao Cheng; Shuo Dong; Deliang Ma; Shuaijie Guo (Transportation Geotechnics, 2026)

Exogenous microbial metabolites improve rhizosphere microecology and reduce Fusarium abundance to control root rot in wolfberry - Dong Zhao; Tingting Xu; Hongyu Chen; Shuo Shen; Shuqun Deng; Junlong Feng; Chenxu Gao; Jiali Ning; Zhuofei Zhang; Zhongyang Xu; Wei Li; Yang Zhang (Rhizosphere, 2026)

Oil removal performance and separation mechanism of oleophilic/oleophobic mixed granular bed - Kelong Chen; Shuo Liu; Yanhong Zhang; Qiang Yang; Hao Lu (Journal of Water Process Engineering, 2026)

Study on defluorination performance and mechanism of Fe-Al modified oyster shell substrate coupled with microbially induced calcium precipitation for enhanced ecological floating beds - Sen Wang; Xueqi Wang; Yile Dai; Long Yang; Jingxin Song; Junqi Sun; Chunyan Zhai; Fanlong Kong; Shuo Li; Jiaxin Shi (Journal of Hazardous Materials, 2026)

Cation regulation on electro-synthesis of peroxydisulfate from sulfate-containing wastewater via outer-sphere pathway - Yizhou Yang; Shuo Sun; Dong Xu; Shengshou Xu; Chong Li; Chenxin Xie; Xuejing Yang (Journal of Hazardous Materials, 2026)

AI-2 type quorum-sensing signal enhances mercury resistance and adsorption in thermotolerant Bacillus subtilis - Shuo Han; Qianyun Mo; Xiaobin Wen; Xiangru Wang; Xiangqian Wang; Yao Yu; Yixiao Yang; Chunzhe Yang; Zhonghua Cai; Jin Zhou (Journal of Hazardous Materials, 2026)

Experimental quantification of the competitive adsorption characteristics and flow dynamics of CO2/CH4/N2 mixtures in a coal seam - Shuo Jia; Hao Xu; Daoyong Yang; Shunyi Dong; Gang Wang (Journal of Cleaner Production, 2026)

Gadolinium-based metal-organic framework with restriction of aggregation-caused quenching effect synergized high-activity pt-single-atom catalyst for multiplex self-enhanced electrochemiluminescence sensing detection of kanamycin - Ling Wu; Kaiwen Yang; Yumeng Qin; Wen Hao; Lin Cai; Mengmeng Guo; Guozhen Fang; Shuo Wang (Food Research International, 2026)

Multi-omics integration reveals antioxidant and lipid metabolic signatures underlying the beneficial effects of selenium-enriched yeast on pork quality - Maocuo Zhou; Xu Wang; Yali Wu; Wanlu Yang; Shuo Liu; Xinyi Liu; Qian Chen; Chunbo Cai; Yan Zhao; Xiaohong Guo; Guoqing Cao; Bugao Li; et al. (Food Bioscience, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Function identification of nitrogen forms in nitrogen-doped biochar for promoting methane production in anaerobic digestion - Xiao-Yue Cao; Cong-Cong Tang; Shuo-Han Chen; Sheng-Jie Sun; Chun-Xue Yang; Ai-Juan Zhou; Zewei Liu; Zhang-Wei He (Environmental Research, 2026)

Injectable hydrogel with synergistically accelerated degradation for synergistic antimicrobial and ER-stress-modulating therapy against diabetic periodontitis - Xiaoming Li; Kun Li; Yuchen Zhou; Can Yang; Siqi Liu; Shuo Yang; Jimin Guo; Jianjun Zhang (Chemical Engineering Journal, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Interdecadal intensification of late-spring precipitation over the Hengduan Mountains since the late 1990s - Meiying Zheng; Huizhi Liu; Shengyuan Liu; Haoran Li; Xiaoyang Liu; Lijun Xie; Guotao Zhang; Ting Yang; Fei Wang; Yunhao Gu; Junjie Zhao; Shuo He (Climate Dynamics, 2026)

First report of broad bean wilt virus 2 infecting spinach in China - Xiaoxiao Gao; Yanan Liu; Liu Yang; Shuo Li; Yinghua Ji; Feng Sun (Journal of Plant Pathology, 2026)

Decoding osteosarcoma mechanobiology: PIEZO channels in tumor progression, immune remodeling, and pain - Baicheng Yang; Zhangfu Li; Jethro Wang Zih-Shuo; Timothy M. Pawlik; Shengji Yu (Cancer and Metastasis Reviews, 2026)

Experimental Study on the Mechanical Response and Damage Evolution Mechanism of Coal at Multiple Burial Depths Under True Triaxial Compensation Effect - Xin Xu; Guangming Zhao; Chongyan Liu; Minjie Qi; Qihang Zhang; Xukun Wu; Shuo Yang; Yian Chen (Rock Mechanics and Rock Engineering, 2026)

Rhizosphere inoculation with Streptomyces pactum is associated with sugar-related fruit quality and rhizosphere variation in goji berry (Lycium barbarum L.) - Yaping Ma; Jie Cao; Ping Yang; Yusupu Wayiti; Shuo Han; Kelong Wang; Alimire Ailimujiang; Yue Zhang (Plant and Soil, 2026)

Resveratrol alleviated inflammatory responses induced by cytopathic bovine viral diarrhea virus infection via NLRP3 inflammasome induced pyroptosis - Yang Han; Zhaofeng Zhang; Fenghua Jiang; Xinli Song; Shuo Jia; Yixin Lu (The Veterinary Journal, 2026)

Wildland-urban interface delineation using self-adaptive thresholding informed by historical wildfire patterns: a case study using very-high-resolution satellite imagery and deep learning algorithm - Shuo Dang; Xiaoyang Kong; Lei Fang; Jian Yang; Xiaorui Tian; Ziyue Chen; Zhiwei Xie; Jinyue Chen; Shilong Ren; Qiao Wang (Sustainable Cities and Society, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Toward rational selection of surfactants for coal dust control: A molecular framework for hydrophilic group–coal compatibility - Weizhi Zhao; Shaocheng Ge; He Liu; Liying Sun; Tianyi Yang; Chuanshan Yue; Shuo Liu (Process Safety and Environmental Protection, 2026)

Divergent trajectories of labile and acid-resistant soil organic carbon during 25 years of afforestation in a temperate desert - Sile HU; Ahmed I. ABDO; Siyi SUN; Jiacong ZHOU; Yundi BAI; Shuo LIU; Keisuke INOMURA; Megan SULLIVAN; Raúl OCHOA-HUESO; Meng LI; Yang YANG; Diego ABALOS; et al. (Pedosphere, 2026)

Selective separation of quartz from brucite at natural pH via ODDAC: From molecular dynamics to industrial potential - Yishen Sun; Jin Yao; Wanzhong Yin; Haoran Sun; Shuo Yang (Minerals Engineering, 2026)

Selenomethionine Alleviates LPS-Induced Intestinal Injury in Rats via Coordinated Modulation of the Microbial–Immune Axis - Yali Wu; Maocuo Zhou; Xinyi Liu; Shuo Liu; Wanlu Yang; Bin Ni; Yuan Li; Xu Wang; Pengfei Gao (Journal of Trace Elements in Medicine and Biology, 2026)

Hydrogen radical is also a critical reductive defluorination species in the Far-UVC-activated sulfite process - Xiangyang Hou; Shu Xu; Qiuling Lu; Kai Wang; Haonan Lu; Haochen Zhang; Yuying Li; Minchao Liu; Jin Jiang; Shuo Li; Jun Ma; Tiangang Luan; et al. (Journal of Hazardous Materials, 2026)

Comparative enhancement of UASB treatment of food waste anaerobic digestate by electric field and magnetite: Performance evaluation and mechanistic insights - Shuo Yang; Xinyu Liu; Hongbo Wang; Mei Li; Liping Qiu (Journal of Environmental Management, 2026)

Condensation thermo-hydraulic modeling of R290 in vehicle heat pumps: an integrated experimental and feature interpretation study - Wencong Shao; Tianyang Yang; Shuo Zhang; Mingxuan Huang; Rongrong Zhang; Huiming Zou (International Journal of Refrigeration, 2026)

Metagenomic sequencing reveals the similarities and differences in microbial community structure and diversity between fermented whey and Rubing cheese, a fresh goat milk cheese - Siying Yang; Xi Fu; Zhihong Yang; Tong Zhang; Chunli Lu; Lunzhao Yi; Qiong Zhao; Ying Gu; Shuo Wang (Food Research International, 2026)

Effects of Spinosin on nonenzymatic glycation of β-lactoglobulin: A mechanism study based on multi-spectroscopy analysis and molecular docking - Shuo Wang; Yanqing Zhang; Mengyu Zhang; Min Wang; Tan Yang; Junbo Xie (Food Chemistry, 2026)

Effects of citrus fiber as a partial phosphate replacer on the quality of grilled chicken sausages: a comprehensive study on water-holding capacity, texture, and flavor - Mingcheng Zhang; Shuo Hu; Miao Feng; Jie Yang; Xinyue Wang; Luyi Jin; Zaifei Zheng; Dengyong Liu; Xiao Ma; Changming Ma (Food Chemistry, 2026)

α-L-fucosidase derived from Lacticaseibacillus rhamnosus: rational mutation, enzymatic properties and application potential in the synthesis of 2′-fucosyllactose - Shuo Yang; Qiaohui Li; Xiangchen Meng; Yanwei Cui (Food Bioscience, 2026)

Chloride-repelling and interfacial hydroxyl enrichment synergy in Co-Pi@Cr2O3-CoP for high current density alkaline seawater electrolysis - Tingting Tang; Cheng Yang; Xinlong Huang; Shuo Cui; Xinjie Liu; Junyang Li; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2026)

Bio-based fiber electrodes via continuous interfacial polyelectrolyte complexation for electro-optical sensing textiles - Lihong Geng; Wenping Zhang; Zhengxi Hao; Xinyu Gan; Yuhang Li; Yang Ming; Shuo Shi; Xiangfang Peng (Chemical Engineering Journal, 2026)

Automatic Detection and Rejection of Defective Potatoes and Impurities Using Machine Vision and a Sorting System - Danyang Lv; Tao Zhang; Minsheng Wu; Ranbing Yang; Jian Zhang; Qimin Liang; Shuo Han (Potato Research, 2026)

Plant–soil feedback persists beyond host death to shape density-dependent plant competition - Ching-Lin Huang; Joe Wan; Shuo Wei; Chia-Hao Chang-Yang; Po-Ju Ke (Plant and Soil, 2026)

Long-Term Evolution of Groundwater Pollution Risk Before and After Groundwater Artificial Recharge (2002–2022) in the Yongding River Replenishment Area, Beijing - Xuehang Zhang; Baonan He; Shuo Ma; Jiangtao He; Fei Liu; Shanshan Yang; Yuanyuan Shi; Wei He; Baiju Yang (Exposure and Health, 2026)

Soil microbial biogeography: from maps to blueprints - Gui-Feng Gao; Shuo Jiao; Ke Dong; Xu Liu; Xin Xin; Beibei Chen; Kunkun Fan; Yu Shi; Congcong Shen; Teng Yang; Minyu Jing; Siyu Chen; et al. (Soil Ecology Letters, 2026)

Hydrothermal humification products with key roles in promoting straw degradation and soil carbon storage - Xiong-Xin Peng; Yulong Chen; Shuo Chen; Xiajie Zhang; Yansong Ma; Liuyang Lei; Zhuqing Liu; Fan Yang (Applied Soil Ecology, 2026)

Legume identity shapes soil multifunctionality and microbial networks in long-term cereal-based rotations - Shuting Yu; Shuo Li; Jin Yang; Kees Jan van Groenigen; Guiying Jiang; Mengru Wang; Beibei Wang; Fang Liu; Haitao Liu; Xiaolei Jie; Shiliang Liu (Applied Soil Ecology, 2026)

Experimental and numerical simulation study on flow and heat transfer characteristics of supercritical CO2 in a minichannel - Hong Liu; Zhigang Zhang; Shuo Yang; Guangliang Chen (Annals of Nuclear Energy, 2026)

Microbial remediation of PAHs in aquatic environments: advances, ssynergistic mechanisms, and emerging strategies - Shuo Yang; Mengying Wang; Han Wang; Qi Yang; Zhilin Yang (Archives of Microbiology, 2026)

Functional differences between healthy and stressed soils: Rare and abundant root exudates as a regulatory switch for quorum sensing in rhizosphere microbiota - Yueyi Liu; Zhenchao Wu; Zeming Ye; Liangyang Mao; Xiujun Tu; Yuhao Guo; Weige Yao; Ying Yang; Shuo Li; Jie Kang; Baiyan Cai; Jingping Ge (Plant and Soil, 2026)

Platelet membrane-fusing MSC-derived apoptotic extracellular vesicles enhanced cardiac repair after ischemia/reperfusion injury - Zhifeng Song; Fangshun Tan; Yu Jiang; Shuo Wang; ZhiYao Wei; Miao Yu; Hongrui Yu; YanXia Tu; Liaoming He; Weixian Yang; Haiyan Qian (Drug Delivery and Translational Research, 2026)

Genome-wide identification and expression analysis of the pectate lyase (PEL) gene family in soybean (Glycine max (L.) Merr. ) - Shuo Wu; Wanqing Du; Yu Han; Zhenggang Wang; Yujuan Gu; Xianlong Ding; Shouping Yang (Genetica, 2026)

A Global Path Planning Method for Unmanned Sailboats with Optimal Time Consumption - Yong Cai; Zhaozhao Zhang; Yixin Yang; Zhexuan Xu; Xing Gao; Shuo Liu; Tao Wang (Journal of Marine Science and Engineering, 2026)
Unmanned sailboats rely on wind and solar energy for long-duration marine missions, yet their navigation performance is strongly constrained by sail aerodynamics, hull hydrodynamics, and time-varying wind fields. Due to their underactuated nature and the critical influence of sailing speed on safety and efficiency, this paper addresses the time-optimal global path planning problem for unmanned sailboats in complex marine environments. A customized velocity prediction program (VPP) is developed to accurately estimate sailing speeds under different true wind angles, explicitly accounting for the drift angle effect. A time-efficient cost function is constructed and integrated into the Rapidly exploring Random Tree Star (RRT*) algorithm. To improve computational efficiency, three strategies, including goal-biased sampling, artificial potential field guidance, and adjacent domain expansion, are introduced. The proposed hybrid algorithm imposes no restrictions on path step size or direction, ensuring asymptotic optimality while complying with sailboat dynamic constraints. Comparative simulations and validation tests using multiple VPP datasets demonstrate that the method is feasible, efficient, and widely applicable for unmanned sailboat navigation.

Pentraxin 3 is an inflammation-related biomarker that distinguishes early-stage from mid-advanced cardiovascular-kidney-metabolic syndrome - Zhen Xu; Shuo Yang; Yuan Tan; Qian Zhang; He Wang; Jingjin Tao; Qi Liu; Zhongxin Li; Chong Wang; Liyan Cui (Molecular and Cellular Biochemistry, 2026)

An integrated morpho-molecular approach revealed dinoflagellate cysts diversity in ballast tank sediments of foreign ships - Caixia Yue; Zhe Tao; Zhaoyang Chai; Tao Li; Zhen Feng; Yangyun Wu; Zhangxi Hu; Yuyang Liu; Shuo Shi; Wanli Yang; Wen Tian; Ying Zhong Tang (Marine Pollution Bulletin, 2026)

Research on the coupling mechanism of explosion overpressure and flame as well as the damage effects of green hydrogen-blended natural gas - Qi Jing; Sheng Qi; Zhisong Wang; Shuo Zhou; Zhiyuan Yang; Yuntao Li; Laibin Zhang (Tunnelling and Underground Space Technology, 2026)

Design for all: Land use and street design interventions to promote all-age active travel - Leyu Zhou; Yihe Jia; Shuo Yang; Hui He; Liang Guo; Xiaoli Sun (Travel Behaviour and Society, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Coupled numerical investigation on focused wave interaction with offshore jacket platform and response assessment - Hong Lin; Qi Fan; Shuo Zhang; Kaixin Liang; Alexander Moiseevich Uzdin; Longcheng Wei; Zixuan Lin; Lei Yang (Ocean Engineering, 2026)

Effects of micro/nanoplastics on physiological and biochemical responses at different life history stages of Neopyropia yezoensis - Shuo Wang; Mingyang Zhao; Mengran Yu; Yujun Duan; Guang Yang; Guanyu Chen; Zewei Wang; Xin Wang; Zhihua Feng (Marine Environmental Research, 2026)

Integration of airborne geophysical data and saltwater intrusion modeling to assess alluvial aquifer dynamics: salinization, upconing, and management implications - Michael Attia; Shuo Yang; Yuqi Song; Frank T.-C. Tsai (Journal of Hydrology, 2026)

Automatic distortion correction and signal reconstruction in GPR data in tunnel lining surveys - Tian Lan; Jiaxin Yang; Chaoyi Huang; Shiwen Sheng; Zexi Wang; Xitao Sun; Shuo Zhao (Journal of Applied Geophysics, 2026)

From economic crop to high-value product: Fermentation of chestnut protein by Lactobacillus rhamnosus ameliorates chronic inflammation via the gut microbiota–SCFAs axis - Dongze Qin; Wenhui Fu; Haoxin Cui; Haiwei Liu; Hang Yang; Yaozhong Hu; Ruican Wang; Xuemeng Ji; Shuo Wang (International Journal of Food Microbiology, 2026)

Delivery technologies for chlorogenic acid: A comprehensive review of carrier platforms, performance, and challenges - Shumeng Hu; Runan Zhao; Shuo Yang; Wei Wang; Songfeng Yu; Xiangbo Zeng (Food Research International, 2026)

Lignin degradation enhancement in poultry manure and maize residue composting via flax retting waste liquid and biochar: Dominant microbial generalist species mediated - Tong Yang; Xiujun Tu; Xuan Tang; Yuhao Guo; Yueyi Liu; Zhenchao Wu; Hao Zhang; Ying Yang; Shuo Li; Weige Yao; Jinyu Du; Tingting Xu; et al. (Food and Bioproducts Processing, 2026)

A PVA-pCD2:1 hydrogel-based wearable patch for dual-mode sweat cholesterol and strain monitoring - Cancan Yang; Chongyue Bai; Kaixin Yang; Shuo Wang; Yuan Wang; Zhibo Zhang; Faming Gao; Huige Wei (Chemical Engineering Journal, 2026)

Highly sensitive H2O2 colorimetric sensing in tumor cells via stable phospholipid-coated CsCu2I3 peroxidase-like nanoenzyme - Jiatong Wang; Yang Yu; Yawen Fan; Sihan Chen; Meiyi Mo; Shuo Yang; Yangyang Zhao; Zixu Zhang; Hongxian Han (Analytica Chimica Acta, 2026)

PBK modelling of phthalates and their metabolites and the application in next generation risk assessment - Miaoying Shi; Ans Punt; Gopal Pawar; Shuo Yang; Hui Yang; Xudong Jia; Dawei Tang (Archives of Toxicology, 2026)

Pharmacological effect of rhCC16 on COPD: anti-senescence via the PI3K-AKT-mTOR pathway - Rui Gao; Shuo Wu; Chu-lin Zhang; Chao-feng Liu; Ting Li; Min Guo; Zhao-yang Chen; Hai-long Wang; Min Pang (Molecular and Cellular Biochemistry, 2026)

Isolation of lytic phage and its inhibition of multidrug-resistant Salmonella and its biofilm - Shuqi Wei; Jikun Wu; Luyang Zhou; Changxu Yu; Shuo Yang; Aofei Wang; Xiaoyu Wang; Zhe Yan; Xiaomeng Yue; Yanli Zhu (Veterinary Microbiology, 2026)

Intelligent and accurate recognition method of lining cracks under complex seam interference and engineering application - Xiaohua Xu; Yuanhai Li; Weiguo He; Shuo Yang; Chengbing Wang; Sen Wang (Tunnelling and Underground Space Technology, 2026)

Multi-scale reinforcement mechanisms and fatigue behavior of loess subgrade grouted with permeable polyurethane polymer - Lisha Yue; Xiaodong Yang; Loukai Du; Chengchao Guo; Shuo Liu; Lina Wang; Huqing Liang; Mengxiong Tang; Fuming Wang (Transportation Geotechnics, 2026)

An ovarian follicle-based angiogenesis microphysiological system for high-efficiency screening of anti-angiogenic drugs - Xuebing Yang; Jing Liang; Nan Sun; Lu Mu; Jinfeng Xiong; Ge Wang; Kaiying Geng; Xie’an Feng; Yibo Wang; Shuo Zhang; Xueqiang Xu; Yan Zhang; et al. (Science Bulletin, 2026)

Reliable and interpretable effluent quality prediction in wastewater treatment plants through the integration of physics-informed neural network and deep learning - Zaixing Li; Shuo Yu; Bin Yang; Lina Tang; Nannan Wang (Journal of Environmental Chemical Engineering, 2026)

Flame impingement to facilitate the stability of NH3-CH4 laminar diffusion flames: High-speed imaging and schlieren visualization - Yidu Tong; Chenyang Fan; Zheng Fu; Ye Liu; Huiyong Du; Bin Xu; Guorong Lin; Shuo Jin; Shuainan Yang; Mingliang Wei (Fuel, 2026)

Synergistic pore-acidity engineering in hierarchical H-beta zeolites for molecular sieving of ethylcyclohexane - Xue Ma; Xianjie Wang; Jinhui He; Jingdong Gou; Yaning Zhao; Akang Liu; Shuo Feng; Louwei Cui; Huiyong Chen; Jun Yang; Liuyi Pan; Dong Li (Fuel, 2026)

Influence of hydrogen blending ratio and ignition timing on trimethyl-phosphate-based suppression of hydrogen-blended natural gas explosions - Yanling Yang; Kang Cen; Hongfu Mi; Yulong Duan; Gang Xi; Shuo Wang (Fuel, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

Integrative microbiomics, metabolomics, and network pharmacology reveal microbial communities and flavor dynamics during traditional acetic acid fermentation of Shanxi aged vinegar - Baoqing Bai; Lanqi Zhang; Xianxian Luo; Ying Zhang; Wenyan Yan; Jinhua Zhang; Tao Bo; Hailong Qian; Yukun Yang; Shuo Wang (Food Bioscience, 2026)

Antibacterial effect and mechanism of plasma-activated water on Salmonella Typhimurium and Listeria monocytogenes - Wenzhe Liu; Rui Gao; Luyao Zhao; Shuo Yang; Hanfeng Zhang; Zhen Jiao; Qing Chi (Food Bioscience, 2026)

Bandgap-engineered iron-coordinated quercetin for enhanced visible-light photodynamic inactivation and strawberry preservation - Kaiyuan Su; Haoqian Chen; Zhuoran Guo; Yikai Song; Lin Yang; Jun Liu; Jianlong Wang; Wentao Zhang; Shuo Shi (Food Bioscience, 2026)

An efficient Mo-doped VS2 cathode material for rechargeable magnesium batteries - Guimiao Wang; Peilin Ran; Jingfei Guan; Baifei Wu; Shuo Wang; Min Liu; Hang Yang; Meilin Chen; Danmei Yu; Bin Zhang; Liyong Gan; Xiaoyuan Zhou (Chemical Engineering Journal, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

S/N induced coordination isomerism hydrogels on 3D-printed device for machine learning-assisted multiplex detection of heavy metal ions - Ziwuzhen Wang; Zixin Jin; Hongyu Shi; Zhiwei Liu; Yuqing Yang; Nawei Shi; Wanlin Jia; Meichao Zhang; Shuo Wang; Wei Sheng (Chemical Engineering Journal, 2026)

Laponite-reinforced marine bioinspired injectable self-healing adhesive chitosan-based hydrogel for infected wounds - Ruirui Guan; Yuhui Su; Shanshan Li; Shuo Yang; Xiaoyun Li; Xiaoying Wang (Carbohydrate Polymers, 2026)

Revealing the lifecycle evolution of hail-producing deep convective clouds by synergy of multi-source data - Qiang Li; Hongrong Shi; Yurui Xie; Rubin Jiang; Chaoying Wang; Yupeng Teng; Shuo Jia; Jianwei Wen; Disong Fu; Jiefan Yang; Xuehua Fan; Jinqiang Zhang; et al. (Atmospheric Research, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Laver cultivation mitigates zooplankton miniaturization in eutrophic coastal ecosystems - Sen Li; Jieqing Yang; Jinchen Yu; Tao Sun; Shuo Chen; Jin Zhou; Peng Zhang; Hong Huang (Hydrobiologia, 2026)

CRISPR/Cas12a-mediated electrochemiluminescent biosensor integrating Ag modified Co-doped metal-organic frameworks for dual detection of malathion and phorate - Ying Zhang; Wenke Liu; Rong Guo; Yanli Qi; Baoqing Bai; Jinhua Zhang; Nan Hu; Ying Gu; Yukun Yang; Shuo Wang (Analytica Chimica Acta, 2026)

From structure to design: experimental and AI-driven approaches in receptor-binding protein engineering for reprogramming phage host range - Shuo Xu; Shuqi Yang; Xin Jiao; Jiaqi Cai; Jiahui Wu; Jinjuan Qiao (Archives of Microbiology, 2026)

Targeting programmed cell death: a novel therapeutic paradigm for cancer based on mode-of-death classification - Xi Qiao; Ting Ye; Tinggai Wu; Xu Han; Tiantian Sun; Haiqiang Wang; Junru Jia; Yuanyuan Dai; Ruohan Yun; Shuo Jiang; Yuming Qin; Zhenzhen Liu; et al. (Apoptosis, 2026)

Physics-Prior-Augmented Deep Learning for Acoustic Convergence Zone Identification in Data-Scarce Marine Environments - Haoyu Wang; Shuai Chang; Hao Zheng; Shuo Yang; Jianxin He; Xiong Deng (Journal of Marine Science and Engineering, 2026)
High-precision identification of acoustic convergence zones (CZs) and acoustic shadow zones (SZs) is a core prerequisite for deep-sea sonar performance prediction and long-range underwater target detection. However, in data-scarce marine environments, traditional acoustic identification methods suffer from high environmental sensitivity and significant computational costs, while pure data-driven deep learning methods face dilemmas such as a lack of physical consistency and poor generalization on small samples. To address these issues, a three-level cascaded recognition framework based on physics-prior-augmented deep learning is proposed in this paper, enabling accurate segmentation of CZs and intelligent classification of sound field types under data-scarce scenarios. In this framework, physical acoustic principles are incorporated exclusively as priors through a training dataset generated by a Gaussian beam acoustic propagation code (Bellhop) and through hand-crafted geometric features derived post hoc from the initial segmentation outputs. Taking a typical deep-sea area in the Northwest Pacific Ocean as the research object, a hybrid dataset comprising 5000 simulated transmission loss images and 500 simulated images from a geographically distinct sea area is constructed. The sound field is categorized into four types: strong convergence, usable convergence, weak convergence, and shadow zone. In the first stage, the ResNet-34 backbone is improved by integrating deformable convolution and a global statistical feature module, which, combined with a joint loss function, achieves high-precision pixel-level segmentation of CZs and SZs, with the regional gray contrast reaching 86.9%. In the second stage, a customized dual-channel VGG16 architecture is designed to fuse the extracted geometric priors and visual features, achieving a sound field classification accuracy of 89.91%. In the third stage, a hybrid data augmentation technique combining Mixup and convolutional autoencoder is adopted alongside a transfer learning strategy to mitigate the data scarcity under cross-domain conditions, boosting the small-sample classification accuracy to 84.45%. The experimental results demonstrate that the models in each stage of the proposed framework significantly outperform traditional methods and baseline networks. This study provides a novel methodology and technical support for intelligent sound field identification in data-scarce marine environments. Finally, the core contributions and current limitations are summarized, and future research directions, such as constructing a dynamic hydrological parameter feedback mechanism and identifying three-dimensional complex sound fields, are prospected.

Oil Slick Detection in X-Band Marine Radar Imagery: Leveraging a Boundary-Aware SBR Feature and an Improved Whale Optimization Algorithm - Jianxun Rui; Jin Xu; Jianbin Yuan; Zekun Guo; Shuo Zhang; Yiteng Zhang; Qiuyu Fu; Boxi Yao; Yulong Yang; Wenhui Li (Journal of Marine Science and Engineering, 2026)
Marine oil spills pose a persistent threat to marine ecosystems and coastal economies, and their rapid and unpredictable spread requires timely and reliable monitoring. In X-band marine radar images, oil slicks usually appear as low-contrast dark targets embedded in heterogeneous sea clutter, making accurate segmentation particularly challenging. To address this problem, this study proposes a training-free two-stage oil slick detection framework that combines an improved Slick Boundary Ratio (SBR) feature with an improved Whale Optimization Algorithm (WOA). First, the improved SBR feature is used to extract the oil slick region of interest (ROI). Then, the improved WOA is employed to determine the global threshold for oil slick segmentation. Experimental results show that the proposed method achieves accurate and spatially coherent oil slick segmentation in complex radar backgrounds, with an Accuracy of 99.36%, a Precision of 85.73%, a Recall of 84.42%, an F1-score of 85.07%, and an Intersection over Union (IoU) of 74.01%. These results indicate that the proposed framework can effectively suppress false positives while maintaining strong detection sensitivity, thereby improving segmentation robustness in low-contrast marine radar scenes. Owing to its training-free design, the proposed method shows potential for shipborne and coastal oil spill monitoring applications.

Sustainable development model of resource-based rural: evaluation and optimization from the perspective of the industrial chain - Yunlong Dong; Qingsong Wang; Ziyang Li; Huibin Zhang; Yujie Zhang; Xueliang Yuan; Qiao Ma; Yue Xu; Shu Tian; Yuan Xu; Shuo Yang; Chengqing Liu (Environment, Development and Sustainability, 2026)

Talarombrevisone A, an β -aminopropionate with two polyketide units, isolated from an endophytic fungus Talaromyces brevis - Yun-He Tuo; Zhong-Duo Yang; Jian-Guo Chen; Cui-Juan Xu; Lin-bo Liu; Tian-Kun Zhao; Yue Li; Li-Bin Xia; Shuai Yu; Ai-Hong Zhao; Shuo Li (Natural Product Research, 2026)

Multiple macroeconomic benefits from mixed coastal flooding adaptation in China's coastal cities - Jiaju Lin; Shuyu Yang; Shuo Wang; Yuning Zhao; Yanhong Lin; Xiongzhi Xue; Yurong Ouyang (Ocean & Coastal Management, 2026)

Occurrence, source identification, and ecological risk assessment of heavy metals in sediments of Beihai Marine Ranching - Yao Guan; Manyu Huang; Bo Yang; Qiongyuan Su; Shuo Yu; Zuhao Zhu; Xianqing Ouyang (Regional Studies in Marine Science, 2026)

InceptionFormer: A deep learning framework for UAV LiDAR point cloud completion to improve tree parameters estimation in dense forests - Binhan Luo; Jian Yang; Shuo Shi; Ruilin Gan; Zhongliang Wu; Sihao Wang; Ao Wang; Lin Du; Wei Gong (Remote Sensing of Environment, 2026)

Research on oil pipeline gradual defect detection system based on ultrasonic guided wave acoustic velocity sensing - Xiaocen Wang; Mingrui Shi; Jiahao Zhou; Hongzhi Sun; Gaofeng Wang; Yiran Chen; Liqun Wu; Shuo Jin; Yunkun Fu; Yang An; Zhigang Qu (Process Safety and Environmental Protection, 2026)

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

Numerical and experimental analysis of wave-slamming characteristics of offshore floating photovoltaic structures - Jijian Lian; Lirui Yan; Shuo Yang; Ye Yao; Xiuwei Yang; Chao Liang (Ocean Engineering, 2026)

Functional diversity and catalytic preference of novel thermophilic catechol 2,3-dioxygenase for the biodegradation of aromatic pollutants - Yalin Yin; Shuxin Su; Shenmei Sun; Hengchao Zhu; Shuo Cheng; Ya Bian; Yue Yang; Jingjing Zhang; Jingjing Liu; Wei Wang (International Biodeterioration & Biodegradation, 2026)

Lability of riverine particulate organic carbon increased by water storage and extreme drought-heatwave events - Jixuan Lyu; Caroline L. Peacock; Yifan Zhang; Tao Liu; Yong Shi; Xiaomei Xu; Shengjing Liu; Yubing Qu; Shuo Zhang; Guang Yang; Dong Peng; Chonghao Chen; et al. (Geochimica et Cosmochimica Acta, 2026)

Improvement effect of air frying on the textural properties of surimi crisps based on heat and mass transfer characteristics - Hao Zhang; Meng Yang; Jiamu Kang; Jianan Liu; Xiufang Xia; Shuo Shi; Haijing Li (Food Research International, 2026)

Effects of hot-air pretreatment in semi-dry milling on rice starch gelatinization, rheological properties, and eating quality of wet rice noodles - Lei Wang; Mengran Guo; Songnan Li; Dan Zhao; Nisi Gao; Jie Chen; Yang Shuo (Food Chemistry, 2026)

A cellulose-based fluorescence aerogel for Hg2+ monitoring and its applications in food samples: From sensitive detection to efficient adsorption - Zhiyuan Meng; Qian Ye; Shuo Zhang; Yue Gu; Xu Xu; Yiqin Yang; Zhonglong Wang; Shifa Wang (Food Chemistry, 2026)

A novel 3D-printed flexible electrode with rGO/MWCNTs ink for capsaicin detection in chilli peppers - Jiachen Zhao; Huilin Hu; Chao Wang; Yingting Li; Xueyu Jiang; Ming Zhang; Fangkai Han; Ning Yang; Xiaodan Liu; Jiahua Wang; Yingli Wang; Shuo Duan; et al. (Food Chemistry, 2026)

Dietary patterns drive sphingolipid metabolic rewiring: Integrative insights from transcriptomics and sphingolipidomics - Shuo Yang; Nan Meng; Xincen Wang; Yanjun Liu; Peixu Cong; Changhu Xue; Jie Xu (Food Bioscience, 2026)

Lactic acid bacteria co-fermentation enhances the hypolipidemic potential of kombucha - Shuo Wang; Yu Su; Jiaxiu Wang; Yuhan Wang; Kaile Feng; Shuai Wang; Jia Yang; Lei Yuan (Food Bioscience, 2026)

The interface regulation strategy constructing high performance C3H6/C3H8 separation membranes via bio-based polyphenols - Dacheng Zhang; Qian Zhang; Ningning Gao; Leixin Yang; Yuchao Ma; Hang Li; Zhanfeng Zhao; Junkui Gao; Kaihua Li; Shuo Yang; Dengkun Shu; Huiguo Wang; et al. (Chemical Engineering Journal, 2026)

Gut-confined nano-interceptors for dual-mode nutrient sequestration and metabolic disease prevention - Shuo Li; Yan Zhao; Changhong Yuan; Zimeng Yang; Hengzhi Liu; Jianying Ye; Hongzhuo Liu; Zhonggui He; Yongjun Wang (Chemical Engineering Journal, 2026)

Integrated fabrication and applications of multifunctional electronic fabrics based on carbon nanotubes/carbonized silk fabrics - Haomin Wang; Xiaolin Liu; Bohan Yang; Jiaqi Su; Yang Ge; Shuo Li; Shengbo Sang (Chemical Engineering Journal, 2026)

Electric field as a priming trigger reshaping redox network for synergistic perfluorooctanoic acid degradation and humus synthesis during aerobic composting - Yueyi Liu; Zhenchao Wu; Hao Zhang; Xuan Tang; Weige Yao; Ying Yang; Shuo Li; Tong Yang; Jinyu Du; Tingting Xu; Yu Su; Yaqi Huang; et al. (Bioresource Technology, 2026)

Processed phellodendri Chinensis cortex attenuates diabetic nephropathy via ferroptosis inhibition through GPX4/SLC7A11/Nrf2/HO-1 signaling pathway - Yue Zhou; Gui Xu; Wenjing Ren; Yang Chen; Shiru Jiang; Shuo Zhang; Xiutong Ge; Hui Gao; Fan Zhang (Journal of Natural Medicines, 2026)

Experimental Study on Pyrolysis Characteristics of Elm Wood Strengthened by Mg(OH)₂-Assisted Torrefaction - Yanyang Mei; Baojun Wang; Jiapeng Gong; Shuo Yang; Weiwei Zhang (BioEnergy Research, 2026)

Integrated Single-Cell and System Network Analysis: Exploring Cellular Communication Network Complexity and Signal Transmission Dysregulation in Down Syndrome Brain - Xuehai Ma; Mengdan Wang; Jing Yang; Gang Li; Yan Wang; Hongkun Fang; Shuo Zhang (Neuroinformatics, 2026)

NFYA transcriptionally activates GPX4 inhibiting ferroptosis in colorectal cancer - Qingzhu Yang; Shuo Sun; Shuwei Dang; Zeyan Li; Lixue Feng; Qiaoyi Yang; Yanyan Sun; Xin Huang; Weiwei Zhang; Zhicheng Zhang; Guodong Li (Tissue and Cell, 2026)

Cr-induced electronic reconstruction in Bi@BiOx catalysts promotes CO2-to-formate conversion - Xin Xie; Ze Gao; Linglong Hu; Daming Yang; Shuo Geng; Guilian Li; Ming Feng (Journal of Environmental Chemical Engineering, 2026)

Optimized hybrid deep learning model for accurate prediction of effluent quality in wastewater treatment plants - Li Zaixing; Yu Shuo; Yang Bin; Tang Lina; Wang Nannan (Journal of Environmental Management, 2026)

Erratum to “Influence of hydrogen blending ratio and ignition timing on trimethyl-phosphate-based suppression of hydrogen-blended natural gas explosions” [Fuel 414 (2026) 138271] - Yanling Yang; Kang Cen; Hongfu Mi; Yulong Duan; Gang Xi; Shuo Wang (Fuel, 2026)

Visible light - driven antibacterial packaging based on whey protein isolate amyloid fibrils for food preservation - Shuo Zhang; Yunlong Wang; Mengjun Wang; Chongjiang Cao; Zhiping Yang; Linyu Nian (Food Chemistry, 2026)

Enhanced ultra-sensitive detection of peanut allergen Ara h 3 on immunochromatographic paper based on surface-enhanced Raman spectroscopy and AuNBs@PDA dual signal amplification strategy - Shuo Yang; Jinglong Qu; Yang Qin; Shuaibing An; Kaiqiang Huang; Yaling Wei; Jun Xi (Food Chemistry, 2026)

The role of VxrB in Vibrio harveyi and evaluation of a VxrB knock-out as a vaccine candidate - Yinhui Peng; Xin Lu; Ming Liu; Shuo Hu; Lulu Liu; Renjie Li; LuJia Yang; Xiaohui Cai; Shuanghu Cai (Fish & Shellfish Immunology, 2026)

Contrast antibiotic activities from muddy and sandy coasts and their potential controls - Shuo Zhang; Lijia Qu; Xintong Li; Ye Lu; Yang Cui; Jianwei Dong; Hui Xie (Environmental Pollution, 2026)

Complete upcycling of iron phosphate slag via ammonium sulfide: Synchronous recovery of phosphorus, Fe7S8/C catalyst, and elemental sulfur - Shaoxiang Yang; Fei Zhang; Yikun Li; Fang Wang; Jiayu Feng; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Lijuan Jia (Chemical Engineering Journal, 2026)

Reduced-order modeling of particle-fluid flows with heat transfer via a curriculum learning approach - Michael Castro; Shuo Li; Kai-en Yang; Toshiki Imatani; Mikio Sakai (Chemical Engineering Journal, 2026)

In situ cultivation and chromogenic screening: a dual approach for rapid discovery of PDE1 inhibitors from pinus-tree associated microbes - Cui-Juan Xu; Shuo Li; Zhong-Duo Yang; Lin-Bo Liu; Yun-He Tuo; Yong-Jiao Niu; Lei-Lei Chen; Jian-Guo Chen; Tian-Kun Zhao; Ai-Hong Zhao (World Journal of Microbiology and Biotechnology, 2026)

Endometrial microbiota-dimethylglycine-Treg cell axis affects endometrial receptivity in recurrent implantation failure - Fen-Ting Liu; Ping Zhou; Feng Deng; Bao-Ying Liao; Zi Yang; Di Sun; Heng Pan; Yang Yu; Shuo Yang; Rong Li (Science China Life Sciences, 2026)

Efficacy and Safety of Temozolomide for the Treatment of Advanced or Recurrent Ependymoma: A Meta-Analysis - Rong Zhang; Binyan Liu; Zhuang Kang; Shenglan Li; Yingfan Sun; Jiachen Wang; Xin Yang; Shuo Yin; Feng Chen; Wenbin Li (Journal of Pharmaceutical Innovation, 2026)

The impact of the wind farm on the vegetation and the microclimate via remote sensing: a case study in Hebei Province, China - Tingting Fei; Dangui Lu; Yan Li; Danlin Li; Shuo Tian; Akbar Amar; Xiuchun Yang; Zhouyuan Li (Energy, Ecology and Environment, 2026)

Genome-Wide Identification and Expression Analysis of EBP Genes in Cotton - Lingyu Hao; Dongyun Zuo; Qiaolian Wang; Limin Lv; Youping Zhang; Yi Yang; Xue Zhang; Shuo Zhang; Guoli Song; Hailiang Cheng (Biochemical Genetics, 2026)

General Biogeographic Rules and Lineage‐Specific History Shape the Assembly of Asian Tropical Megadiversity - Hao Wu; Bing‐Yue Zhu; Jing Yang; Qiang Zhang; Zhen‐Ping Shi; Yan‐Jing Shi; Xiao‐Chen Zhao; Pei‐Yi Yang; Ke‐Xin Fan; Guang‐Shun Li; Si‐Qi Hu; Yee Wen Low; et al. (Journal of Biogeography, 2026)
Aim Tropical Asia's extraordinary plant diversity is thought to be intrinsically linked to its dynamic geological history. However, quantifying the precise evolutionary processes that assembled this diversity across the archipelago remains challenging. A recently proposed biogeographic framework classifies the functional roles of different regions as “radiators,” “incubators,” “corridors” or “accumulators,” offering a useful framework to analyse this complexity. Here, we aim to provide a critical, independent test of this framework using the megadiverse tree genus Syzygium as a model system. Syzygium originated on the Sahul Shelf, contrasting with the Indochinese origin of rattan palms used in the original framework validation. Location Tropical Asia, Pacific Islands and Africa. Methods We analysed the complete chloroplast genome of 200 species of the genus Syzygium and performed phylogenetic analysis to estimate divergence times, ancestral region reconstruction, and estimated diversification and extinction rates. We then analysed the relationship between regional area and the dispersal of species and examined speciation and dispersal patterns in relation to the geographical environment. Results Our comprehensive chloroplast phylogenomic analysis indicates rapid diversification of Syzygium commencing ~12 million years ago, coinciding with shelf collision. Biogeographic reconstructions indicate that while the framework's general principles hold – continental shelf act as “radiators” and isolated islands as “incubators” – the specific geographic roles vary depend on lineage history . Main Conclusions Our study validates the radiator‐incubator model as a general feature of tropical Asian evolution but refines it by demonstrating that historical contingency is key to understanding the assembly of Earth's richest biota. Tropical Asian plant diversity reflects a unique geological history of continental shelf collision and dynamic island geography, offering insights into biodiversity evolution in other geologically active regions worldwide, highlighting the importance of maintaining large, connected natural areas and dispersal corridors for preserving the evolutionary processes that generate Earth's botanical richness.

Molecular characteristics of apolipoprotein M and its biological functions in kidney diseases - Jingjin Tao; Yuan Tan; Shuo Yang; Qian Zhang; Zhongxin Li; Qi Liu; He Wang; Liyan Cui (Molecular and Cellular Biochemistry, 2026)

Physics-enhanced deep learning for sea surface temperature forecasting via multi-scale feature integration - Hu Li; Qingao Liu; Tianping Wang; Haoyu Wang; Shuo Yang (Frontiers in Marine Science, 2026)
Accurate prediction of sea surface temperature (SST) is essential for marine environmental monitoring and climate forecasting. However, most existing deep-learning-based approaches rely heavily on data-driven methodologies and lack sufficient integration of physical mechanisms, thereby limiting their physical consistency and interpretability. To overcome this limitation, this study introduces a multi-source coupled prediction neural network (MSCPNN), which incorporates temperature, salinity, and current dynamics into a multi-scale feature learning framework. Built upon the multi-feature physical neural network (MFPNN), the proposed model integrates a convolutional block attention module (CBAM), where channel attention adaptively models the multi-factor coupling among temperature, salinity, and currents, and spatial attention captures multi-scale spatial patterns in SST. Using high-resolution reanalysis data from the South China Sea spanning 2011 to 2020, comprehensive experiments were conducted comparing MSCPNN with MFPNN and PCL-MFPNN. The results demonstrate that MSCPNN significantly outperforms the baseline models across multiple evaluation metrics—including RMSE, correlation coefficient, PSNR, and SSIM—achieving an average reduction in RMSE of 17% and an increase in correlation coefficient of 0.035, which reflects higher predictive accuracy and improved physical consistency. Ablation studies further validate the superiority of multi-factor coupling over single-factor alternatives and clarify the distinct contributions of salinity and currents to SST prediction. Overall, MSCPNN advances the accuracy and stability of long-term SST forecasting while providing a more interpretable framework for intelligent ocean prediction.

Evaluation of kidney biological age based on IgG N-glycosylation profiles and its association with chronic kidney disease in the context of predictive, preventive and personalized medicine - Haotian Liu; Shiyun Lv; Haibin Li; Runhuang Yang; Yixing Tian; Jinqi Wang; Xia Li; Shuo Chen; Guohong Zhang; Xiuhua Guo (EPMA Journal, 2026)

From identification to prevention: a kiwi disease diagnosis system integrating vision and large language models - Xiaopeng Li; Shuo Yang; Shuqin Li (Computers and Electronics in Agriculture, 2026)

A generative AI-Driven framework integrating CNN-VLM-LLM for intelligent crop disease diagnosis and control strategy generation - Shuo Yang; Junxian Guo; Jiangtong Yu (Computers and Electronics in Agriculture, 2026)

A generative AI-enhanced multitask learning framework for weed detection and drivable area segmentation in smart agriculture - Xuewei Chao; Shuo Yang (Computers and Electronics in Agriculture, 2026)

Effects of vitamin D3 on glucose and lipid metabolism in Chinese sturgeon (Acipenser sinensis) - Xuetao Shi; Kan Xiao; Wei Jiang; Hongtao Huang; Pei Chen; Shuo Zheng; Guangfu Hu; Jing Yang (Aquaculture, 2026)

EKTFD: Precise-guided empirical knowledge and time-frequency domain data joint-driven machine learning method for rock mass intelligent perception - Wenkun Yang; Zuyu Chen; Haitao Zhao; Jianchun Li; Shuo Chen; Chong Shi; Yangtao Li; Dong Chen (Tunnelling and Underground Space Technology, 2026)

Heterologous overexpression of apple MdWAPL1 promotes fruit shape and alters fruit quality in tomato - Wenyun Shen; Pengda Cheng; Xiaomei Li; Zhiyu Zheng; Shuo Zhang; Fang Ma; Abid Khan; Xinyue Yang; Zhongxing Li; Yutian Zhang; Fengwang Ma; Chundong Niu; et al. (Plant Science, 2026)

Low phosphorous and polyethylene microplastics synergistically increase Cd uptake in Lolium rigidum: Insights into underlying mechanisms - Xunzhe Yang; Ping Yun; Shuo Liu; Haiqin Zhang; Yonghong Zhou; Sergey Shabala; Yinglong Chen (Journal of Hazardous Materials, 2026)

Paleo-Pacific slab break-off revealed by Cretaceous I-type and peralkaline A-type granite associations in the Cathaysia Block, SE China - Ao Li; Wu-Bin Yang; Ning-Bo Li; Shuo Xue; He-Cai Niu; Qiang Shan (Journal of Asian Earth Sciences, 2026)

Precambrian crustal evolution of the southern margin of the North China Craton: Evidence from the Paleo–Mesoproterozoic sedimentary rock - Shuo Wang; De-Bin Yang; Xiang-Yu Yan; Ke Wu; Jian-Ning Liu; Rui-Qing Xue (Journal of Asian Earth Sciences, 2026)

Time-Feature Fused Transformer model: A study on TBM performance prediction and attention evolution patterns - Wenkun Yang; Zuyu Chen; Haitao Zhao; Jianchun Li; Shuo Chen; Chong Shi; Dong Chen; Jing Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

Novel nucleoside-degrading Lactiplantibacillus plantarum and Levilactobacillus brevis isolated from kimchi: In vitro screening, probiotic evaluation, and potential application in yogurt - Xinru Yang; Shuo Fan; Jue Xu; Hui Liu; Xiaomeng Wu; Xiaoqun Zeng; Daodong Pan; Maolin Tu (Innovative Food Science & Emerging Technologies, 2026)

Responses of a harmful algal bloom-causing dinoflagellate Karenia mikimotoi to elevated temperature and high N:P ratio - Xiang Ye; Wen-Jing Sun; Wei-Ping Zhang; Yang Zhou; Shuo-Yu Zhang; Can-Jun Cai; Shu-Feng Zhang; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Harmful Algae, 2026)

Competitive adsorption and temperature-dependent diffusion of O2/CO/CO2 in oxidized coal: Implications for coal spontaneous combustion - Yang Zhou; Shuo Li; Lulu Fan; Ruizhi Chu; Xianliang Meng; Ning Li; Haichen Liu; Xiaofeng Jiang; Yongzhou Wan; Shi Yu; Jingbo Li; Xiaomeng Du (Fuel, 2026)

Microencapsulation of high loaded algae oil powders: Spray drying of electrostatic self-assembled emulsion stabilized by SPI and cellulose nanocrystals - Shuo Wang; Liuping Fan; Yang Ni; Jinwei Li (Food Hydrocolloids, 2026)

FSMP storage stability: Comparing MASLT & GSI shelf-life models - Hong Yang; Ling Hou; Wei Guo; Mengxi Yu; Hongmei Sun; Shuo Zhang; Fang Yu; Hui Xiao; Liyuan Liu; Shuhong Ye (Food and Bioproducts Processing, 2026)

Aging processes and microplastic release behavior of aquaculture implements - Yujun Duan; Xin Wang; Kexin Song; Shuo Wang; Lei Wang; Guang Yang; Zhihua Feng (Environmental Pollution, 2026)

Synergistic enhancement of lithium storage by zinc single-atom regulation in Co2P/carbon composite anodes - Kexin Wang; Xu Zhang; Miao Tian; Xiang Li; Xingyang Wu; Jiahao Qiu; Haotian Song; Shuo-Wang Yang; Jing Lyu; Zhongkai Hao; Guo Qin Xu (Chemical Engineering Journal, 2026)

Switchable electrolytic pathways for nitrate to ammonia or dinitrogen on a robust PdCu/nickel foam cathode - Siyang Gu; Yiyun Cao; Shuo Li; Yunmei Du; Zhaodong Ding; Yuanhong Ding; Yang Zhang (Chemical Engineering Journal, 2026)

Simulated moving bed for steady methane chemical looping reaction - Kai Liu; Taixiu Liu; Jiquan Luo; Shuo Gao; Yang Li; Qibin Liu; Hongguang Jin (Chemical Engineering Journal, 2026)

Synthesis of a porous deep eutectic solvent based on supramolecular deep eutectic solvent and its application in extractive−oxidative desulfurization - Chenhua Shu; Jun Yang; Jiayi Zhang; Helin Fan; Xingyu Dai; Dan Luo; Shuo Mi; Tonghua Sun (Chemical Engineering Journal, 2026)

Decoupling multicellular activation circuits: MPDA-mediated co-delivery of quercetin/simvastatin for potent hepatic fibrosis reversal - Lu Zhang; Huan Shen; Boheng Liu; Tingting Liu; Yun Mei; Bin Li; Yang Liu; Gang Cao; Shuo Yu (Chemical Engineering Journal, 2026)

Phosphorus‑nitrogen synergistic flame retardancy in lyocell fiber composites: Mechanistic investigation - Chunzu Cheng; Qingbo Zhao; Zhongkai Xu; Min Gao; Dong Zhang; Jia Shi; Shuo Yang; Jigang Xu; Bowen Cheng (Carbohydrate Polymers, 2026)

Green fluorescent carbon dots remodel soil microbial communities and regulate gene expression to enhance the salt stress adaptability of wheat - Tiantian Zheng; Qing Chi; Yue Wang; Ting Li; Wenzhe Liu; Luyao Zhao; Shuo Yang; Dongjie Cui; Ruqiang Xu; Zhen Jiao; Hanfeng Zhang (Plant and Soil, 2026)

Predicting macrolide resistance in pediatric Mycoplasma pneumoniae pneumonia: A machine learning modeling study - Shuo Yang; Xinying Liu; Huizhe Wang; Yaowei Han; Dan Sun; Huanmin Li; Liting Ma; Haokai Wang; Xinmin Li (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Varied growth patterns of 25 fish species in the Yunnan section of the Lixian River - Shuo Yang; Jing Ye; Shiqi Zhong; Jinfeng Zhao; Bolin Chen; Rong Huang; Zhijian Wang; Yaqiu Liu; Xiaohong Liu (Environmental Biology of Fishes, 2026)

Willing or unable? The cognitive–resource mismatch behind farmers' adaptive behavior under agricultural disasters - Zhiyuan Zhu; Yongzhong Feng; Binkun Wu; Shuo Zhang; Xu Ma; Guangxin Ren; Gaihe Yang (Agricultural Systems, 2026)

Biological characterization and genomic analysis of Kpp-61, a lytic bacteriophage against K1-type Klebsiella pneumoniae - Xin Jiao; Shuqi Yang; Jiayi Liu; Shuo Xu; Jiahui Wu; Xiao Dong; Jinjuan Qiao (Archives of Virology, 2026)

Shifts of dinoflagellate cyst assemblages over the past 100 years indicate the history of harmful algal blooms, eutrophication, and possible alien genotype invasion around the Shandong Peninsula, China - Zhaoyang Chai; Zhe Tao; Caixia Yue; Ruoxi Li; Yuyang Liu; Shuo Shi; Wanli Yang; Kun Sun; Ying Zhong Tang (Marine Pollution Bulletin, 2026)

Physical feature shared online transfer learning framework for cross-engineering rock mass quality perception during TBM excavation - Wenkun Yang; Zuyu Chen; Haitao Zhao; Jianchun Li; Shuo Chen; Chong Shi (Tunnelling and Underground Space Technology, 2026)

Role of lncRNA H19 modification (m6A methylation) and YTHDC1 in high glucose induced human microvascular endothelial cell biological behaviors - Jingcun Sun; Zhongyong Zhang; Huajun Li; Yuqian Chi; Shuo Yang; Guiye Zhang; Zhaozhen Li; Hongliang Zhang (Tissue and Cell, 2026)

The modulatory effect of high frequency rTMS on cortical beta bursts in Parkinson’s disease - Runze Li; Shuo Yang; Keke Feng; Yao Yao; Longlong Wang; Shaoya Yin; Guizhi Xu (Next Research, 2026)

Seasonal dynamics of plankton networks and copepod selection strategies in the laver cultivation area of Haizhou Bay, China: based on sparse correlations for compositional data analysis - Sen Li; Hong Huang; Jinchen Yu; Tao Sun; Shuo Chen; Jin Zhou; Yunrong Shi; Peng Zhang; Jieqing Yang (Marine Environmental Research, 2026)

Unveiling ODDAC's selective adsorption mechanism for magnesite-quartz reverse flotation via TOF-SIMS microscopic site mapping - Yishen Sun; Jin Yao; Wanzhong Yin; Haoran Sun; Shuo Yang; Yingcai Chen (Journal of Environmental Chemical Engineering, 2026)

River remediation driven by micro-nano bubbles: From laboratory verification to in situ application - Fangshu Wang; Wen Yang; Shuo Li; Guosheng Wang; Dongmei Wang; Jicheng Duan; Jianyong Feng; Xiaowan Dong; Shuoyang Wang; Qingyang Bi; Dong Chen (Journal of Environmental Chemical Engineering, 2026)

From synthesis to application: A review of carbon quantum dots in photo-enhanced deep oxidation for wastewater treatment - Yalun Yang; Shuo Li; Heshan Zheng; Junfeng Niu; Yoong Kit Leong; Jo-Shu Chang (Journal of Environmental Chemical Engineering, 2026)

Experimental investigation of helium gas heat exchangers for vibration and thermal noise control in closed-cycle cryostats - Shuo Yang; Hejun Hui; Yanyang Jiang; Meng Guo; Zhenhua Jiang; Yinong Wu; Shaoshuai Liu (International Journal of Refrigeration, 2026)

Explainable spatiotemporal deep learning for subseasonal super-resolution forecasting of Arctic sea ice concentration during the melting season - Jianxin He; Yuxin Zhao; Shuo Yang; Woping Wu; Jian Wang; Xiong Deng (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Multi-objective optimization of proton exchange membrane water electrolyzer based on machine learning - Hongwei Zhan; Zhimin Yang; Shuo Wang; Di Wu; Menghui Yuan; Kaiyang Li; Yanqiang Kong; Lijun Yang; Xiaoze Du (Fuel, 2026)

Inhibiting browning in ready-to-eat oysters: The efficacy and mechanism of L-cysteine combined with light-proof nitrogen-filled packaging during accelerated storage - Ying Luo; Jie Xu; Shuo Lv; De-Yang Li; Yuan-Yuan Hu; Xiao-Yang Liu; Fa-Wen Yin; Da-Yong Zhou (Food Research International, 2026)

From aroma to off-flavor: Metabolomics unveils the metabolic double-sided nature of traditional Chinese fermented foods - Wei Ruan; Jiayu Liu; Huanxin Guo; Shuo Yang; Mengmeng Niu; Hang Yu; Xiangchen Meng (Food Chemistry, 2026)

The multi-carboxyl metal-organic framework MIL-101(Fe) effectively adsorbs total purines from whole soybean seeds - Deshuai Shao; Cui He; Na Li; Yuqing Gao; Xiaoyu Hu; Yingrun Cai; Qinqin Zhang; Jiahui Yao; Shuo Wang; Yifan Yang; Jiayi Pan; Huihui Gao; et al. (Food Chemistry, 2026)

Sulfur-induced electronic coupling in g-C3N4/Ti3C2Tx-MXene 2D/2D heterojunction enables highly efficient solar-driven disinfection - Rong Ma; Xiaochun Tao; Shuo Li; Chenglong Chen; Qinqin Liu; Shaosheng Rao; Juan Yang (Chemical Engineering Journal, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

An integrated engineered microbial system for copper biosorption, real-time monitoring, and magnetic recovery in water remediation - Mingzhu Huang; Yanzi Huang; Xindong Yang; Wenxin Liu; Li Kong; Shuo Gao; Hao Cheng; Xuelan Chen (Bioresource Technology, 2026)

Experimental study on the high-temperature co-pyrolysis of Elm and waste textiles - Yanyang Mei; Baojun Wang; Jiapeng Gong; Shan Zhang; Shuo Yang (Biomass and Bioenergy, 2026)

A new isoflavone from processed root barks of Paeonia suffruticosa and their procoagulant activity - Shuo-Guo Li; Rui Yang; Mi-Mi Lu; Shu-Mei Wang; Jiang Meng (Natural Product Research, 2026)

Characteristics of Clostridium perfringens from sheep (Ovis aries) flocks in Northern China - Shuo Liu; Wen-Xu Tan; Kai-Meng Shang; Li Guo; Quan Zhao; Hong-Bo Ni; Bei-Ni Chen; Xing Yang; Xiao-Xuan Zhang (Veterinary Research Communications, 2026)

Curcumin alleviates ferroptosis in CCl₄-induced acute liver injury in vitro: involvement of TXNIP/NLRP3 inhibition and SLC7A11/GSH/GPX4 activation - Wei Zhang; Ziqi Liu; Changle Dong; Huimin Yang; Yunchao Zhang; Shuo Li; Yinsheng Qiu; Lingyun Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Assessing global wheat supply security based on a cascading failure model in the context of the Russia-Ukraine conflict - Laijun Zhao; Wanying Xie; Huiyong Li; Shuo Sun; Hongru Yi; Lixin Zhou; Pingle Yang (Food Security, 2026)

Experimental and numerical research of thermo-hydraulic characteristics of liquid lead–bismuth eutectic and S-CO2 in a MCHE - Hong Liu; Zhigang Zhang; Shuo Yang; Guangliang Chen; Zhibin Rao; Runze Wang (Annals of Nuclear Energy, 2026)

An ensemble model for predicting Hyphantria cunea invasion risks: implications for ecological monitoring and management - Hongwei Zhou; Yunbo Yan; Yantao Zhou; Yifan Chen; Haochang Hu; Shuo Li; Yue Wang; Zihan Xu; Di Cui; Yumo Chen; Jun Yang; Jun Chen (Biological Invasions, 2026)

Monocyte-mediated mechanisms in idiopathic pulmonary fibrosis: opportunities for early intervention - Zhiguo Mao; Ying Liu; Chengfu Han; Xingyi Yang; Xiangke Lin; Shuo Tian; Mingsan Miao (Apoptosis, 2026)

Deciphering the sexually dimorphic endocrine regulatory network of Pacific white shrimp (Litopenaeus vannamei) after unilateral eyestalk ablation - Ying Chen; Zhihui Yang; Xiaojuan Sun; Shuo Bai; Guanrong Feng; Ying Du; Diane A. Blake; Jingjie Hu; Zhenmin Bao; Yue Sun; Zhe Qu (Marine Life Science & Technology, 2026)
Eyestalk ablation (ESA) is widely used in decapod aquaculture to induce maturation by altering endocrine function. While pronounced sexual dimorphism in growth and development is common in decapods, the endocrine regulatory mechanisms underlying sex-specific responses to ESA remain unclear. Here, we comprehensively investigated sexual dimorphic responses to unilateral ESA in the most important farming decapod— Litopenaeus vannamei —via multi-tissue transcriptomics. Integrated mRNA and sRNA profiling of eyestalk and hepatopancreas tissues revealed pronounced sex-biased differential expression. Only a limited set of differentially expressed genes (DEGs) and transcripts (DETs) were common to both males and females (101 DEGs and 16 DETs in eyestalk; 478 DEGs and 231 DETs in hepatopancreas), with the majority being sex specific. We found unilateral ESA could trigger responses in hormonal pathways and metabolic processes related to carbohydrates, lipids, and proteins, while sex differences in metabolic (lipase and amylase activities), immune responses, and hormone signaling (ecdysteroids and sesquiterpenoids) were revealed. Co-expression network analysis identified sex-specific responsive modules and hub genes (e.g., Trypsin and Chit1 ). In addition, we found sexually dimorphic post-transcriptional regulation, including widespread alternative splicing, polyadenylation-induced 3′UTR length variation (longer in females and shortened in males), and microRNA–target interactions (e.g., miR-750, miR-2788, and miR-263a/b). Our study systematically reveals sexually dimorphic responses of L. vannamei to unilateral ESA from physiological, gene regulatory network, and post-transcriptional regulation aspects, advancing the understanding of the endocrine and molecular basis of sex dimorphism in decapods and offering insights for shrimp aquaculture improvement.

A cucurbitane-type triterpene from Sorbaria kirilowii (Regel) Maxim. and its PDE1 inhibitory activity - Ke Yang; Shuo Li; Zhong-Duo Yang; Bing Sun; Tian-Kun Zhao; Ai-Hong Zhao; Jian-Guo Chen; Yong-Jiao Niu; Sahyun Kim (Natural Product Research, 2026)

The Evolution and Development of Integrated Coastal Zone Management in China Since the 1950s - Yanping Li; Wenjing Zheng; Tuanxi Dong; Yingzi Yang; Shuo Wang; Yinuo Kang; Yilin Liu; Yuqing Chen; Dahai Liu (Coastal Management, 2026)

FM-SAM: individual tree crown delineation and classification based on Segmentation Anything Model (SAM) and YOLOv10 in UAV imagery for forest monitoring - Haohua Que; Haojia Gao; Weihao Shan; Mingkai Liu; Jianshuo An; Fei Deng; Shuo Feng; Xinghua Yang; Lei Mu (Computers and Electronics in Agriculture, 2026)

Schisantherin A alleviates hepatotoxicity induced by diosbulbin B in mice via suppressing metabolic activation of diosbulbin B - Shuo Wang; Bufan Yang; Guangyao Li; Dongju Lin (Toxicology and Applied Pharmacology, 2026)

Lipid droplets-mitochondria interaction involved in testosterone synthesis in Leydig cells of dairy goats (Capra hircus) - Fang-e Zhao; Shuo Wang; Xinge Zhang; Haorui Yang; Mengyuan Zhou; Hongbo Chen; Na Chen; Yongjie Wu; Shulin Chen; Jun Liu; Hong Chen (Theriogenology, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Beyond sucking pests: Spirotetramat disrupts sex pheromone biosynthesis and induces transgenerational population suppression in lepidoptera insect, Conogethes punctiferalis - Shuo Huang; Yuxin Chu; Yao Zhang; Yihan Zhang; Xifa Yang; Mengfang Du; Xiaoguang Liu; Shuangyan Yao; Shiheng An (Pesticide Biochemistry and Physiology, 2026)

Fungal diversity, pathogenicity, and fungicide sensitivity in leaf diseases of Chinese cabbage from Heilongjiang Province, China - Shuo Wang; Siqi Ma; Yiwen Wang; Xilang Yang; Chenyang Jiao; Chunbo Yang; Xuemeng Wang; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (Physiological and Molecular Plant Pathology, 2026)

Sparse deconvolution beamforming for compact AUV-mounted passive inverted ultra-short baseline systems - Yi Zhu; Zhiwen Qian; Shuo Yang; Yufei Zhang; Jie Li; Jingsheng Zhai (Ocean Engineering, 2026)

Formononetin protects against oxaliplatin-induced peripheral neurotoxicity via Nrf2/HO-1 antioxidant pathway without impairing anticancer efficacy - Yang-Chen Chang; Wan-Hsuan Lin; Horng-Huey Ko; Yi-Ching Lo; Hsun-Shuo Chang; Hui-Ching Lin; Yih-Fung Chen (NeuroToxicology, 2026)

Starch/polyvinyl alcohol based smart packaging reinforced with recycled pitaya peel-derived anthocyanins for dual-function pork freshness monitoring and shelf-life extension - Lili Ma; Wenyu Han; Yurou Jiang; Zhenquan Yang; Dan Xiong; Shuo Wang; Wenyuan Zhou; Xin-an Jiao; Lei Yuan (Meat Science, 2026)

Upcycling sediment wastes into S-scheme heterojunctions for efficient photocatalytic tetracycline degradation: Performance, DFT calculations and toxicity assessment - Ni Su; Shuo Yang; Mohan Wang; Yuanyuan Liu; Ruixian Yuan; Hefan Zhang; Zhao Liang; Changyu Lu (Journal of Environmental Management, 2026)

Preparation of acetamiprid monoclonal antibody and its application in colorimetric and photothermal dual-mode immunochromatographic assay based on cu-doped PDA composite - Zixin Jin; Yuqing Yang; Hongyu Shi; Zhiwei Liu; Dongmei Bai; Ziwuzhen Wang; Caixu Fan; Yamin Liu; Qiuyue Ji; Wei Sheng; Shuo Wang (Food Chemistry, 2026)

Distribution and potential risks of antibiotics in inland lakes in China - Kejian Chu; Shuo Qin; Zonghao Tian; Fuzhu Ye; Xuan Yang; Li Gu; Yuanyuan Liu; Yang Zhang; Yuanyuan Sha (Environmental Research, 2026)

Microwave-triggered plasma catalysis over Cu/CuOx wires: Synergistic CO2 reduction via enhanced discharge and dynamic oxygen vacancies - Shuning Xiao; Yang Xu; Haotong Ma; Xiuwen Zhao; Hao Zheng; Shuo Wang; Zhanshuo Tao; Hexing Li (Chemical Engineering Journal, 2026)

Rational design of zwitterionic electrolyte additives to induce preferential deposition of Zn(100) to achieve high performance Zn||I2 battery - Shuo Yang; Zhanpeng Zhang; Xingyu Zhu; Weina Xu; Jing Zhang; Yushuang Chen; Biao Wang; Heng Chen; Yuanmin Zhu (Chemical Engineering Journal, 2026)

The p -JNKThr183/Tyr185 / p -Keap1Thr43 /Keap1 axis mediates arsenic-induced endothelial dysfunction by coordinating Chaperone-mediated autophagy with macroautophagy - Jinyu Li; Jin Cheng; Zhihan Yang; Lin Gao; Qiaoling Liu; Jing He; Yishan Dong; Shuo Wang; Jing Cui; Ziqi Xu; Dianjun Sun; Wei Zhang (Chemico-Biological Interactions, 2026)

Cyanobacterial biochar and cyanobacteria-bamboo growth elicitors for establishing a self-sustaining nitrogen cycle in soybean - Xuejia Gu; Huichang Bian; Yibiao Zhang; Qi Sun; Yuzhi Li; Yang Sun; Hao Jiang; Yufeng Wang; Shuo Wang; Ji Li (Bioresource Technology, 2026)

A Novel Approach to Neuropathic Pain Treatment: Lactylation Targeting Microglia - Mingjie Chen; Fan Yang; Yingui Sun; Shuo Feng (Molecular Neurobiology, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

Ecological characteristics and carrying capacity analysis of marine ranching ecosystem in Beibu Gulf based on Ecopath model - Cheng Cheng; Haolin Yu; Jie Feng; Yan Li; Qingxian Cao; Li Liu; Cheng Yang; Shan Zhao; Shuo Li; Zhen Zhang; Haiyan Wang; Tao Zhang (Journal of Oceanology and Limnology, 2026)

Mapping interaction between human activities and land surface temperature in the Yellow River Basin - Zhongwu Zhang; Xue Bai; Zhe Li; Xin Yue; Xin Zhang; Shuo Yang; Lu Wang (Journal of Geographical Sciences, 2026)

Target Fibroblast-B cell crosstalk via MIF signaling drives pathogenic B cell differentiation and joint damage in knee osteoarthritis - Bizhi Tu; Zheng Zhu; Yan Li; Zhengming Zhu; Shijie Wang; Peizhi Lu; Ya Li; Shuo Yang; Dingtao Hu; Run Fang; Rende Ning (Inflammation Research, 2025)

High-Resolution Underwater Imaging via Richardson–Lucy Deconvolution Beamforming with Acoustic Frequency Comb Excitation - Jie Li; Jiace Jia; Deyue Hong; Yi Zhu; Shuo Yang; Zhiwen Qian; Jingsheng Zhai (Journal of Marine Science and Engineering, 2025)
Underwater acoustic imaging is essential in marine science and engineering, enabling high-resolution detection and characterization of underwater structures and targets. However, conventional deconvolution beamforming methods using broadband signals often suffer from model mismatch, inter-frequency interference, and limited noise robustness. To overcome these challenges, this study rigorously analyzes the point spread function of the imaging system and introduces Acoustic Frequency Comb (AFC) excitations to enhance resolution. By exploiting the autocorrelation characteristics of AFC signals and optimizing key parameters, imaging artifacts are effectively suppressed and the main-lobe width is narrowed, resulting in a 50% improvement in range resolution. Comparative analyses identify the Richardson–Lucy algorithm as the most effective in enhancing azimuthal resolution and maintaining robustness under array perturbations and low signal-to-noise ratios. Parametric studies further demonstrate that AFC excitation outperforms conventional linear frequency modulated pulses, achieving a 30% main-lobe width reduction, 10 dB sidelobe suppression, and a 14 dB noise decrease. Finally, tank experiments confirm the simulation results, showing that accurate PSF modeling enabled by AFC ensures high angular resolution. The discrete spectral structure facilitates more effective separation of signal and noise during iterative deconvolution, while excellent autocorrelation characteristics guarantee high range resolution, yielding superior overall imaging performance.

Adsorption of bisphenol S onto polyethylene terephthalate microfibers and their combined effects in oysters - Chaowen Zhang; Shuo Liu; Haiying Zhang; Wenjing Li; Chuchu Hu; Zhixue Wang; Yuchuan Yang; Tuyizere Clarck; Jingmin Zhu (Water Research, 2025)

Climate change poses risks to water retention and carbon sequestration capacity in the source area of the Yangtze River - Huiwen Liu; Huan Liu; Hui Peng; Tianyuan Zheng; Yongzhen Zhao; Shuo Wang; Yangwen Jia; Qinghui Zeng; Zefan Yang; Long Yan; Qin Yang; Baolong Zhao; et al. (Water Research, 2025)

Bee venom alleviates isoproterenol-induced cardiac hypertrophy via JAK2/NF-κB signaling cascade - Peiying Shi; Shuo Han; Yang Sun; Mengmeng Li; Xueling Xu (Tissue and Cell, 2025)

A pH-responsive multimodal antimicrobial nanosystem for plant disease control - Aiguo Gu; Chengshuai He; Shuo Zhang; Hao Wu; Song Yang; Jie Zhou; Yunhao Gao (Pesticide Biochemistry and Physiology, 2025)

TAD-YOLO: A lightweight nearshore ship detection method for small USVs in maritime trade surveillance - Xiaofei Yang; Shuo Shao; Weiyong Liu; Zhengrong Xiang; Bin Zhang (Ocean Engineering, 2025)

Sedimentological and geochemical evidence of Early Permian coal accumulation patterns linked to paleoclimate: Example from the Liujiang Basin, North China - Kai Zhou; Minfang Yang; Shuo Zhang; Ran Gao; Zhiming Yan; Peixin Zhang; Lei Wang; Haoqing Liu; Xiaowei Liu; Longyi Shao; Jing Lu (Marine and Petroleum Geology, 2025)

Electrokinetic remediation of hexavalent chromium-contaminated soil using low-molecular-weight organic acids combined with ion exchange membranes - Shuo Li; Jiao Yang; Qing Wang; Lieyan Shi; Pengxiang Liang; Yimin Hao; Wenjing Ge; Sviatoslav Viktorovich Fedorov; Hao Liu; Jingqing Gao (Journal of Water Process Engineering, 2025)

“Beggar-thy-Neighbor” or “Good-Neighbor Policy”: the spatially divergent governance effect in border areas under province-wide environmental policy implementation - Lu Pan; Zhaozhong Zhang; Jie Geng; Shuo Yang (Journal of Cleaner Production, 2025)

Role of carbonate in light-driven periodate activation for efficient tetracycline abatement - Shuo Li; Peixuan Sun; Yalun Yang; Heshan Zheng; Jun Ma; Tao Yang (Journal of Cleaner Production, 2025)

Enhanced degradation of carbamazepine in water by a chitosan-supported tea polyphenols/nano-zero-valent iron system: Mechanistic insights and toxicological risk assessment - Weiwei Yu; Yuanxin Liu; Jianglin Tan; Yue Liang; Jiang Hu; Qing Tu; Shuo Yang; Ji Li; Sikai Zhao; Yang Liu; Xinyan Li; Yan Luo; et al. (Journal of Cleaner Production, 2025)

Unraveling polarity-dependent adsorption and charge transfer in charged droplet-dust interactions: Toward cleaner coal production - Weizhi Zhao; Shaocheng Ge; He Liu; Liying Sun; Tianyi Yang; Shuo Liu; Hongjie Zhang (Journal of Cleaner Production, 2025)

The gold, palladium, silver, copper, and silicon were synergistically recovered from the waste chips through the phase reconstruction and stepwise recovery methods - Shuo Liu; Yaobin Lai; Xin Chen; Jian Li; Hui Zhang; Linlin Chang; Tianyi Chen; Xuxia Zhang; Yangyang Xie; Liuyimei Yang; Tao Qi (Journal of Environmental Chemical Engineering, 2025)

Salt-fouling-resistant CMWCNTs-functionalized graphene aerogel for high-efficiency solar interfacial brine evaporation - Mingjia Dong; Yukun Li; Shuo Yang; Yingying Fu; Qiqian Huang; Shuying Dong (Journal of Environmental Chemical Engineering, 2025)

A newly developed Germlings Harvester (GEHA) in combination with metabarcoding analysis detected numerous plankton species, particularly HABs-causing species, from in-situ germination of resting stage cells - Shuo Shi; Zhe Tao; Wanli Yang; Fengting Li; Ben Wei; Caixia Yue; Suzhi Pan; Yunyan Deng; Lixia Shang; Zhaoyang Chai; Ying Zhong Tang (Harmful Algae, 2025)

Calcium salt-induced rice starch-soybean protein composite gels: Mechanism of influence of calcium salt type and concentration on gel properties - Shuanghe Ren; Yahui Du; Shuo Zhang; Fangxiao Lou; Zhuying Wang; Hong Yang; Lianzhou Jiang; Zhongjiang Wang; Zengwang Guo (Food Chemistry, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

Mechanism of xanthan gum in inhibiting aggregation in soy protein isolate gels after commercial Sterilization: Implications for texture-modified food for dysphagia - Zhuying Wang; Yahui Du; Shuo Zhang; Jinrui Hu; Zhongjiang Wang; Zengwang Guo; Hong Yang (Food Hydrocolloids, 2025)

Experimental validation of elastoplastic topology optimization through additive manufacturing and digital image correlation - Yilin Yuan; Guodong Zhang; Tong Guo; Kapil Khandelwal; Shuo Yang (Engineering Structures, 2025)

NADPH oxidase-mimicking nanozyme for disulfidptosis-induction strategy to amplify cuproptosis in cancer therapy - Juan Ruan; Chen Li; Yu Wang; Chunhui Wang; Xinda Yang; Chuansheng Xu; Yan Gao; Song Hu; Shuo Shi (Chemical Engineering Journal, 2025)

Spatiotemporal oxygen modulation reprograms hypoxia-induced antibiotic resistance - Shuo Shi; Ma Bai; Lili Kong; Jinjie Li; Xiyan Ding; Jialun Yang; Jianlong Wang; Chao Guo; Jinyou Duan (Chemical Engineering Journal, 2025)

Real-time food freshness monitoring with AI assisted colorimetric and fluorescent dual-mode paper-based sensors: Harnessing size-dependent effects of mesoporous Cu2O - Zixin Jin; Zhiwei Liu; Ziwuzhen Wang; Yuqing Yang; Hongyu Shi; Caixu Fan; Yamin Liu; Qiuyue Ji; Wei Sheng; Long Ma; Shuo Wang (Chemical Engineering Journal, 2025)

Genomic Survey and Characterization of 14-3-3 Genes in Lycium barbarum L. and Its Expression Patterns Responding to Infection of Fusarium solani - Kun Zhao; Rui Feng; Teja Manda; Shuo Liu; Rui Zheng; Liming Yang (Tropical Plant Biology, 2025)

Genome-wide identification and functional annotation of the ascorbate peroxidase (APX) gene family in cotton: putative roles in reactive oxygen species (ROS) homeostasis within pigment glands - Xue Zhang; Dongyun Zuo; Qiaolian Wang; Limin Lv; Youping Zhang; Yi Yang; Lingyu Hao; Shuo Zhang; Guoli Song; Hailiang Cheng (Planta, 2025)

G Proteins-Associated Dose-Dependent Effects of Oxytocin on Oxytocin Neuronal Activity and Astrocytic Plasticity of the Supraoptic Nucleus - Xiao-Yu Liu; Shuo Ling; Yang Liu; Yunhao Jiang; Xiaoran Wang; Shuwei Jia; Chunmei Hou; Yanpeng Li; Delai Qiu; Yu-Feng Wang (Molecular Neurobiology, 2025)

Inflammation in cardiovascular-kidney-metabolic syndrome: key roles and underlying mechanisms–a comprehensive review - Zhen Xu; Shuo Yang; Yuan Tan; Qian Zhang; He Wang; Jingjin Tao; Qi Liu; Qingchen Wang; Weimin Feng; Zhongxin Li; Chong Wang; Liyan Cui (Molecular and Cellular Biochemistry, 2025)

Thrombin-preconditioned mesenchymal stem cell–derived exosomes for wound healing in vitro and in vivo - Liu Yang; Minming Lou; Hongwei Wang; Shuo Zhang; Jie Ma (In Vitro Cellular & Developmental Biology - Animal, 2025)

Inhibitory effect of carvacrol nanoemulsions on Staphylococcus aureus and its biofilms - Yifei Wang; Feng Chen; Zongxin Lu; Lin Ye; Xiaobo Yang; Josphat Njenga Gichure; Joanna Trafiałek; Shuo Zhang; Shoukui He (Journal of Consumer Protection and Food Safety, 2025)

PLSELM: A lightweight modeling approach for low-data calibration in near-infrared spectroscopy - Xiaqiong Fan; Lijin Shang; Shuo Zhao; Jixing Fan; Senlin Zhang; Qiong Yang; Chengyang Wu; Yulin Liu; Tiejun Yang; Hongchao Ji (Analytica Chimica Acta, 2025)

Different distribution patterns and potential risks of pesticide residues between soils and sediments: a case study in Lake Taihu Ecological Conservation Area - Yuyang Hao; Mohan Bai; Lanqing Sun; Shuo Yang; Chunyu Wang; Qing X. Li; Bruce D. Hammock; El-Sayed A. El-Sheikh; Ting Xu (Environmental Monitoring and Assessment, 2025)

Rational Green Synthesis of Eu MOF for Ratiometric Fluorescence Sensing Cu2+ - Yimeng Jia; Mengjiao Nie; Qianzhuo Lei; Ying Zou; Yuxin Yang; Jia He; Shuo Liu (Journal of Fluorescence, 2025)

From innovation to sustainability: How does the birth of innovative enterprises affect urban carbon emission intensity in China? - Tianheng Shu; Xia Liao; Shuo Yang; Guangyu Cheng; Taofang Yu (Sustainable Cities and Society, 2025)

Variational Holo-spectral analysis method of high-dimensional feature representation for underwater acoustic target recognition - Jinxi Sun; Zhaohui Du; Yixin Yang; Jiahao Wang; Yang Shi; Shuo Liu (Ocean Engineering, 2025)

Evaluation zooplankton community and energy transfer efficiency: A case in the coastal waters of Shandong, China - Shuo Wang; Fang Zhang; Shuangyan Zhang; Dezhou Yang; Shuqun Song (Marine Environmental Research, 2025)

Assessing the effectiveness of non-point source pollution models in data-limited urban areas - Fangze Shang; Sijie Tang; Hantao Wang; Ruiyi Yang; Zhiqiang Hou; Yang Ping; Zhenzhou Zhang; Huayu Chen; Yange Yu; Ashantha Goonetilleke; Changhyun Jun; Xin Tian; et al. (Journal of Hydrology, 2025)

Responses of a harmful algal bloom-causing dinoflagellate Prorocentrum obtusidens to elevated temperature and urea - Wei-Ping Zhang; Yang Zhou; Wen-Jing Sun; Shuo-Yu Zhang; Shu-Feng Zhang; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Harmful Algae, 2025)

Extraordinary deactivation offset effect of lead and chromium on the poisoning of commercial V2O5-WO3/TiO2 catalysts - Ke Zhuang; Hexiao Huang; Shuo Huang; Qian Zhang; Xiongbo Chen; Yun Xu; Dianhui Chen; Yuqin Zhong; Yaoyu Zhang; Liu Yang; Zhongyi Sheng (Fuel, 2025)

Peptidomics and molecular docking reveal digestion-resistant IgE-binding epitopes in bovine β-lactoglobulin and α-lactalbumin from simulated infant digestion - Fan Yang; Hongwei Zhang; Shaolei Wang; Xue Zhao; Yuying Tang; Jianhua Zeng; Weixue Zhao; Shuo Feng; Changhong Ma; Lanwei Zhang; Kai Lin (Food Chemistry, 2025)

A rosmarinic acid-fish skin protein-chitosan hybrid nano-delivery system with excellent sustained-release and antioxidant performances - Kemeng Qin; Xinyu Sun; Jingmin Liu; Ruican Wang; Xufang Huang; Yi Wang; Haitao Wang; Jingying Yang; Shuo Wang (Food Chemistry, 2025)

Acidification boosts the photodynamic activity of anthocyanidin for enhanced sterilization - Zhenqing Guo; Yajie Wang; Xinqi Wang; Ting Du; Kaiyuan Su; Lin Yang; Yaru Han; Shuo Shi; Jianlong Wang; Wentao Zhang (Chemical Engineering Journal, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Buried interface modulation via functionalized π-conjugated molecules enables efficient wide-bandgap perovskite photovoltaics - Shuo Dong; Jiahui Qi; Yimeng Tian; Yiren Gao; Huiyang Ye; Li Zhang; Changjiu Sun; Shaopeng Yang; Tingwei He (Chemical Engineering Journal, 2025)

Synergistic effect of carbon defects and iron active sites in biochar-activated peroxymonosulfate for acetaminophen degradation: Unlocking the non-radical mechanisms - Xuchao Sun; Kaizhen Wu; Gui Yang; Fang Shen; Shiping Zhang; Tingwei Wu; Shuo Sun; Yu Jiang; Xiaoyong Wu (Chemical Engineering Journal, 2025)

Dynamic reversible thermochromic camouflage smart textiles for temperature visualized personal healthcare and thermal management - Weiyi Zhang; Shuo Luan; Yuyan Fang; Linlin Zhu; Yang Yang; Mingwei Tian; Lijun Qu; Tingting Fan; Jinlei Miao (Chemical Engineering Journal, 2025)

Monocyte/macrophage-mediated transport and intratumoral bacteria-responsive ZIF nanoplatform for enhanced immunotherapy against microsatellite-stable colorectal cancer - Xietao Ye; Yeyang Sun; Lin Yang; Chen Chen; Shihao Li; Shuo Dong; Xiaoying Qin; Xiaoqi Li; Congyan Liu; Jiege Huo; Yuping Liu; Yan Chen (Chemical Engineering Journal, 2025)

ISRIB-loaded nanoplatform disrupts cellular homeostasis by depleting glutathione and inhibiting stress granules formation to drive immunosuppressive reprogramming - Yu Wang; Zhongqi Cui; Yang Wang; Chunhui Wang; Yue Zhang; Nan Huang; Xinda Yang; Fenyong Sun; Sufeng Qiang; Shuo Shi; Bing Shen (Chemical Engineering Journal, 2025)

Multi-omics insights into the regulatory mechanism of citric acid in silage fermentation - Jingbo Ma; Xuejuan Zi; Shuo Wu; Yingying Ma; Runfei Liang; Jiarui Yang; Junhu Yao; Mao Li; Zongjun Li (Bioresource Technology, 2025)

Novel laser-driven fast pyrolysis of biomass: Insights into biochar characteristics and applications - Rui Ma; Jintao Luo; Xiaoning Duan; Yuwan Sheng; Shaohui Wang; Deli Zhang; Fang Wang; Shuo Yang; Weiming Yi (Bioresource Technology, 2025)

Unveiling dynamics of microbial communities, species interactions, and ecological assembly during low-temperature-induced sludge bulking in full-scale wastewater treatment systems - Han-Jun Sun; Xian Zhao; Jie Ding; Yu-Qian Wang; Wen-Shuo Wang; Zhi-Hua Feng; Sha Zhao; Liang Wang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2025)

Reanalysis-based retrieval of near-surface ozone concentrations and its implications for ozone pollution events across China - Lili Wang; Xingchuan Yang; Haili Zhou; Yang Yang; Jiantao Dong; Shuo Dong; Wenji Zhao; Minghui Tao; Pengfei Ma (Atmospheric Pollution Research, 2025)

El Niño-Southern Oscillation induced migration of typhoon tracks in the northwestern Pacific Ocean over the last two millennia - Shuo Zhang; Vittorio Maselli; Zhenyu Zhang; Yang Yang; Xiaolin Wang; Xing Jian; Yong Shi; Jianhua Gao (Science China Earth Sciences, 2025)

Optimizing blood–brain barrier permeability: the effect of wine processing on alkaloids in Phellodendri Chinensis Cortex - Shuo Zhang; Jiahui Zhao; Wenjing Ren; Yue Zhou; Yang Chen; Shiru Jiang; Gui Xu; Xiutong Ge; Hui Gao; Fan Zhang (Journal of Natural Medicines, 2025)

Multidirectional interstitial flow promotes microvascular network formation: insights from a square chip-based platform - Qihang Yang; Yuening He; Shuo Wang; Zengting Li; Jiaxuan Wang; Zehao Sun; Wenbo Yang; Xiang Zhong; Bo Peng; Zaozao Chen; Zhongze Gu; Dan Zhu; et al. (Angiogenesis, 2025)

Multi-Objective Optimization for PTO Damping of Floating Offshore Wind–Wave Hybrid Systems Under Extreme Conditions - Suchun Yang; Shuo Zhang; Fan Zhang; Xianzhi Wang; Dongsheng Qiao (Journal of Marine Science and Engineering, 2025)
Floating offshore wind–wave hybrid systems, as a novel structural form integrating floating wind turbine foundations and WECs, can effectively enhance the efficiency of renewable energy utilization when properly designed. A numerical model is established to investigate the dynamic responses of a wind–wave hybrid system comprising a semi-submersible FOWT and PA wave energy converters. The optimal damping values of the PTO system for the wind–wave hybrid system are determined based on an NSGA-II. Subsequently, a comparative analysis of dynamic responses is carried out for the PTO system with different states: latching, fully released, and optimal damping. Under the same extreme irregular wave conditions, the pitch motion of the FOWT with optimal damping is reduced to 71% and 50% compared to the latching and fully released states, respectively. The maximum mooring line tension in the optimal damping state is similar to that in the fully released state, but nearly 40% lower than in the latching state. This optimal control strategy not only sustains power generation but also enhances structural stability and efficiency compared to traditional survival strategies, offering a promising approach for cost-effective offshore wind and wave energy utilization.

One new benzoate glycoside from Gentiana triflora pall - Shuo Liu; Gang Chen; Yun Sun; Yang Ju (Natural Product Research, 2025)

Numerical simulation and optimization design of a novel longitudinal-flow online fertilizer mixing device - Kang Zheng; Shuo Yang; Yuanyuan Gao; Xiu Wang; Jiakai Wang; Senlin Song; Changyuan Zhai; Liping Chen (Computers and Electronics in Agriculture, 2025)

Immunoregulation and antibacterial effect of IFNf for Mycobacterium marinum infection in Chinese sturgeon (Acipenser sinensis) - Peipei Yu; Guangyi Ding; Simei Hu; Keli Gong; Shuo Yang; Kai Luo; Xincheng Jiang; Shuhuan Zhang; Dingda Xu; Qiaoqing Xu; Mei Liu (Aquaculture, 2025)

Effects of the lpfD gene on biofilm formation in Salmonella - Shuo Yang; Jing Gao; Changxu Yu; Fahui Song; Jikun Wu; Luyang Zhou; Shuqi Wei; Aofei Wang; Yanli Zhu (Veterinary Microbiology, 2025)

Efficient production of 5-hydroxymethylfurfural from glucose over the combination of nano-metal oxides and HCl in biphasic methyl isobutyl ketone/H2O–NaCl - Yang Liu; Shuo Zhang; Tingwei Zhang; Yongcan Jin; Huining Xiao; Chaofeng Zhang (Sustainable Chemistry and Pharmacy, 2025)

Middle Devonian (Givetian) coal-bearing strata of the Haikou Formation, Qujing Basin, South China: Paleoenvironmental and paleoclimatic implications - Kai Zhou; Minfang Yang; Shuo Zhang; Jing Lu; Lusheng Yin; Yanwen Shao; Haoqing Liu; Peixin Zhang; Zhiming Yan; Ran Gao; Longyi Shao; Christopher R. Fielding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Esterquat EQ-90 as a green novel collector for effective desilication in magnesite flotation: Adsorption mechanisms and selectivity - Yishen Sun; Jin Yao; Wanzhong Yin; Haoran Sun; Shuo Yang (Minerals Engineering, 2025)

Revisiting the causal relationship between the built environment, automobile ownership, and mode choice using double machine learning - Shuo Yang; Leyu Zhou; Zhehao Zhang; Haidong Li; Liang Guo; Xiaoli Sun; Tongyang Song (Journal of Transport Geography, 2025)

Nanoconfinement assists the selective generation of singlet oxygen to efficiently remove emerging organic contaminants in soil with a low consumption of oxidant - Qi Wang; Shuo Yang; Yanlin Wu; Olivier Monfort; Wenbo Dong (Journal of Hazardous Materials, 2025)

Z-scheme Cu2O/g-C3N4/Ag heterostructures: A novel approach for simultaneous water pollutant removal and real-time SERS monitoring - Kaiyue Li; Wenhui Li; Ping Huang; Yuquan Zhuo; Ziwen Yang; Bo Wang; Runru Liu; Bing Liu; Enzhu Hou; Shuo Yang; Donglai Han (Journal of Environmental Chemical Engineering, 2025)

Recent advances in photocatalytic degradation of pollutants in wastewater using bismuth-based catalysts modified with low-dimensional materials - Yalun Yang; Ying Deng; Shuo Li; Heshan Zheng; Jun Ma; Junfeng Niu; Yoong Kit Leong; Jo-Shu Chang (Journal of Environmental Chemical Engineering, 2025)

Transformation of waste PET into bimetallic MOF materials for photothermal interfacial evaporation - Meng Wang; Qingbo Yu; Shuo Yang; Guoqiang Wang; Xiujuan Feng (Journal of Environmental Chemical Engineering, 2025)

Study on hydraulic condition optimization of a new permeable modular constructed wetland - Fangxing Zhao; Xinwen Zhang; Jianchao Yang; Zhiheng Ye; Shuo Liu; Linan Zhou; Yixin Wang; Zhenghe Xu (Journal of Environmental Chemical Engineering, 2025)

Pilot test study on a new physical treatment method for the electric desalting wastewater - Binghe Li; Shaoxuan Li; Yu Li; Haonan Liu; Shuo Huang; Qiang Yang; Yiqian Liu (Journal of Environmental Sciences, 2025)

Nitrogen addition decouples the microbial necro-mass from soil organic carbon formation in a temperate grassland - Huanhuan Cheng; Yingbin Li; Shuo Li; Tianran Sun; Guoxiang Niu; Qi Li; Junjie Yang; Yanxia Ma; Yingzhi Gao; Qiang Yu; Haitao Zhao; Qiushi Ning; et al. (Journal of Environmental Sciences, 2025)

Variations in quality attributes of cow and goat milk subjected to microwave and high-pressure treatments over a two-week storage period - Nina Ding; Qiyue Sun; Zhongna Yu; Qijing Du; Rongbo Fan; Guangxu Ren; Liangliang You; Shuo Feng; Yongxin Yang; Rongwei Han (Innovative Food Science & Emerging Technologies, 2025)

Unveiling the role of Al location in H-BEA zeolite on the adsorption and diffusion of iso-butane and 1-Butene in C4 alkylation - Shuo Li; Guangxiang Wang; Yupeng Du; Xiaoping Chen; Hui Tian; Lei Wang; Xiang Feng; Chaohe Yang (Fuel, 2025)

Sensitive dual detection of N-nitrosodiphenylamine and N-nitrosodiethylamine using a PtNPs-enhanced MWCNTs/Fe-porphyrinic MOF nanocomposite-based electrochemical sensor - Jiachen Zhao; Yue Zou; Junlan Yu; Chao Wang; Yili Hu; Fangkai Han; Ning Yang; Fuwei Pi; Ming Zhang; Xiaodan Liu; Jiahua Wang; Huang Dai; et al. (Food Chemistry, 2025)

Antifouling electrochemical aptasensor based on a polyzwitterion copolymer for analyzing aflatoxin B1 in food - Meirong Niu; Xujun Pu; Xian Chen; Dabing Ren; Cheng Zhang; Lunzhao Yi; Yukun Yang; Ying Gu; Shuo Wang (Food Chemistry, 2025)

Spatiotemporally engineered bilayer microneedles for biphasic drug delivery in corneal neovascularization therapy - Changhong Yuan; Shuo Li; Zimeng Yang; Hengzhi Liu; Jiang Yv; Hongzhuo Liu; Zhonggui He; Yongjun Wang (Chemical Engineering Journal, 2025)

Cluster-net structured polymer hydrogel elastomer engineered as artificial temporomandibular joint disc for establishing mechanical homeostasis - Hao Dai; Jianming Zhao; Kun Qiao; Tianyi Lin; Yajie Xie; Lin Lan; Jie Wang; Yuchen Liu; Shuo Chen; Yudong Zheng; Yang He (Chemical Engineering Journal, 2025)

Regulating chemical and electronic structure of Ni-based catalysts via introducing heteroatoms for boosting electrochemical oxidation of borohydride - Ying Yang; Zhihong Cui; Caini Yi; Meilin Chen; Hang Yang; Xiaolong Hou; Guimiao Wang; Shuo Wang; Yuping Liu; Guozhong Cao; Danmei Yu; Xiaoyuan Zhou (Chemical Engineering Journal, 2025)

Enhancing blue phosphorescent OLED efficiency by modulating the excited state of tetradentate Pt(II) complexes via N-embedding and steric hindrance effects - Feng Zhan; Teng-Shuo Zhang; Jianqiang Chen; Kewei Xu; Jieying Tong; Yun-Fang Yang; Yuanbin She; Guijie Li (Chemical Engineering Journal, 2025)

Dual network CMCS/PNIPAM temperature-sensitive hydrogel based fluorescent and RGB colorimetric dual-mode immunosensor for detection of capsaicinoids as an exogenous index in edible oil samples - Ziwuzhen Wang; Wei Sheng; Zixin Jin; Hongyu Shi; Zhiwei Liu; Yuqing Yang; Shuo Wang; Qiuyue Ji; Caixu Fan; Yamin Liu (Chemical Engineering Journal, 2025)

Development of novel acetate- and water-soluble fertilizer-based medium for Chlorella cultivation - Zhuzhu Xu; Shuo Chen; Yujie Zhang; Wei Wu; Lingfu Fang; Shijuan Dou; Ming Yang; Guozhen Liu (Bioresource Technology, 2025)

Progression of the Residual Lesion in Cavernous Sinus Extra-Axial Cavernous Hemangioma After Surgery - Ran Huo; Qifeng Yu; Hongyuan Xu; Jie Wang; Shaozhi Zhao; Jiancong Weng; Xiudan Bai; Yuming Jiao; Wenqian Zhang; Qiheng He; Zhiyou Wu; Shaowen Liu; et al. (Translational Stroke Research, 2025)

Research progress on aroma enhancement strategies for fruit wine - Shuo Ha; Tong Qu; Qingbo Zeng; Jiaojiao Liu; Jiaqi Zhang; Ming Chen; Hua Yang (Systems Microbiology and Biomanufacturing, 2025)

Effects of hydrothermal charcoal on saline-alkaline soil properties in the Yellow River Delta - Shuo Yang; Yujun Ma; Binjie Ji; Hongbo Wang; Fengkai Sun; Mei Li (Plant and Soil, 2025)

Causal Matrix Long Short-Term Memory Network for Interpretable Significant Wave Height Forecasting - Mingshen Xie; Wenjin Sun; Ying Han; Shuo Ren; Chunhui Li; Jinlin Ji; Yang Yu; Shuyi Zhou; Changming Dong (Journal of Marine Science and Engineering, 2025)
This study proposes a novel causality-structured matrix long short-term memory (C-mLSTM) model for significant wave height (SWH) forecasting. The framework incorporates a two-stage causal feature selection methodology using cointegration testing and Granger causality testing to identify long-term stable causal relationships among variables. These relationships are embedded within the C-mLSTM architecture, enabling the model to effectively capture both temporal dependencies and causal information within the data. Furthermore, the model integrates Bayesian optimization (BO) and twin delayed deep deterministic policy gradient (TD3) algorithms for synergistic optimization. This combined TD3-BO approach achieves an 11.11% improvement in the mean absolute percentage error (MAPE) on average compared to the base model without optimization. For 1–24 h SWH forecasts, the proposed TD3-BO-C-mLSTM outperforms the benchmark models TD3-BO-LSTM and TD3-BO-mLSTM in prediction accuracy. Finally, a Shapley additive explanations (SHAP) analysis was conducted on the input features of the BO-C-mLSTM model, which reveals interpretability patterns consistent with the two-stage causal feature selection methodology. This research demonstrates that integrating causal modeling with optimization strategies significantly enhances time-series forecasting performance.

Spatiotemporal patterns of fecal cortisol metabolites in critically endangered wild Alpine musk deer in eastern edge regions of Tibetan Plateau: influencing factors and conservation implications - Jiayi Wu; Xiaoping Lu; Shuo Geng; Liquan Shen; Gong Wang; Rui Liu; Jun Qi; Chunting Feng; Junyi Yang; Zhengxu An; Rongxin Li; Na Qiao; et al. (Biologia, 2025)

Bimetallic catalyst with dual-reaction-center and oxygen vacancies for synergistically boosting peracetic acid activation and decontamination via 1O2 generation - Shuo Li; Yalun Yang; Heshan Zheng; Junfeng Niu; Ying Deng; Jun Ma; Yoong Kit Leong; Jo-Shu Chang; Wen-Wei Li (Water Research, 2025)

Efficient permanganate activation under UV 222 nm irradiation for enhanced pollutant abatement - Haochen Zhang; Peng Su; Maoju Jiang; Chenlong Liu; Qixiao Lv; Wenqi Li; Xiangyang Hou; Junhui Zhou; Shuo Li; Bin Zhang; Bei Zhang; Jun Ma; et al. (Water Research, 2025)

Time-dependent characteristics of quick-setting slurry rheological parameters with extremely high temperature: Experimental study - Qingsong Zhang; Changxin Huang; Jun Liu; Lianzhen Zhang; Xiaochen Wang; Yan Pei; Shuo Zhou; Zongjian Yang (Tunnelling and Underground Space Technology, 2025)

Does the first/last-mile design matter for transit commuting compared to land use? - Shuo Yang; Yixin Guo; Leyu Zhou; Jia Chen; Liang Guo (Transportation Research Part D: Transport and Environment, 2025)

Chronic low-level exposure to Pb, Hg, and Cd mixture triggers brain premature aging in rat - Jie Xie; Lu Ouyang; Jiajun Li; Shuo Yang; Qi Li; Yue Li; Lingyu Yan; Yihong Fu; Qijun Li; Yuting Xia; Xinling Chen; Ziyang Fu; et al. (Toxicology, 2025)

Design and evaluation of bio-inspired electro-osmosis system for reducing soil adhesion on agricultural equipment - Le Yang; Zhihong Zhang; Baoping Yan; Shuo Yuan; Fu Zhang (Soil and Tillage Research, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Assessing Mississippi embayment and coastal lowlands aquifer systems by groundwater stress index and regional groundwater model - Shuo Yang; Frank T.-C. Tsai; T. Prabhakar Clement (Journal of Hydrology, 2025)

Distribution and fate of antibiotics in water–sediment–biofilm phases and their potential risks in urban lakes within a large-scale city in eastern China - Fuzhu Ye; Kejian Chu; Zulin Hua; Yuanyuan Liu; Xuan Yang; Shuo Qing; Li Gu (Journal of Hazardous Materials, 2025)

Toxicity of true-to-life microplastics to human iPSC-derived intestinal epithelia correlates to their protein corona composition - Hugo Brouwer; Mathias Busch; Shuo Yang; Tom Venus; Germaine Aalderink; Juan Francisco Ferrer Crespo; Aliro Villacorta; Alba Hernández; Irina Estrela-Lopis; Sjef Boeren; Hans Bouwmeester (Journal of Hazardous Materials, 2025)

Transboundary conservation of musk deer (Moschus spp.): global synthesis of populations, distributions, threats, and recovery strategies - Xiaoping Lu; Shuo Geng; Junyi Yang; Jiayi Wu; Chunting Feng; Biqing Li; Rongxin Li; Zhengxu An; Achyut Aryal; Xiuxiang Meng (Journal for Nature Conservation, 2025)

Investigation on deactivation periods of ZSM-5/SAPO-34 catalyst in MTA reaction: Carbon deposition behavior - Jingbo Li; Bangming Yang; Ning Li; Jianqiao Zhao; Shuo Li; Ruizhi Chu; Xianliang Meng; Weisong Li; Shi Yu (Fuel, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

Unlocking the flavor potential of fruit wine: Enhancing RallsJanet wine quality and aroma complexity through ARTP induced mutagenesis of Saccharomyces cerevisiae - Qingbo Zeng; Shuo Ha; Jiaojiao Liu; Tong Qu; Ming Chen; Hua Yang (Food Bioscience, 2025)

Experimental study on flexible energy use feature of multi-split air-conditioning system with different control schemes in summer - Anqi Ye; Shuo Liu; Tao Zhang; Zhigang Zhao; Qiuhao Yang; Xiaohua Liu (Energy and Buildings, 2025)

Cascade regulatory mechanism of soil organic phosphorus mineralization mediated by quorum sensing signal molecules C4/C6/C8-HSL: Dynamic response based on phosphatase secretion of core species - Zhenchao Wu; Jie Kang; Liangyang Mao; Yueyi Liu; Shuo Li; Weige Yao; Ying Yang; Xiujun Tu; Yuhao Guo; Jinyu Du; Xuan Tang; Tong Yang; et al. (Chemical Engineering Journal, 2025)

Application of asymmetric FeN4-NiN3O diatomic bifunctional catalysts with d-d coupling in zinc-air batteries - Shuo Tian; Lihua Chen; Shang Wu; Jiankun Li; Jincai Yang; Huize Zhang; Liangshou Wang; Yuzhi Sun; Lihong Wang; Xiaoyi Meng; Quanlu Yang (Chemical Engineering Journal, 2025)

Engineering a zero-strain CoNb₂O₆ anode via ZIF-67-derived sol-gel pyrolysis for ultra-stable lithium-ion capacitors - Shuo Zhao; Zhen Liu; Ruiyong Chen; Yong Deng; Chunzhen Yang; Peng Zhang (Chemical Engineering Journal, 2025)

Dependence of ε-caprolactone selectivity on diffusion performance over Sn-Beta zeolite catalyst for Baeyer-Villiger oxidation of cyclohexanone - Xiaolong Liu; Jiahe Sun; Shuo Li; Kaixuan Yang; Ting Su; Hongying Lü; Zhiguo Zhu (Chemical Engineering Journal, 2025)

Perovskite-socketed FeCoNiCu quaternary alloy nanoparticles for efficient CO2 reduction in solid oxide electrolyzer - Shuo Liu; Lin-Bo Liu; Ming Yang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Subiao Liu; Jing-Li Luo (Chemical Engineering Journal, 2025)

Integrated super-resolution plasmonic scattering imaging and fluorescence localization for multiparametric exosome analysis in complex biological samples - Zhaochen Huo; Bing Chen; Pengfei Wang; Haoliang Li; Shuo Meng; Qi Xue; Ya Li; Ruijun Guo; Xiaonan Yang (Chemical Engineering Journal, 2025)

Design of Control System for Underwater Inspection Robot in Hydropower Dam Structures - Bing Zhao; Shuo Li; Xiangbin Wang; Mingyu Yang; Xin Yu; Zhaoxu Meng; Gang Wan (Journal of Marine Science and Engineering, 2025)
As critical infrastructure, hydropower dams require efficient and accurate detection of underwater structural surface defects to ensure their safety. This paper presents the design and implementation of a robotic control system specifically developed for underwater dam inspection in hydropower stations, aiming to enhance the robot’s operational capability under harsh hydraulic conditions. The study includes the hardware design of the control system and the development of a surface human–machine interface unit. At the software level, a modular architecture is adopted to ensure real-time performance and reliability. The solution employs a hierarchical architecture comprising hardware sensing, real-time interaction protocols, and an adaptive controller, and the integrated algorithm combining a fixed-time disturbance observer with adaptive super-twisting controller compensates for complex hydrodynamic forces. To validate the system’s effectiveness, field tests were conducted at the Baihetan Hydropower Station. Experimental results demonstrate that the proposed control system enables stable and precise dam inspection, with standard deviations of multi-degree-of-freedom automatic control below 0.5 and hovering control below 0.1. These findings confirm the system’s feasibility and superiority in performing high-precision, high-stability inspection tasks in complex underwater environments of real hydropower dams. The developed system provides reliable technical support for intelligent underwater dam inspection and holds significant practical value for improving the safety and maintenance of major hydraulic infrastructure.

Two new diarylheptanoids from Curcuma kwangsiensis rhizomes - Shuo-Guo Li; Le Deng; Qiu-Fang Chen; Rui Yang; Cao-Min Zou; Shu-Mei Wang; Meng-Hua Wu; Jiang Meng (Natural Product Research, 2025)

Investigation of the transportation characteristics of marine dredged-sediment in pipelines based on experimental pipeline models - Yinghao Huang; Shuo Wang; Chenye Yang; Fei Lou (Marine Georesources & Geotechnology, 2025)

Investigation on the inhibition dynamic mechanism of short carbon chain fluoride foam on the coal spontaneous combustion - Xin-xiao Lu; Zhao Yang; Zi-yao Chen; Shuo Wang; Guan Wang; Long He (Process Safety and Environmental Protection, 2025)

Hypoxia-preconditioned ADSC exosomes encapsulated in a multifunctional dual-network hydrogel promote the healing and functional regeneration of seawater-immersed wounds - Jie Li; Zishuo Wang; Wenjing Yang; Yongchao Zhou; Tao Fu; Yuhui Zhang; Xuzhou Duan; Dong Liu; Lingtong Kong; Yan Shang; Yuchen Zhang; Xuhui Wang; et al. (Chemical Engineering Journal, 2025)

A dual-biomimetic evaporator with Marangoni-induced ultra-salt-resistance for long-durable solar desalination - Zhaolong Wang; Jiyuan Yu; Meiyang Hu; Ciwei Wu; Shuo Yang; Qihui Xie; Yong Shuai (Chemical Engineering Journal, 2025)

Energy-dissipating binder for self-healing sulfurized polyacrylonitrile electrode for rechargeable lithium batteries - Qihang Wang; Lizhi Xiang; Huichao Lu; Shuo Liu; Chenran Hao; Jiqiong Liu; Jing Han; Jun Yang; Yanna NuLi; Jiulin Wang (Chemical Engineering Journal, 2025)

Impact of Alternating Reactor Functions on Aerobic Granular Sludge: Treatment Efficiency of Brewery Wastewater and Microbial Community - Shuo Yang; Dongxu Lu; Shaogen Liu; Yunkun Wang; Hongkui He; Jintong Ma; Liming Qin (Water, Air, & Soil Pollution, 2025)

Experimental Investigation of Grout Flow Behaviour Through Rough Parallel Multi-Fractures - Yuhao Jin; Lijun Han; Shuo Yang; Hui Guo; Shanjie Su; Lanying Huang; Deyuan Zong; Peitao Qiu; Kun Hu (Rock Mechanics and Rock Engineering, 2025)

A Male-Biased Ion Transport Peptide-Like Gene Regulates Sex Dimorphic Growth in Litopenaeus vannamei - Xiaojuan Sun; Ying Chen; Ying Du; Xiaoliu Yang; Chunxiang Liu; Shuo Bai; Jingjie Hu; Zhenmin Bao; Zhe Qu (Marine Biotechnology, 2025)

Development and application of a real-time fluorescent RAA assay for H9 subtype avian influenza viruses - Wanting Zhou; Xiaoqi Li; Jie Tian; Shuo Liu; Cheng Peng; Jinping Li; Guangyu Hou; Jizhe Yang; Wenming Jiang; Hualei Liu (Virus Genes, 2025)

Simultaneously enhance nutrient removal and sludge settleability through hydrocyclone-based technology in a full-scale high-inert containing activated sludge process - Yanjun Shao; Sisi Chen; Xiang Tao; Weilan Yang; Tao Liu; Binzheng Wang; Yan Wang; Shuo Wang; Dongdong Xu; Jianhua Guo; Ji Li (Water Research, 2025)

Quantifying the contribution of sediment recycling in mantle: A case study of Early Cretaceous gabbroic intrusions in the northeastern North China Craton - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Feng Wang; Shuo Wang; Ke Wu (Lithos, 2025)

Organic fertilizer mitigated the oxidative stress of tomato induced by nanoplastics through affecting rhizosphere soil microorganisms and bacteriophage functions - Liang-Bin Zhao; Zi-Xuan Tang; Hui-Fang Zhai; Hong-Yu Lai; Hai-Yang Li; Shuo Liu; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

A cellulose based fluorescent microsphere for sensitive detection and efficient removal of hydrazine and its versatile applications in environmental samples and live plants - Zhiyuan Meng; Xinyan Li; Qian Ye; Shuo Zhang; Xu Xu; Yiqin Yang; Zhonglong Wang; Shifa Wang (Journal of Hazardous Materials, 2025)

Dual-site Langmuir-Hinshelwood mechanism in ZnCr-LDH/NH2-UIO66 heterojunction for efficient photocatalytic NO oxidation - Jing Guo; Haotong Ma; Huan Shang; Wenchao Wang; Ruiyi Yang; Shuo Wang; Yingchun Miao; David Lee Phillips; Guisheng Li; Shuning Xiao (Journal of Hazardous Materials, 2025)

Synergistic defect engineering in TiO2 nanotubular electrodes for advanced electrochemical oxidation of benzene-toluene mixtures: Performance and mechanisms - Yameng Li; Peizhen Yang; Yongge Zang; Hongrui Liu; Shuo Zhang; Xiang Liu; Miao Li (Journal of Environmental Management, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Experimental testing and machine learning to predict the load-slip behavior of stud connectors in steel-UHPC composite structures - Yong-jian Zhou; Xia Yang; Wu-wu Zou; Cheng-shuo Han (Engineering Structures, 2025)

Regulating excited state of local excitation and charge transfer to boost phototherapeutic effect of AIE-active free radical photosensitizer - Chunwang Guo; Xue Bai; Zihang Ma; Yili Xie; Mingzhe Wang; Yiwen Tang; Yaoqiu Zheng; Shuo Zhao; Yang Liu; Qing Wan (Chemical Engineering Journal, 2025)

One-step forming strategy of highly stable Li4SiO4 for low-concentration CO2 capture - Yu Zhang; Shuo Chen; Shikun Wen; Jiaojiao Li; Rui Yang; Liang Huang; Junya Wang; Ping Ning; Qiang Wang (Chemical Engineering Journal, 2025)

An investigation into microphysical processes of autumn frontal clouds influenced by the warm conveyor belt in Central China - Shuo Jia; Jiefan Yang; Hengchi Lei; Hongbin Chen (Atmospheric Research, 2025)

Energy-Optimized Path Planning for Fully Actuated AUVs in Complex 3D Environments - Shuo Liu; Zhengfei Wang; Tao Wang; Shanmin Zhou; Yu Zhang; Pengji Jin; Guanjun Yang (Journal of Marine Science and Engineering, 2025)
This paper presents an energy-optimized path planning approach for fully actuated autonomous underwater vehicles (AUVs) in three-dimensional ocean environments to enhance their operational range and endurance. A fully actuated AUV is characterized by its high degrees of freedom and precise controllability. Using real terrain data, we construct environmental models incorporating a Lamb vortex and random obstacles. We develop a mathematical model of the AUV’s total energy consumption, accounting for constraints imposed by its fully actuated design and extensive maneuverability. To minimize energy usage, we propose an energy-optimized path planning algorithm that combines energy-optimized particle swarm optimization (EOPSO) and sequential quadratic programming (SQP). The proposed method identifies the optimal path for energy consumption and the corresponding optimal surge speed. The efficacy of the algorithm in optimizing the total energy consumption of the AUV is demonstrated through the simulation of various scenarios. In comparison to other algorithms, paths planned by this algorithm are shown to have superior robustness and optimized energy consumption.

Corrigendum to “Hippocampal MEF2C phosphorylation mediates synaptic plasticity in lead-induced learning and memory impairments” [Toxicology 512 (2025) 154082] - Shuo Yang; Yanhui Zhu; Jinmei Xiao; Lingyu Yan; Xuebing Zhuang; Qi Li; Yue Li; Jie Xie; Guihua Du; Fankun Zhou; Guangqin Fan; Chang Feng (Toxicology, 2025)

An adaptive large neighborhood search with multi-deletion operators for multi-depot green vehicle routing problem with time windows - Yukang Su; Shuo Zhang; Yang Wang; Xing Cui; Yuyang Wu (Swarm and Evolutionary Computation, 2025)

Corrigendum to “Investigation of apparent digestibility, caecal fermentation and microbiota of rabbit fed with raffinose” [Volume 295, May 2025, 105692] - Kai Yang; Shuo Yang; Zixuan Tie; Zhenxin Li; Meinan Ji; Kun Wang; Shugui Zheng; Fangfang Li (Livestock Science, 2025)

Demulsification characteristics of electrostatic–swirling coupling enhanced migration - Guidong Chen; Silong Feng; Shuo Liu; Lin Li; Xiangyi Long; Qiang Yang; Hao Lu (Journal of Water Process Engineering, 2025)

Phytolith formation and its contribution to soil organic carbon sequestration in an Inner Mongolia grassland under long-term nitrogen deposition - Shuo Li; Liangchao Jiang; Guojiao Yang; Xingguo Han; Dongmei Jie; Niankang Chen; Haiyang Zhang (Journal of Environmental Management, 2025)

Volcanism-driven synchronous terrestrial and marine anoxia during the Kungurian (early Permian) - Kai Zhou; Minfang Yang; Shuo Zhang; Ran Gao; Peixin Zhang; Longyi Shao; Weichao Wang; Lei Wang; Jing Lu; Jason Hilton (Gondwana Research, 2025)

Interspecies interactions promote dual-species biofilm formation by Lactiplantibacillus plantarum and Limosilactobacillus fermentum: Phenotypic and metabolomic insights - Bingxin Zhang; Yuxin Sun; Wenyu Han; Wenwen Ge; Zhenbo Xu; Shuo Wang; Zhenquan Yang; Lei Yuan (Food Research International, 2025)

The emulsion-filled gels with different fat contents exhibit various friction behavior and dynamic fat-related texture perception at different temperatures - Yueji Zeng; Sihan Zhang; Ke Fan; Shuo Mu; Yang Luo; Linlin Wang; Xiankang Fan; Fuqing Wang; Ran Wang; Jie Luo (Food Quality and Preference, 2025)

Effects of amino acid addition on aroma quality of pear wine and gene expression of Saccharomyces cerevisiae - Hua Yang; Shuo Ha; Qingbo Zeng; Ming Chen (Food Bioscience, 2025)

Characteristics of Bifidobacterium longum subsp. infantis metabolizing 2’-fucosyllactose: on the basis of comparative genomics, α-L-fucosidase properties and metabolomics - Shuo Yang; Junwu Cai; Yuhan Chen; Qiaohui Li; Yan Li; Xiangchen Meng (Food Bioscience, 2025)

A spatiotemporal mixed-enhanced generative adversarial network for radar-based precipitation nowcasting - Long He; Kun Zheng; Huihua Ruan; Shuo Yang; Jinbiao Zhang; Cong Luo; Siyu Tang; Yunlei Yi; Yugang Tian; Jianmei Cheng (Computers & Geosciences, 2025)

Investigation on the impact of gaseous impurities in coal-fired flue gas on isothermal integrated CO2 capture and utilization to ethylene production via dual functional materials - Shuo Wang; Xiaoyu Zhang; Wei Wei; Yuandong Yang; Shutao Wang; Wenqiang Liu (Chemical Engineering Journal, 2025)

Elucidating the promotional effect of Cr doping on CeTi catalysts for chlorobenzene degradation: Enhancement of redox property and suppression of chlorination reaction - Hao Li; Shuo Yang; Manlin Zhang; Weijia Wang; Jing Gao; Weilong Li; Zitao Qi; Shihan Zhang; Wei Li; Sujing Li (Chemical Engineering Journal, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Schiff-base crosslinked gelatin-mycosporine-like amino acids/dialdehyde starch composite film: a UV-resistant, biodegradable food packaging material - Donghui Wang; Ke Li; Jingyun Zhang; Kaiqing Zhou; Kai Wang; Yingzi Wang; Shuo Yang; Shuxin Wang; Pu Wang; Hao Chen (Chemical Engineering Journal, 2025)

Ratiometric FRET encoding Zr-MOF@Au-FAM/TAMRA nano assemblies based on tetrahedral framework nucleic acid-functionalized magnetic beads and DNA walker for ultrasensitive quantifying enrofloxacin and ciprofloxacin - Hongtao Jiang; Shuo Qi; Beijun Ang; Imran Mahmood Khan; Xiaoze Dong; Zhouping Wang; Junsong Yang (Chemical Engineering Journal, 2025)

Using quantitative evaluation model to assess the environmental benefits of metabolites in flax retting wastewater aerobic compost: The trade-offs of core species build the profiles of beneficial and harmful metabolites converted from lignocellulose - Ying Yang; Zhichao Yang; Jie Kang; Zhenchao Wu; Yangcun Sun; Xinbo Cao; Yuhao Guo; Xiujun Tu; Liangyang Mao; Shuo Li; Weige Yao; Jingping Ge; et al. (Chemical Engineering Journal, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Clinical characteristics and associated factors of macrolide-resistant mycoplasma pneumoniae pneumonia in children: a systematic review and meta-analysis - Shuo Yang; Xinying Liu; Yaowei Han; Huizhe Wang; Yunzheng Mei; Haokai Wang; Na Zhang; Yingying Peng; Xinmin Li (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Molecular docking and molecular dynamics simulations revealed interaction mechanism of acetylcholinesterase with organophosphorus pesticides and their alternatives - Jiawen Yang; Lin Chen; Shuo Wang; Bing Zhao; Ruige Wang (Archives of Toxicology, 2025)

Using a seasonal and trend decomposition algorithm to improve machine learning prediction of inflow from the Yellow River, China, into the sea - Shuo Wang; Ke Yang; Hui Peng (Frontiers in Marine Science, 2025)
The Yellow River is the largest inflow into the Bohai Sea, and its inflow changes directly affect the ecological environment and marine health of the Bohai Sea. Therefore, accurate prediction of the inflow of the Yellow River is crucial for maintaining the ecological balance of the Bohai Sea and protecting marine resources. Time decomposition algorithms, combined with machine learning, are effective tools to enhance the capabilities of inflow prediction models. However future data leakage from decomposition items was ignored in many studies. It is necessary to develop the right method to operate time decomposition to avoid future data leakage. In this study, the inflow from the Yellow River into the sea was predicted based on a machine learning model (light gradient boosting machine, LightGBM) and a time decomposition algorithm (seasonal and trend decomposition using loess, STL), and the future data leakage in different ways of using STL were evaluated. The results showed that the overall performance of the STL–LightGBM model was better than that of the LightGBM model. The STL–LightGBM took the historical inflow for 8 days as the input, and predicted that the average NSE of the next 1–7 days would reach 0.720. Even when the forecast period was 7 days, the STL–LightGBM (NSE: 0.549 for 7-day lead time) was 0.105 higher than the LightGBM (NSE: 0.444 for 7-day lead time). We found that STL pretreatment of the entire test set overestimated the true performance of STL–LightGBM. It is recommended that the STL preprocesses each sample of the test set to avoid future data leakage. The study can provide help for water resources management and offshore environmental management.

Airborne geophysical analysis to decipher salinization for coastal Louisiana - Michael Attia; Frank T.-C. Tsai; Shuo Yang; Burke J. Minsley; Wade H. Kress (Water Research, 2025)

Investigation of apparent digestibility, caecal fermentation and microbiota of rabbit fed with raffinose - Kai Yang; Shuo Yang; Zixuan Tie; Zhenxin Li; Meinan Ji; Kun Wang; Shugui Zheng; Fangfang Li (Livestock Science, 2025)

Comparative study of the toxicity responses of Vallisneria natans and Pistia stratiotes to sulfadiazine under different planting methods - Qihui Li; Weizhen Zhang; Jian Su; Dayang Yang; Shuo Ma; Yi Liu; Xusong Yao; Li Gong; Qianchao Wang; Qi Li (Journal of Hazardous Materials, 2025)

Reaction mechanism of extracting Li and Fe from retired lithium iron phosphate battery powder through roasting and water leaching with sulfamic acid - Zhenning Liu; Zhenan Jin; Linlin Tong; Shuo An; Tenghao Yang (Journal of Cleaner Production, 2025)

A review of biomass porous carbon for carbon dioxide adsorption from flue gas: Physicochemical properties and performance - Zhaoming Li; Shuo Feng; Xu Yang; Honghong Lyu; Shuzhou Wei; Boxiong Shen (Fuel, 2025)

Vine tea (Ampelopsis grossedentata) ameliorates chronic alcohol-induced hepatic steatosis, oxidative stress, and inflammation via YTHDF2/PGC-1α/SIRT3 axis - Qihan Luo; Jiang Qiu; Minxia Chen; Na Yang; Xinyue Li; Shuo Huang; Qing Ma; Zongyuan Li; Dayong Lou; Yu Du; Li Chen; Qing Shen; et al. (Food Research International, 2025)

Elucidation of potential lipid precursors and formation pathways for the warmed-over flavor (WOF) in precooked Chinese stewed beef through lipid oxidation mechanisms - Junmei Liu; Feng Huang; Dong Han; Ying Xu; Shuo Shen; Yanlu Luan; Ping Yang; Chunhui Zhang; Christophe Blecker (Food Chemistry, 2025)

Biomimetic construction of multi-enzyme reactor through artificial antibody-antigen-directed immobilization for cascade catalytic conversion of cellulose to gluconic acid - Shuo Liu; Hongli Chao; Meishan Guo; Ruifang Wang; Dongyu Gu; Yi Wang; Dajun He; Yi Yang (Food Chemistry, 2025)

Exploring the potential of Pediococcus pentosaceus PPF28-8 in a rapid fermentation model for soy sauce flavor enhancement using machine learning - Shuo Wang; Minghui Zeng; Jiaxiu Wang; Shuai Wang; Jia Yang; Yong Sun; Lei Yuan; Zhenquan Yang (Food Bioscience, 2025)

Rapid and interference-resistant colorimetric detection of viable Staphylococcus aureus in food using a broad host range phage SapYZU04 and MnFeO nanozyme - Aiping Deng; Xuan Li; Xiaoxing Fan; Yajie Li; Yelin Han; Tianzhu Guan; Shuo Wang; Guoqiang Zhu; Zhenquan Yang; Wenyuan Zhou (Food Control, 2025)

Engineering chiral carbon dots for triple-mode discrimination of tryptophan enantiomers - Dan Chang; Shuo Wang; Yanan Yan; Jianyang Feng; Jianan Pei; Hu Shi; Yongxing Yang; Lihong Shi; Shaomin Shuang; Chuan Dong (Chemical Engineering Journal, 2025)

FePS3-Nanosheets-Integrated multifunctional nanocomposite hydrogel for multimodal synergistic osteosarcoma therapy and enhanced bone regeneration - Bing Ye; Xirui Jing; Yanlin Su; Wenzhe Sun; Qing Gao; Lian Zeng; Hongwei Lu; Shuo Tang; Yizhou Wan; Tingfang Sun; Zekang Xiong; Xiao Lv; et al. (Chemical Engineering Journal, 2025)

The strong metal-support interaction regulation on cathode–anode coupling catalysts to boost the pollutant degradation - Chuanshun Feng; Qicheng Zhang; Xiuyu Loh; Shuo Chen; Jiawen Wu; An Cai; Bin Chen; Jijie Zhang; Xiaobin Fan; Wenchao Peng; Yang Li (Chemical Engineering Journal, 2025)

Study on Measurement Method and Influencing Factors of Surface Temperature for Rock Under Microwave Irradiation - Zhongjun Ma; Xiaobao Zhao; Shuo Yang; Yanlong Zheng; Yangwei Long; Ping Che (Rock Mechanics and Rock Engineering, 2025)

Improved Boreability Index for Gripper TBMs in Medium- to Strong-Quality Rocks Based on Theoretical Analysis and Field Penetration Tests - Wenkun Yang; Zuyu Chen; Shuangjing Wang; Haitao Zhao; Jianchun Li; Shuo Chen; Chong Shi (Rock Mechanics and Rock Engineering, 2025)

Prediction of Pharmacoresistance in Drug-Naïve Temporal Lobe Epilepsy Using Ictal EEGs Based on Convolutional Neural Network - Yiwei Gong; Zheng Zhang; Yuanzhi Yang; Shuo Zhang; Ruifeng Zheng; Xin Li; Xiaoyun Qiu; Yang Zheng; Shuang Wang; Wenyu Liu; Fan Fei; Heming Cheng; et al. (Neuroscience Bulletin, 2025)

Microscopic augmented reality calibration with contactless line-structured light registration for surgical navigation - Yuhua Li; Shan Jiang; Zhiyong Yang; Shuo Yang; Zeyang Zhou (Medical & Biological Engineering & Computing, 2025)

Polycaprolactam microplastics reduce allelopathic potential of Iris pseudacorus via toxic effects on stimulatory bacteria - Shengpeng Zuo; Qing Zhang; Shuo Yang; Huimei Wang (Ecotoxicology, 2025)

Experimental and Numerical Investigation on Mechanical Properties of Large-Diameter Metallurgically Clad Pipes - Feng Wang; Yanan Gao; Zhiguo Hu; Shuo Yang; Zhenying Cui; Rui Fu; Lin Yuan (Journal of Marine Science and Engineering, 2025)
Bimetallic-clad pipes demonstrate exceptional advantages in transporting corrosive oil and gas through the combination of the load-carrying capacity of the base material and the anti-corrosive function of the thin layer of corrosion-resistant alloy. This study investigates the mechanical properties of 24-inch X65 + Alloy625 metallurgically clad pipes through experimental tests and finite element analysis. Uniaxial tensile testing with digital image correlation reveals uniform deformation between the base and clad layers until interfacial failure initiates at an average strain threshold of 34.17%. Microstructural characterization shows continuous metallurgical bonding, with the X65 layer exhibiting polygonal ferrite and bainitic phases, contrasting with the austenitic equiaxed grain structure of Alloy625. In terms of numerical modeling, finite element analyses that consider both initial geometric imperfections and manufacturing-induced residual stresses are performed to evaluate the bending response of the clad pipe. The effect of initial ovality and residual stresses on its bending capacity is also studied.

Optimization of Adaptive Observation Strategies for Multi-AUVs in Complex Marine Environments Using Deep Reinforcement Learning - Jingjing Zhang; Weidong Zhou; Xiong Deng; Shuo Yang; Chunwang Yang; Hongliang Yin (Journal of Marine Science and Engineering, 2025)
This paper explores the application of Deep Reinforcement Learning (DRL) to optimize adaptive observation strategies for multi-AUV systems in complex marine environments. Traditional algorithms struggle with the strong coupling between environmental information and observation modeling, making it challenging to derive optimal strategies. To address this, we designed a DRL framework based on the Dueling Double Deep Q-Network (D3QN), enabling AUVs to interact directly with the environment for more efficient 3D dynamic ocean observation. However, traditional D3QN faces slow convergence and weak action–decision correlation in partially observable, dynamic marine settings. To overcome these challenges, we integrate a Gated Recurrent Unit (GRU) into the D3QN, improving state-space prediction and accelerating reward convergence. This enhancement allows AUVs to optimize observations, leverage ocean currents, and navigate obstacles while minimizing energy consumption. Experimental results demonstrate that the proposed approach excels in safety, energy efficiency, and observation effectiveness. Additionally, experiments with three, five, and seven AUVs reveal that while increasing platform numbers enhances predictive accuracy, the benefits diminish with additional units.

Creep Behavior Research of Deep-Sea Pressure Hull: A Review - Yuan Zeng; Changli Yu; Shuo Yang (Journal of Marine Science and Engineering, 2025)
Pressure hulls are the primary pressure-bearing structures in submersibles and deep-sea space stations, which are essential for marine scientific research. Due to repeated dive cycles and extended operational periods, these hulls undergo creep deformation over time, posing risks to their structural integrity. This paper provides a comprehensive review of research on the creep behavior of pressure hulls, focusing on three key aspects: creep testing, creep constitutive models, and numerical simulation techniques. Initially, various creep testing methodologies are presented, with the experimental data serving as a foundational basis for subsequent analyses. Experimental data from creep tests form the foundation for constructing and validating constitutive models, which are critical for predicting long-term deformation. The review also explores advanced numerical simulation techniques, such as user subroutines and multiscale modeling, to analyze creep in complex pressure hull structures. Finally, based on the insights from the reviewed studies, the paper proposed potential directions for future research to address current challenges and enhance the design and maintenance of pressure hulls.

Bidirectional denoising method based on Fast Fourier transform analysis for TBM field penetration data - Wenkun Yang; Zuyu Chen; Haitao Zhao; Jianchun Li; Shuo Chen; Chong Shi (Tunnelling and Underground Space Technology, 2025)

IL-11 regulates the biosynthesis of PGE2 through JAK1/STAT3 signaling pathway in bovine granulosa cells - Hanxiao Wu; Xiaoxue Zheng; Shuo Zhou; Peihao Sun; Mingxiao Liu; Liguo Yang; Aixin Liang (Theriogenology, 2025)

Drug resistance detection of canine origin Escherichia coli in China and inhibition by genipin - Nan Niu; Lei-Na Dou; Shuo Yang; Hai-Xin Wang; Shen Zhuang; Yun-Peng Fan; Ying- Qiu Liu; Wei-Min Zhang; Wu-Ren Ma (The Veterinary Journal, 2025)

Pilot study on a physical process for treating petrochemical wastewater - Shaoxuan Li; Binghe Li; Yu Li; Haonan Liu; Shuo Huang; Qiang Yang; Yiqian Liu (Journal of Environmental Management, 2025)

Experimental study on the kinetic characteristics of CO2 hydrate growth in the presence of Gua2SO4 promoter system - Xiao-Fang Lv; Shuai Qin; Yang Liu; Ji-Miao Duan; Chuan-Shuo Wang; Qian-Li Ma; Hai-Yuan Yao; Xiao-Yan Li; Xiao-Wei Li; Shi-Dong Zhou (Journal of Environmental Chemical Engineering, 2025)

Influence of influent suspended solids concentration on a two-stage partial nitrification/anammox process treating liquid digestate of kitchen waste: Nitrogen removal performance and microbial community analysis - Shuo Li; Xiang Chen; Hui Gong; Jing Yang; Qian Guo; Xiankai Wang; Hang Wang; Danyang Zhu; Yanyan Zhang; Shuyan Zhou; Mohammad Azari; Xiaohu Dai (Journal of Environmental Chemical Engineering, 2025)

Experimental and simulation study on the formation and microstructure of ionic liquid microemulsion collectors used for low-rank coal slime - Meng He; Lixin Song; Shuo Yang; Feifei Wang; Gang Hu; Liqing Sun; Lin Li; Xiaofang You (Fuel, 2025)

A novel antioxidant peptide from soybean meal alleviates H2O2-induced oxidative damage via the Keap1-Nrf2-HO-1 pathway - Yiding Yu; Sitong Ma; Yuxi Han; Shuo Zhang; Meng Yang; Zhiyang Du; Zhipeng Yu; Chunmei Liu (Food Research International, 2025)

Establishment of DAS-ELISA and lateral flow immunochromatography for the detection of peanut allergen Ara h 3 after heat-moisture treatment - Shuo Yang; Fuyu Sun; Xiao Wu; Pengbo Huang; Jinglong Qu; Runrun He; Yuanyuan Cui; Jun Xi (Food Chemistry, 2025)

Probiotics and bioactive ingredients from fermented foods for the effective prevention and regulation of hyperuricemia - Lei Yuan; Bing-xin Zhang; Shuo Wang; Zhen-quan Yang (Current Opinion in Food Science, 2025)

Nanowire-filled layered SiC aerogels with excellent thermodynamic properties for thermal insulation at ultrahigh temperatures - Yuanjia Xia; Guobin Chen; Zhen Zhang; Shuang Zhao; Haifei Lu; Shuo Deng; Zichun Yang (Chemical Engineering Journal, 2025)

Natural phenolic Acid-Functionalized polyurethane microcapsules with superior foliar retention and UV protection for improving pesticide efficacy and safety - Yanan Xiao; Mengdie Li; Shuhui Hu; Lin-Lin Yang; Jian Wang; Chang Yan; Yi Tong; Shuo Liu; Liqian Cao; Wenneng Wu; Bo Zhang (Chemical Engineering Journal, 2025)

A highly compressible and expandable cellulose sponge with arch-like lamellar structures for non-compressible hemorrhage - Bingjing Cai; Yawen Fan; Shuo Yang; Chaoqun Che; Xiaoyun Li; Xiaoying Wang (Carbohydrate Polymers, 2025)

Efficient biodegradation of flurochloridone herbicide by Streptomyces parvus strain F-G-2 and its degradation mechanism - Dong Zhao; Shuo Shen; Junlong Feng; Shuqun Deng; Enyu Lu; Chenxu Gao; Yang Zhang; Hongyu Chen; Wei Li (Bioresource Technology, 2025)

Common organic acids in fruit wine and the deacidification strategies - Qingbo Zeng; Shuo Ha; Ming Chen; Chunzhi Zhang; Hua Yang (Systems Microbiology and Biomanufacturing, 2025)

Distribution and risk assessment of heavy metals in the upper, middle, and lower reaches of the Yellow River wetlands - Yiqiao Zhou; Shuo Li; Fan Yang; Qingsong Guan; Ning Zhang (Limnology, 2025)

Gushan virus: a newly discovered virus found in mosquitoes of Shandong, China - Long Yuan; Yongchao Yang; Wenbing Zhu; Shuo Feng; Xinbei Li; Jian Song; Yujing Zhu; Guoyu Niu (Virus Genes, 2025)

Assimilation of MetOp-C AMSU-A Data Using the ARMS as an Observation Operator in the YH4DVAR System - Tengling Luo; Shuo Ma; Weimin Zhang; Yanlai Zhao; Yi Yu; Jinhui Yang; Shaoying Li (Journal of Meteorological Research, 2025)

Inflammation May Mediate the Effects of Fluoride on Liver and Kidney Function of Adults: Cross-Sectional Studies in China - Minghao Geng; Yi Cheng; Leizhen Duan; Guangshen Dong; Shuo Yang; Xuecheng Jiao; Weihua Jia; Hui Huang; Ming Dou; Xiaoli Fu; Fangfang Yu; Yuhui Du; et al. (Biological Trace Element Research, 2025)

Feature fusion method for rock mass classification prediction and interpretable analysis based on TBM operating and cutter wear data - Wenkun Yang; Zuyu Chen; Haitao Zhao; Shuo Chen; Chong Shi (Tunnelling and Underground Space Technology, 2025)

Hippocampal MEF2C phosphorylation mediates synaptic plasticity in lead-induced learning and memory impairments - Shuo Yang; Yanhui Zhu; Jinmei Xiao; Lingyu Yan; Xuebing Zhuang; Qi Li; Yue Li; Jie Xie; Guihua Du; Fankun Zhou; Guangqin Fan; Chang Feng (Toxicology, 2025)

Distinct baseline toxicity of volatile organic compounds (VOCs) in gaseous and liquid phases: Mixture effects and potential molecular mechanisms - Shuo Yang; Zhiwei Shao; Ling N. Jin; Liuwen Chen; Xiang Zhang; Mingliang Fang; Dan Li; Jianmin Chen (Journal of Hazardous Materials, 2025)

Crack removal of carrot based on the Cartesian robot with a novel path planning method - Weijun Xie; Kai Huang; Shuo Wei; Hanyu Fu; Deyong Yang (Journal of Food Engineering, 2025)

Identification of key ecological restoration areas based on ecological security patterns and territorial spatial ecological restoration zoning: A case study of the middle and lower reaches of the Yellow River in China - Zhongxiao Cong; Shuo Yang; Baokun Zhu; Yixin Wang; Jinhua Liu (Journal for Nature Conservation, 2025)

Cyclic plasticity of hardened oil well cement paste: A nonlinear kinematic hardening perspective - Linlin Wang; Shuo Chen; Shuitao Zhang; Jiyun Shen; Rongwei Yang (Geomechanics for Energy and the Environment, 2025)

Exploring the impact of ethanol blending on ammonia combustion: Multivariate effects on laminar burning characteristic and novel insights into NO generation mechanism in ammonia/ethanol mixtures - Jiangping Tian; Hongen Yang; Xiaolei Zhang; Qingxing Zhou; Yifang Ren; Mingfei Lu; Shuo Yin; Mingyuan Ye; Yang Wang; Zechuan Cui (Fuel, 2025)

Corrigendum to ‘Testing adulterated liquid-egg: developing rapid detection techniques based on colorimetry, electrochemistry, and interfacial fingerprinting’ [Food Chemistry, Volume 444, 30 June 2024, 138674] - Shuo Yang; Fuming Yang; Wenhao Dou; Yuan Chi; Yujie Chi (Food Chemistry, 2025)

Lactobacillus paracasei GF027 promotes growth and cognitive development in juvenile rats via regulating intestinal microecology and nourishing the brain - Hang Yang; Yuanyifei Wang; Haiwei Liu; Jin Wang; Dancai Fan; Yi Sun; Huan Lv; Wenhui Fu; Shuo Wang (Food Bioscience, 2025)

Associations between long-term exposure to fine particulate matter and its constituents with lung cancer incidence: Evidence from a prospective cohort study in Beijing, China - Jinlong Hu; Lei Yang; Ning Kang; Ning Wang; Luyan Shen; Xi Zhang; Shuo Liu; Huichao Li; Tao Xue; Shaohua Ma; Tong Zhu (Environmental Pollution, 2025)

Mechanisms of phosphorus conversion in chicken manure and straw composting systems regulated by flax-retting wastewater and a combination of flax-retting wastewater and biochar - Shuo Li; Jie Kang; Zhenchao Wu; Yangcun Sun; Xiujun Tu; Yuhao Guo; Liangyang Mao; Ying Yang; Weige Yao; Jingping Ge (Chemical Engineering Journal, 2025)

Experimental and kinetic study of laminar combustion characteristics of ammonia/air mixtures under oxygen enrichment at high temperature and pressure - Jiangping Tian; Chunlei Hou; Jianing Liu; Song Shi; Hongen Yang; Qingxing Zhou; Shuo Yin; Yuantao Yu; Xiaolei Zhang; Zechuan Cui (Chemical Engineering Journal, 2025)

Structure optimized pyrenetetraone composites for long-life high-energy Al-ion batteries - Mian Cai; Chengyun Ma; Zehao Li; Jingwen Li; Shuo Gao; Hao Yan; Zhengkun Du; Huiping Du; Xin Yang; Yaqun Wang; Ze Yang (Chemical Engineering Journal, 2025)

Establishing age-group specific reference intervals of human salivary proteome and its preliminary application for epilepsy diagnosis - Nianci Xue; Xia Xia; Yini Wang; Xianju Li; Nairen Zheng; Yi Wang; Baoying Gong; Bin Zhang; Yanjia Chen; Yue Chen; Yanjuan Li; Hong Cao; et al. (Science China Life Sciences, 2025)

Correction to: Seepage behaviors of gap-graded sand subjected to suffusion - Minqiang Meng; Shuo Zhang; Zhifa Wei; Jingxuan Peng; Xiujuan Yang; Henghui Fan (Bulletin of Engineering Geology and the Environment, 2025)

Nutrient Availability Shapes the Resistance of Soil Bacterial Community and Functions to Disturbances in Desert Ecosystem - Hang Gao; Yuan Song; Mingyu Li; Min Gao; Ziheng Peng; Haibo Pan; Jiejun Qi; Shi Chen; Yu Liu; Yang Wang; Chujie Jin; Gehong Wei; et al. (Environmental Microbiology, 2025)
Climate change has exposed desert ecosystems to frequent extreme disturbances, including wet‐dry cycles and freeze–thaw events, which accelerate desertification on a global scale. The limited nutrient availability characteristic of these ecosystems may constrain microbial survival and growth, making them more vulnerable to environmental perturbations and stressors. However, how nutrient availability modulates the stability of soil ecological communities and functions in desert ecosystems remains poorly understood. In this study, we examined how nutrient addition, applied either before or after disturbances, affects the resistance of bacterial communities and multifunctionality to drought and freeze events in desert ecosystems. Our findings revealed that freeze–thaw events, rather than drought, significantly reduced bacterial diversity, with all disturbances altering the community structure. Pre‐disturbance nutrient addition notably improved the resistance of soil bacterial diversity and community composition to disturbances, which played a critical role in maintaining multifunctionality in desert ecosystems. This enhanced bacterial resistance was strongly associated with increased bacterial network complexity and the enrichment of disturbance‐tolerant taxa. Our results highlight the pivotal role of nutrient availability in stabilising soil bacterial communities and multifunctionality under extreme climatic conditions in desert ecosystems. These findings offer valuable insights and practical strategies for the ecological protection and management of desertification.

Potential of hyperspectral LiDAR in individual tree segmentation: A comparative study with multispectral LiDAR - Ao Wang; Shuo Shi; Jian Yang; Bowei Zhou; Yi Luo; Xingtao Tang; Jie Du; Sifu Bi; Fangfang Qu; Chengyu Gong; Wei Gong (Urban Forestry & Urban Greening, 2025)

Numerical study on hydrodynamic characteristics, wave forces and dynamic responses of offshore jacket platform under tsunami-like solitary waves - Hong Lin; Shuo Zhang; Alexander Moiseevish Uzdin; Longcheng Wei; Qi Fan; Lei Yang (Ocean Engineering, 2025)

Oily-bubble and its typical applications in enhancing the separation and mass transfer processes: A review and perspectives - Tianze Chen; Shengpeng Su; Shuo Chen; Yizhuang Wang; Yanfang Huang; Bingbing Liu; Hu Sun; Shuzhen Yang; Guihong Han (Minerals Engineering, 2025)

Resource utilization of electric arc furnace dust: Efficient wet desulfurization and valuable metal leaching kinetics investigation - Hanwei Yang; Kaiqiang Hu; Jiayu Feng; Ping Ning; Fang Wang; Shuo Cui; Lijuan Jia (Journal of Environmental Management, 2025)

Experimental study of data-driven model predictive control on transcritical CO2 thermal system in electric vehicles - Tongyu Miao; Shuo Zong; Xu Yang; Wenyi Wang; Yulong Song; Feng Cao (International Journal of Refrigeration, 2025)

Interactive mechanisms of CF3CHFCF3 with H2-CH4-air mixture explosion: A synergistic study using chemical kinetic simulation and density functional theory - Hongfu Mi; Nan Luo; Peng Shao; Hang Yi; Shuo Wang; Wenhe Wang; Yihui Niu; Ao Yang; Xinsheng Jiang; Yu Feng; Li-Huan Zhu; Chi-Min Shu (Fuel, 2025)

Proteomics-guided isolation of a novel serine protease with milk-clotting activity from tamarillo (Solanum betaceum Cav.) - Tong Zhang; Zhihong Yang; Yingcui Zhang; Lunzhao Yi; Fengmin Duan; Qiong Zhao; Ying Gu; Shuo Wang (Food Chemistry, 2025)

One simple and integrated nano-inspection platform for high-throughput detection of clenbuterol - Lu Yang; Tong Zhai; Jing Wang; Hong Zheng; Jing-Min Liu; Shuo Wang (Food Chemistry, 2025)

SIGIRR plays a dual role in zebrafish infected with Edwardsiella piscicida: Boosting digestive system wellness and mitigating inflammation - Ting Yu; Shuo Yang; Lifeng Zhang; Dan Deng; Xiao Zhang; Kai Luo; Weihua Gao; Bei Wang; Shuhuan Zhang; Qiaoqing Xu (Fish & Shellfish Immunology, 2025)

Extracellular vesicles from mechanical loading stimulated-macrophages favor fracture healing through targeting Adrb2 of osteoblasts - Haiyue Zhao; Weijian Liu; Peng Wang; Shuo Zhang; Xin Xing; Zijian Yan; Lei Wang; Dengying Wu; Fengkun Wang; Shuai Yang; Xiangtian Deng; Xinyan Li; et al. (Chemical Engineering Journal, 2025)

Effect of inoculated sludge concentration on start-up of anammox reactor: Nitrogen removal performance and metabolic pathways - Qian Guo; Xiang Chen; Hui Gong; Jing Yang; Shuo Li; Danyang Zhu; Xiankai Wang; Kun Li; Yanyan Zhang; Shuyan Zhou; Kejin Chen; Xiaohu Dai (Bioresource Technology, 2025)

Genome-wide CRISPR screens identify CLC-2 as a drug target for anti-herpesvirus therapy: tackling herpesvirus drug resistance - Fayu Yang; Nan Wei; Shuo Cai; Jing Liu; Qingping Lan; Hao Zhang; Lu Shang; Bo Zheng; Mi Wang; Yingchun Liu; Lifang Zhang; Chenzhong Fei; et al. (Science China Life Sciences, 2025)

Seepage behaviors of gap-graded sand subjected to suffusion - Minqiang Meng; Shuo Zhang; Zhifa Wei; Jingxuan Peng; Xiujuan Yang; Henghui Fan (Bulletin of Engineering Geology and the Environment, 2025)

Probiotic DNA regulates intestinal Th2 polarization by inducing epithelial cells to produce PD-L1 - Shuo Song; Hanqing Zhang; Le Liu; Minyao Li; Xiangyu Wang; Haotao Zeng; Miao Zhao; Pixin Ran; Qing Shu; Pingchang Yang (Apoptosis, 2025)

Evaluation on the antiviral activity of luteolin against largemouth bass virus - Guang-shuo Wang; Jia-cheng Qin; Yun-long Qin; Yao Wang; Bin Yang; Xiang Liu; Fei Ling; Gao-xue Wang (Aquaculture, 2025)

Regulating self-assembly of concomitant isotropic Ag78 and anisotropic Ag110 nanoclusters - Xin-Lan Peng; Shuo Huang; Yu-Jing Zhao; Xi-Ming Luo; Hai-Yang Li; Jia-Hua Hu; Jia-Hong Huang; Shuang-Quan Zang (Science Bulletin, 2025)

An effective strategy for high-value utilization of chromite ore processing residue (COPR) through reductive alkali roasting and physical separation - Cheng Tian; Cunfang Lu; Jun Yang; Rui Xu; Min Zhang; Juan Wen; Yelei Wang; Shuo Zhang; Yuanyuan He; Dan Luo; Huazheng Luo; Xingran Zhang (Process Safety and Environmental Protection, 2025)

PagNAC2a promotes phloem fiber development by regulating PagATL2 in poplar - Yu Guo; Yang-Xin Shi; Shuo Song; Yan-Qiu Zhao; Meng-Zhu Lu (Plant Science, 2025)

Construction of novel quaternary ammonium nitroxy-hybrid rhenium adsorbent system with dual mechanisms and separation research from rhenium (VII)/copper (II) - Qian Cheng; Enming Luo; Lilin Gan; Wenzheng Luo; Dingfeng Yang; Hongquan Fu; Shuo Li (Journal of Water Process Engineering, 2025)

Divergent responses of an armored and an unarmored dinoflagellate to ocean acidification - Wei-Ping Zhang; Shuo-Yu Zhang; Yang Zhou; Wen-Jing Sun; Shu-Feng Zhang; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Harmful Algae, 2025)

Prediction of hydrate formation boundaries in pure water and salt/alcohol containing systems based on prior knowledge and artificial intelligence - Shu-Kai Chen; Xiao-Fang Lv; Jian-Ping Ding; Yang Liu; Ji-Miao Duan; Hui Du; Chuan-Shuo Wang; Ming-Guo Peng; Qian-Li Ma; Shi-dong Zhou (Fuel, 2025)

An antifouling electrochemical sensor based on a U-shaped four-in-one peptide and poly(3,4-ethylenedioxythiophene) for vancomycin detection in fresh goat milk - Yonghui Li; Xujun Pu; Yangyue Ding; Lunzhao Yi; Yukun Yang; Ying Gu; Shuo Wang (Food Chemistry, 2025)

Synbiotic potential of Bifidobacterium longum subsp. infantis H11 in combination with human milk oligosaccharides in cellular barrier protection - Shuo Yang; Yuhan Chen; Junwu Cai; Yan Li; Qian Su; Xiangchen Meng (Food Bioscience, 2025)

A scalable wood-based interfacial evaporator assisted with localized joule heating for round-the-clock operations - Yang Ming; Shuo Shi; Wei Cai; Jing Liu; Daming Chen; Xin Hu; Rujun Yu; Xia Zhou; Benjamin Tawiah; Bin Fei (Chemical Engineering Journal, 2025)

Phototunable phosphorescence energy transfer based on photodimerization of coumarin-12-crown-4 accelerated by γ-cyclodextrin - Hui-Juan Wang; Yan-Tao Li; Ming-Che Shao; Chang-Shuo Yu; Jin-Yao Yang; Lingyang Liu; Suna Wang; Jianmin Dou (Chemical Engineering Journal, 2025)

Hydrogen-Bonded organic framework Containing stacked Cu2+ for photocatalytic reduction of CO2 to C2H4 - Mengmeng Zhou; Debo Ding; Yansong Shi; Keke Wang; Qin Wang; Xiahe Chen; Hai-Min Shen; Teng-Shuo Zhang; Yun-Fang Yang; Jiexiang Xia; Huaming Li; Yuanbin She (Chemical Engineering Journal, 2025)

Evaluating the liquid egg white freshness: Development, mechanistic analysis and application of a novel electrochemical method-based rapid detection technique - Shuo Yang; Fuming Yang; Yuan Chi; Yujie Chi (Chemical Engineering Journal, 2025)

Plasma-enhanced methanol steam reforming over Pt/In2O3-ZnO/Al2O3 catalyst with ultralow Pt-loading for in-situ H2 production - Hao-Yu Lian; Shuo Geng; Yi-Zhi Wang; Yuan Lv; Hao-Chen Yang; He Zhang; Xiao-Qing Deng (Chemical Engineering Journal, 2025)

Research progress of chlorine corrosion resistance in seawater electrolysis: Materials and technologies - Li-Juan Yang; Hao-Yue Guan; Shuo Yuan; Tao Sun; An-Ning Jiang; Ji-Jun Feng (Chemical Engineering Journal, 2025)

Highly sensitivity and wide-range flexible humidity sensor based on LiCl/cellulose nanofiber membrane by one-step electrospinning - Xiaomeng Liu; Lang Wang; Ying Lei; Xiao Li; Chunzu Cheng; Leixin Yang; Long Jiao; Shuo Yang; Dengkun Shu; Bowen Cheng (Chemical Engineering Journal, 2025)

An active-conductive layer stacked sensor platform for real-time detection of heavy metal ions - Yuping Yang; Lijia Xu; Yongpeng Zhao; Yuchao Wang; Zhijun Wu; Zhiliang Kang; Zhiyong Zou; Hui Huang; Yong He; Fei Liu; Zuoliang Tang; Ao Feng; et al. (Chemical Engineering Journal, 2025)

An optimised molecular-based method for ecological study of tardigrades in soils - Zi-Yang He; Hang-Wei Hu; Keren Wu; Li Bi; Shuo Na; Anthony Weatherley; Michael Nash; Ji-Zheng He (Soil Biology and Biochemistry, 2024)

Selection of engineered degradation method to remove microplastics from aquatic environments - Ruizhen Tong; Bo Wang; Na Xiao; Shuo Yang; Yan Xing; Yanhua Wang; Baoshan Xing (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Estimation of daily XCO2 at 1 km resolution in China using a spatiotemporal ResNet model - Chao Wu; Shuo Yang; Donglai Jiao; Yixiang Chen; Jing Yang; Bo Huang (Science of The Total Environment, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Tuning microenvironment of Bi2O3 nanosheets via Ce doping for promoting CO2 electrolysis to formate - Rongqian Ning; Fei Liu; Shuo Geng; Chenyue Li; Yifan Yang; Lixiong Xu; Xiaodan Wang (Journal of Environmental Chemical Engineering, 2024)

Electrostatic self-assembly of hydrotalcite-based g-C3N4 composites for adsorption and photocatalytic degradation of aqueous norfloxacin - Xiaodong Yang; Minghui Li; Zhiyong Hou; Xuefei Yang; Yuanxia Guo; Shuaiqi Luo; Jin Zhao; Kai Wang; Pengkai Sun; Qiang Yang; Rui Chen; Shuo Yang; et al. (Journal of Environmental Chemical Engineering, 2024)

Age and provenance of the Baluntai arc-related complex (NW China): Implications for the middle Silurian − Early Carboniferous accretionary tectonics of the Central Tianshan arc in the southern Altaids - Tongyang Zhao; Wenjiao Xiao; Qigui Mao; Ping Li; Shuo Yang (Journal of Asian Earth Sciences, 2024)

Concurrent removal of Fe(II), Cu(II), and Zn(II) cations from acid mine drainage by an industrial solid waste - Steel slag: Behaviors and mechanisms - Mingyuan Yang; Cunfang Lu; Shuo Zhang; Yelei Wang; Rui Xu; Min Zhang; Juan Wen; Zilong Li (Environmental Research, 2024)

A recommendation model for optimizing transfer learning hyper-parameter settings in building heat load prediction with limited data samples - Di Bai; Shuo Ma; Xiaochen Yang; Dandan Ma; Xiaoyu Ma; Hongting Ma (Energy and Buildings, 2024)

Evaluating the thresholds for predicting post-earthquake debris flows: Comparison of meteorological, hydro-meteorological and critical discharge approaches - Zhen-lei Wei; Xuan-mei Fan; Jie Yang; Zong-shuo Zhang; Cheng-bin Zou (Engineering Geology, 2024)

Constructing valid Li+ fast-transfer channels on novel P(TPC@Lys-Li) separator to enable security, high energy density, and controllable Li dendrites for lithium-metal batteries - Lei Ding; Dandan Li; Sihang Zhang; Shuo Zhang; Zhaoyang Wang; Fanghui Du; Pengfang Zhang; Feng Yang (Chemical Engineering Journal, 2024)

Antibacterial bioadaptive scaffold promotes vascularized bone regeneration by synergistical action of intrinsic stimulation and immunomodulatory activity - Yuhan Qian; Chenglin Li; Qian Feng; Xiaojun Mao; Guang Yang; Shuo Chen; Tao Li; Xiaojun Zhou; Chuanglong He (Chemical Engineering Journal, 2024)

Crocin-1 laden thermosensitive chitosan-based hydrogel with smart anti-inflammatory performance for severe full-thickness burn wound therapeutics - Xiansen Lv; Hui Li; Ya Chen; Yanting Wang; Jinhua Chi; Shuo Wang; Yan Yang; Baoqin Han; Zhiwen Jiang (Carbohydrate Polymers, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

A Protocol for Body MRI/CT and Extraction of Imaging-Derived Phenotypes (IDPs) from the China Phenobank Project - Chengyan Wang; Shuo Wang; Sha Hua; Ruokun Li; Yan Li; Zhang Shi; Kai Feng; Lizhen Lan; Meng Liu; Xutong Kuang; Xueqin Xia; Shihai Zhao; et al. (Phenomics, 2024)

Roseomonas populi sp. nov., an acetate-degrading bacteria isolated from the stem of Populus tomentosa - Yao Cheng; Wen Zhu; Shuo Han; Jingjing Yang; Guanqi Wu; Guozhu Zhao; Xiangwei He (Antonie van Leeuwenhoek, 2024)

A Fast Adaptive AUV Control Policy Based on Progressive Networks with Context Information - Chunhui Xu; Tian Fang; Desheng Xu; Shilin Yang; Qifeng Zhang; Shuo Li (Journal of Marine Science and Engineering, 2024)
Deep reinforcement learning models have the advantage of being able to control nonlinear systems in an end-to-end manner. However, reinforcement learning controllers trained in simulation environments often perform poorly with real robots and are unable to cope with situations where the dynamics of the controlled object change. In this paper, we propose a DRL control algorithm that combines progressive networks and context as a depth tracking controller for AUVs. Firstly, an embedding network that maps interaction history sequence data onto latent variables is connected to the input of the policy network, and the context generated by the network gives the DRL agent the ability to adapt to the environment online. Then, the model can be rapidly adapted to a new dynamic environment, which was represented by the presence of generalized force disturbances and changes in the mass of the AUV, through a two-stage training mechanism based on progressive neural networks. The results showed that the proposed algorithm was able to improve the robustness of the controller to environmental disturbances and achieve fast adaptation when there were differences in the dynamics.

Reducing automobile commuting in inner-city and suburban: Integrating land-use and management intervention - Shuo Yang; Leyu Zhou; Chang Liu; Yixin Guo; Shan Sun; Liang Guo; Xiaoli Sun (Transportation Research Part D: Transport and Environment, 2024)

Nonlinear associations between design, land-use features, and active travel - Zhehao Zhang; Shuo Yang; Leyu Zhou; Haiming Wang (Transportation Research Part D: Transport and Environment, 2024)

Bee venom prompts the inhibition of gefitinib on proliferation, migration, and invasion of non-small cell lung cancer cells via EGFR-mediated autophagy - Shihui Xie; Shuo Han; Jietao Gong; Zhiyuan Feng; Yang Sun; Hong Yao; Peiying Shi (Toxicon, 2024)

Ameliorative effect of Schisandrol B against Diosbulbin B-induced hepatotoxicity via inhibiting CYP3A4-mediated bioactivation - Dongju Lin; Shuo Wang; Bufan Yang; Guangyao Li (Toxicology and Applied Pharmacology, 2024)

Elevated temperature as the dominant stressor on the harmful algal bloom-causing dinoflagellate Prorocentrum obtusidens in a future ocean scenario - Wei-Ping Zhang; Hui Wei; Shuo-Yu Zhang; Shu-Feng Zhang; Yang Zhou; Wen-Jing Sun; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Science of The Total Environment, 2024)

Effect of water migration on changes of quality and volatile compounds in frozen Penaeus monodon - Chuang Pan; Shuo Shi; Xianqing Yang; Huan Xiang; Di Wang; Yongqiang Zhao; Qianqian Ouyang (Food Chemistry, 2024)

An in-depth review of the dermal toxicity of T-2 toxin: Clinical symptoms, injury mechanisms, and treatment approach - Jiayan Fan; Wenxi Song; Youshuang Wang; Shuo Li; Cong Zhang; Xuebing Wang; Xu Yang (Food and Chemical Toxicology, 2024)

A review of deep-seawater samplers: Principles, applications, performance, and trends - Shijun Wu; Zhiheng Chen; Shuo Wang; Jian Zhang; Canjun Yang (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Hierarchical structural design of cobalt sulphide nanoparticles/nickel sulphide for high-performance supercapacitors - Xin Sun; Shang Wu; Jiajia Wang; Jincai Yang; Shuo Tian; Qinzheng Hu; Liang Chang; Zhe Wang; Yuzhi Sun; Yanbin Wang; Quanlu Yang (Chemical Engineering Journal, 2024)

Nondestructive electrochemical capacity restoration of LiNi1/3Co1/3Mn1/3O2 cathode for lithium batteries - Chenyu Bai; Yiding Jiao; Wei Mao; Fangyan Li; Shuo Yang; Jie Song; Yiran Li; Luhe Li; Yu Deng; Peng Wang; Ye Zhang (Chemical Engineering Journal, 2024)

A high-entropy electrode material for electrobiochemical and eletrophysiological signals detection - Liangtao Yang; Zilong Hu; Zhengchen Xiang; Jie Zhou; Xue Wang; Qing Liu; Lu Gan; Shuo Shi; Wendong Yang; Yi Zhang; Jinglong Wu (Chemical Engineering Journal, 2024)

Experimental cyclic testing of masonry pier-spandrel substructures reinforced with engineered cementitious composites overlay - Tong Li; Wei Zhang; Zhengtao Qiu; Shuo Yang; Yangxi Zhang; Mingke Deng (Bulletin of Earthquake Engineering, 2024)

Thermal environmental and energy effects of vertical greening system under the influence of localized urban climates - Zhi-Dian Jiang; Shu-Long Luo; Xing Shi; Shuo-Ning Tang; Feng Qian; Feng Yang (Urban Forestry & Urban Greening, 2024)

Glutamine metabolism in fluorosis: Integrated metabolomics and transcriptomics analysis - Yue Ba; Shu Niu; Zichen Feng; Shuo Yang; Shuiyuan Yu; Chaofan Shi; Xuecheng Jiao; Guoyu Zhou; Fangfang Yu (Science of The Total Environment, 2024)

An innovative enhanced flotation approach of non-metallic components in waste printed circuit boards: Application of pyrolysis oil as self-generated collector - Chun-chen Nie; Qian-yun Sun; Xi-guang Li; Shuo Yang; Fei-fei Wang; Gang Hu; Si-qi Jiang; Xiang-nan Zhu; Lin Li; Xiao-fang You (Process Safety and Environmental Protection, 2024)

Active vibration control for ship pipeline system based on PI-LQR state feedback - Shuo Zhang; Lu Liu; Xiaomeng Zhang; Yukang Zhou; Qi Yang (Ocean Engineering, 2024)

Fabrication of chitosan-based smart film by the O/W emulsion containing curcumin for monitoring pork freshness - Yanhong Liu; Guangrao Chen; Yajiao Yang; Ruonan Wu; Lingling Zhang; Xiwang Mu; Shuo Wang (Journal of Food Engineering, 2024)

Enhanced and robust nitrogen removal using an integrated zeolite and partial denitrification anammox process - Shuo Wang; Tan Jiang; Xiang Hao; Yu Dai; Jiayi Yang; Bo Wang (Journal of Environmental Management, 2024)

Facile preparation of hollow covalent organic frameworks as superior and universal matrix clean-up micro-structures for high throughout determination of food hazards - Tong Zhai; Dan Qiao; Jing Wang; Chun-Yang Li; Lu Yang; Jin Wang; Jing Wu; Qisijing Liu; Jing-Min Liu; Shuo Wang (Food Chemistry, 2024)

Advancements and future perspectives in the study of oligosaccharides derived from edible-medicinal mushrooms - Shuo Wang; Jiajie Qi; Xiaoming Cai; Weijie Wu; Zhuo A. Wang; Siming Jiao; Caihong Dong; Yi Li; Zhenquan Yang (Food Bioscience, 2024)

Inhibition effect of marine active peptides SF on dual-species biofilms of Vibrio parahaemolyticus and Aeromonas sobria - Xinran Lv; Wenqi Yang; Shuilin Liu; Xueqing Liu; Shuo Yuan; Le An; Anqi Ren; Fengling Bai; Jianrong Li; Xuepeng Li; Yuqiong Meng; Rui Ma (Food Bioscience, 2024)

Multi-enzyme mimic nanozyme with enhanced catalysis for methylene blue probe promotes the one-step detection of tau protein - Xiyu Chen; Shuo Yang; Huikai Shao; Sheng Wang; Jianjun Xie; Qiwen Liu; Yang Huang; Ning Gan; Shengfeng Huang (Chemical Engineering Journal, 2024)

Universal and large-scale transform engineering from commercial metals to micron/nanoporous metals via an induced oxidation-reduction reaction - Zhihong Wang; Yingshuang Guo; Shuo Wang; Zhengjia Wang; Weiming Lü; Kongfa Chen; Qingxin Yang; Zhe Lü (Chemical Engineering Journal, 2024)

Structurally optimized rosette-like microspheres carbon with Fe-Ni single atom sites for bifunctional oxygen electrocatalysis in Zinc-Air batteries - Chaoyang Liu; Shang Wu; Shuo Tian; Jincai Yang; Jiankun Li; Quan Guan; Fenping Yin; Xiaoming Xiang; Yanbin Wang; Xiaoyi Meng; Quanlu Yang (Chemical Engineering Journal, 2024)

Natural β-carotene based nanodrug: A promising phosphatidylinositol 3-kinase targeting strategy to treat oral carcinogenesis - Xing Wang; Zhuo Wan; Shuo Yang; Lili Ma; Qi Zhan; Jianqiu Jin; Zuoying Yuan (Chemical Engineering Journal, 2024)

Cyclodextrin-based host-guest hierarchical fire retardants: Synthesis and novel strategy to endow polylactic acid fire retardancy and UV resistance - Jing Zhang; Xiuqin Zhang; Rui Wang; Wenqing Wang; Hui Zhao; Shuo Yang; Zhenfeng Dong; De-Yi Wang; Ye-Tang Pan (Carbohydrate Polymers, 2024)

Unravelling ice growth characteristics beneath cloud tops with joint analysis of airborne Ka-band radar and Himawari observations - Shuangzhi You; Delong Zhao; Haoran Li; Wei Zhou; Yuanmou Du; Ping Tian; Jiujiang Sheng; Wei Xiao; Fei Wang; Hui He; Mengyu Huang; Deping Ding; et al. (Atmospheric Research, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Regulation of Tert methylation alleviates food allergy via regulating the Tert-IL10 signal pathway - Haotao Zeng; Lingzhi Xu; Jiangqi Liu; Lihua Mo; Minyao Li; Shuo Song; Xuejie Xu; Shihan Miao; Miao Zhao; Pingchang Yang (Immunologic Research, 2024)

Analysis of binding and authentic virus-neutralizing activities of immune sera induced by various monkeypox virus antigens - Shuo Song; Zuning Ren; Jiayin Chen; Mengjun Li; Yushan Jiang; Yingxia Liu; Bao Zhang; Hongzhou Lu; Wei Zhao; Chenguang Shen; Yang Yang (Immunologic Research, 2024)

Unearthing the impact of urban sprawl on transport carbon dioxide emissions: Fresh evidence from 274 Chinese cities - Tianheng Shu; Taofang Yu; Xia Liao; Shuo Yang (Journal of Geographical Sciences, 2024)

Effects of AI-2 quorum sensing related luxS gene on Streptococcus suis formatting monosaccharide metabolism-dependent biofilm - Shuji Gao; Shuo Yuan; Yingying Quan; Wenjie Jin; Yamin Shen; Baobao Liu; Yuxin Wang; Yang Wang (Archives of Microbiology, 2024)

The Role of miRNA in Hyperthyroidism Induced by Excessive Iodine in Drinking Water - Zhihan Yang; Yishan Dong; Shuo Wang; Jing He; Zheng Shen; Jin Cheng; Jinyu Li; Qiaoling Liu; Ziqi Xu; Dianjun Sun; Wei Zhang (Biological Trace Element Research, 2024)

Application and comparison of RBF and BP neural networks for lithology identification of Permian volcanic rocks in the Shunbei area of the Tarim Basin in China - Shuo Shi; Wenlong Ding; Zhan Zhao; Ruiqiang Yang; Teng Zhao; Jinhua Liu; Tan Zhang (Journal of Earth System Science, 2024)

Extraction and modeling of carrot crack for crack removal with a 3D vision - Weijun Xie; Kai Huang; Shuo Wei; Deyong Yang (Computers and Electronics in Agriculture, 2024)

Contrasting range changes and drivers of four forest foundation species under future climate change in China - Weixue Luo; Chengxiang Sun; Shuo Yang; Wenke Chen; Yuhong Sun; Zongfeng Li; Jinchun Liu; Wenjing Tao; Jianping Tao (Science of The Total Environment, 2024)

Ferrum effect on pyrolysis of IL swelling modified coal: Experiment and simulation - Zhihao Li; Beiji Yang; Shuo Yang; Feifei Wang; Qingbiao Wang; Lin Li; Xiaofang You (Minerals Engineering, 2024)

Diverse apatite geochemical compositions in early Paleozoic granitoids of the North Qinling orogen, China: Insights into their petrogenesis and magma sources - Leran Hao; Debin Yang; Anqi Wang; Yikang Quan; Xiangyu Yan; Shuo Wang (Lithos, 2024)

Enhanced nitrogen removal from low C/N municipal wastewater through nitrification, partial denitrification and anammox via a step-feed strategy: Synergistic contribution by bacteria in biofilm and floc sludge - Wenjie Li; Lu Wang; Xiaodi Li; Yu Dai; Shuo Wang; Wen Wang; Jiayi Yang; Bo Wang (Journal of Water Process Engineering, 2024)

Flexible roles of TiO2 in enhancing carrier separation for the high photocatalytic performance of water treatment under different spectrum sunlight - Zhongxi Lu; Shaosheng Rao; Shuo Li; Xiaohui Yu; Haopeng Jiang; Yangyang Sun; Weikang Wang; Lele Wang; Juan Yang; Qinqin Liu (Journal of Water Process Engineering, 2024)

The research and application of technology and core components in commercial refrigeration and freezing Systems：A review - Hailing Fu; Shuo Huang; Yuan Li; Jiasen Cheng; Yang Guo; Kang Wang; Ranran Sun (Journal of Stored Products Research, 2024)

Increasing contamination of polycyclic aromatic hydrocarbons in Chinese soils - Shuo Dai; Qing Zhou; Yadi Yang; Yanni Zhang; Songhe Zhang; Yijun Yao (Journal of Environmental Management, 2024)

Characterization of emetic Bacillus cereus biofilm formation and cereulide production in biofilm - Fanchong Ren; Yuhang Chen; Shuo Yang; Yinan Zhang; Yangtai Liu; Yue Ma; Yating Wang; Yang Liu; Qingli Dong; Dasheng Lu (Food Research International, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Visible light-responsive vitamin B2 functionalized ZnO with dual-mechanism bactericidal effects for perishable agrofood preservation - Jianxing Feng; Zhenqing Guo; Runli Li; Chaoqun Zhang; Ting Du; Xiang Li; Xuewei Yang; Junchen Zhuo; Yanmin Liang; Yaru Han; Jianlong Wang; Shuo Shi; et al. (Chemical Engineering Journal, 2024)

One-step rapid removal of Cu(II) complexes via dual-active-site MOF catalysis with Peroxymonosulfate: Cooperative oxidation and adsorption - Shuo Wang; Simeng Guo; Xuedong Du; Ziqian Liu; Yujia Yang; Yaran Song; Qingrui Zhang (Chemical Engineering Journal, 2024)

Bifunctional halloysite nanotube-based Ripk1 siRNA delivery system rescues cognitive impairment by targeting amyloid β plaques for clearance and reducing necrotic neurons in Alzheimer’s disease mice - Linmei Wu; Shuo Tan; Yizhu Yan; Lianghao Zhu; Zhaoyuan Wu; Zhihong Liu; Qiang Cheng; Qiuhao Qu; Xinyu Li; Qi Zhang; Jiayi Liu; Jun Chang; et al. (Chemical Engineering Journal, 2024)

Monodispersed Au nanoparticles decorated MoS2 nanosheets with enhanced peroxidase-like activity based electrochemical H2O2 sensing for anticancer drug evaluations - Qiwen Liu; Yang Huang; Sheng Wang; Shuo Yang; Zhengjin Jiang; Shengfeng Huang (Analytica Chimica Acta, 2024)

Viscous-dependent fingering dynamics of gas invading into multi-fluids - Shuo Yang; Hongxia Li; Si Suo; Zan Wu (Advances in Water Resources, 2024)

Toxicokinetics of α- and β-amanitin in mice following single and combined administrations: Simulating in vivo amatoxins processes in clinical cases - Shuo Yang; Xin Wang; Fenshuang Zheng; Lina Pei; Jinting Liu; Bin Di; Yan Shi (Toxicon, 2024)

Water scarcity footprint and water saving potential for large-scale green hydrogen generation: Evidence from coal-to-hydrogen substitution in China - Lifeng Du; Yanmei Yang; Xue Bai; Shuo Xu; Ling Lin; Min Liu (Science of The Total Environment, 2024)

Inhibitory effects of Lactobacillus brevis on Aspergillus westerdijkiae and antifungal compounds identification - Li Li; Bolei Yang; Shuo Yang; Xiaoyu Tian; Yuan Gao; Jun Song; Wang Haifeng; Tiejun Li; Fuguo Xing (Postharvest Biology and Technology, 2024)

Automatic detection of urban flood level with YOLOv8 using flooded vehicle dataset - Jiaquan Wan; Youwei Qin; Yufang Shen; Tao Yang; Xu Yan; Shuo Zhang; Guang Yang; Fengchang Xue; Quan J. Wang (Journal of Hydrology, 2024)

Catalytic methane decomposition on CNT-supported Fe-catalysts - Miao Yang; Jan Baeyens; Shuo Li; Zehao Li; Huili Zhang (Journal of Environmental Management, 2024)

Microfluidic-oriented green synthesis of pepsin-doped gold nanoparticles for colorimetric and photothermal dual-readout detection of food hazards - Fuyuan Zhang; Yamei Li; Seid Mahdi Jafari; Yang Liu; Yaxin Sang; Shuo Wang; Xianghong Wang (Food Chemistry, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

Addition of lactic acid bacteria modulates microbial community and promotes the flavor profiles of Kombucha - Shuo Wang; Chuanwei Li; Qiangshen Xu; Ying Wang; Shuai Wang; Yongping Zou; Zhenquan Yang; Lei Yuan (Food Bioscience, 2024)

Disorders of the small intestinal microenvironment in ovalbumin-sensitized mice and mitigation strategies of 2′-fucosyllactose and Bifidobacterium longum subsp. Infantis - Wenhui Fu; Ruixin Kou; Huan Lv; Jin Wang; Qiang Xie; Dongze Qin; Bowei Zhang; Huan Rao; Yang Tian; Shuo Wang (Food Bioscience, 2024)

Ubiquitous nanocolloids suppress the conjugative transfer of plasmid-mediated antibiotic resistance in aqueous environment - Caixia Jin; Shuo Yang; Haiwen Ma; Xingli Zhang; Kai Zhang; Wei Zou (Environmental Pollution, 2024)

Concentration polarizations of PEG and silica colloids in ceramic nanofiltration - Shuo Zhang; Yaxin Liang; Cai Yang; Paul Venema; Luuk C. Rietveld; Sebastiaan G.J. Heijman (Desalination, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

Horizon-assisted lithologic modeling: understanding Mississippi Embayment and Coastal Lowlands aquifer systems in Louisiana and southwestern Mississippi, USA - Shuo Yang; Frank T-C Tsai; Lance D. Yarbrough (Hydrogeology Journal, 2024)

Positive feedback between the negative phase of interannual component of the Pacific Decadal Oscillation and La Niña - Hong-Shuo Tang; Yu Zhang; Yu Kosaka; Jun-Chao Yang; Qi Shu; Yi Liu; Xiaopei Lin (Climate Dynamics, 2024)

Effects of miR-204-5p and Target Gene EphB2 on Cognitive Impairment Induced by Aluminum Exposure in Rats - Wei Liu; Jie Gao; Niping Hao; Jing Li; Jing Pei; Danfeng Zou; Shuo Yang; Yuhua Yin; Xiaoming Yang; Ping Mu; Lifeng Zhang (Biological Trace Element Research, 2024)

The Role of Histone H2B Acetylation Modification in Aluminum-Induced Cognitive Dysfunction - Jie Gao; Wei Liu; Jing Pei; Jing Li; Niping Hao; Shuo Yang; Xiaoming Yang; Danfeng Zou; Kebin Xu; Lifeng Zhang (Biological Trace Element Research, 2024)

Folic acid capping Bi3+-doped Ag quantum dots for enzyme-like dual-mode recognition of toxic S2− and visual sensing of NO2− - Jing Feng; Lei Feng; Shuo Sun; Xujie Wang; Huitian Zhi; Ruhui Shang; Yingchao Yang; Luyao Wang; Zhengquan Yan; Lei Hu (Analytica Chimica Acta, 2024)

Optimization of recirculating water scallop larval cultivation system based on EDEM-fluent coupling - Xiuchen Li; Yu Yang; Dongshuo Liu; Shuo Chen; Shuqiao Wu; Xiang Yuan; Zibo Liu; Yubao Wang; Hanbing Zhang (Frontiers in Marine Science, 2024)
This article aims to address the issues of low cultivation density and high labor intensity of manual water exchange in existing scallop seedling ponds, an upwelling recirculating water system for scallop larval cultivation is designed. EDEM-Fluent coupled model was used to simulate the movement of scallop larvae in the culture cone in order to guarantee the uniform distribution of larvae in the cultivation device. Design-Expert software was utilized to investigate the impact of the bottom cone angle( θ ), the column height/cone height ratio( n ) and the inflow velocity( v ) on the variation coefficients of the axial and radial distributions of D-shaped larvae within the culture cone. The results indicated that θ = 108.97° and n = 1.8 represent the ideal structural parameters for the culture cone. The further investigation of the culture cones prototype was conducted to examine the impact of the inlet deflector angle ( α ), cultivation density ( τ ), and inflow velocity ( v ) on its performance. θ =108.97°, n =1.8, v =0.19m/s, α =60.94°, and τ=110pcs/ml were found to be the ideal combination of parameters, in this scenario, the D-shaped larvae’s radial distributions’ coefficients of variation is 22.13%, the error between the experimental and simulation results is 4.41%. Research has shown that EDEM-Fluent based simulation analysis methods can be used for the design and parameter optimization of upwelling recirculating water scallop larval cultivation system, this paper can provide a reference for the design of an upwelling recirculating water scallop larval cultivation system.

FSDNET: A features spreading net with density for 3D segmentation in agriculture - Qinghe Liu; Huijun Yang; Junjie Wei; Yuxuan Zhang; Shuo Yang (Computers and Electronics in Agriculture, 2024)

Arbuscular mycorrhizal fungi reduce soil N2O emissions by altering root traits and soil denitrifier community composition - Tangqing He; Wei Lin; Shuo Yang; Jiaqi Du; Bhoopander Giri; Cheng Feng; Frank S. Gilliam; Fuliang Zhang; Xiaoquan Zhang; Xuelin Zhang (Science of The Total Environment, 2024)

Honokiol and magnolol: A review of structure-activity relationships of their derivatives - Si-Yang Dai; Wen-Xiu Qin; Shuo Yu; Chang Li; Yi-Hui Yang; Yue-Hu Pei (Phytochemistry, 2024)

Examining multiscale built environment interventions to mitigate travel-related carbon emissions - Shuo Yang; Leyu Zhou; Chang Liu; Shan Sun; Liang Guo; Xiaoli Sun (Journal of Transport Geography, 2024)

Correlations between bone metabolism biomarkers and fluoride exposure in adults and children - Shuo Yang; Shuiyuan Yu; Yuhui Du; Zichen Feng; Xuecheng Jiao; Qinyang Li; Jingjing Wu; Lei Sun; Juan Zuo; Xiaoli Fu; Zhiyuan Li; Hui Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Associations of incident female breast cancer with long-term exposure to PM2.5 and its constituents: Findings from a prospective cohort study in Beijing, China - Yutong Song; Lei Yang; Ning Kang; Ning Wang; Xi Zhang; Shuo Liu; Huichao Li; Tao Xue; Jiafu Ji (Journal of Hazardous Materials, 2024)

Salt distribution and alkalinity characterization in bauxite residue disposal areas from the spatial scale range - Fan Yang; Xiaoqiang Dong; Wei Duan; Shuo Zhang; Wenwen Cui (Journal of Cleaner Production, 2024)

Divergent impacts of fertilization regimes on below-ground prokaryotic and eukaryotic communities in the Tibetan Plateau - Shuo Sun; Chen Liu; Yun Zhang; Yang Yue; Shiqi Sun; Yang Bai; Pengfei Zhang; Mohammadhossein Ravanbakhsh; Francisco Dini-Andreote; Rong Li; Zhenhua Zhang; Alexandre Jousset; et al. (Journal of Environmental Management, 2024)

Predicting post-fire forest recovery using the 3-PG model with bi-temporal Landsat imagery in high-severity burned areas of Great Xing’an Mountain - Simei Lin; Linyuan Li; Shangbo Liu; Shuo Yang; Danyang Lin; Xun Zhao; Ling Chen; Huaguo Huang (Forest Ecology and Management, 2024)

Enhanced antibacterial activity of bovine milk exosome-based drug formulation against bacterial pathogens - Qingjun Xu; Shuo Yang; Kai Zhang; Ying Liu; Lin Li; Shaoqi Qu (Food Chemistry, 2024)

Microfluidic paper-based analysis device applying black phosphorus nanosheets@MWCNTs-COOH: A portable and efficient strategy for detection of β-Lactoglobulin in dairy products - Xintong Han; Dan Zhang; Mengjiao Xie; Jingying Yang; Yueyao Wang; Huilin Li; Shuo Wang; Mingfei Pan (Food Chemistry, 2024)

Bimetallic Ag/Au nanoclusters encapsulated in ZIF-8 framework: A novel strategy for ratiometric fluorescence detection of doxycycline in food - Yueyao Wang; Mengmeng Gao; Jingying Yang; Huilin Li; Xintong Han; Shuo Wang; Mingfei Pan (Food Chemistry, 2024)

Waste to wealth: Efficient wet desulfurization of electric arc furnace dust (EAFD) and recycling of desulfurization solid residue - Jiayu Feng; Jintao Yang; Shuo Cui; Kaiqiang Hu; Fang Wang; Ping Ning; Lijuan Jia (Chemical Engineering Journal, 2024)

High-density mapping of durable and broad-spectrum stripe rust resistance gene Yr30 in wheat - Xiaoting Wang; Mingjie Xiang; Huaizhou Li; Xiaoxiao Li; Keqing Mu; Shuo Huang; Yibo Zhang; Xiangrui Cheng; Shuqing Yang; Xunying Yuan; Ravi P. Singh; Sridhar Bhavani; et al. (Theoretical and Applied Genetics, 2024)

Evolutionary genomics of climatic adaptation and resilience to climate change in alfalfa - Fan Zhang; Ruicai Long; Zhiyao Ma; Hua Xiao; Xiaodong Xu; Zhongjie Liu; Chunxue Wei; Yiwen Wang; Yanling Peng; Xuanwen Yang; Xiaoya Shi; Shuo Cao; et al. (Molecular Plant, 2024)

Why choose active travel over driving? Investigating the impact of the streetscape and land use on active travel in short journeys - Hui He; Leyu Zhou; Shuo Yang; Liang Guo (Journal of Transport Geography, 2024)

Examining the correlation of household electric vehicle ownership: Insights for emerging mobility and planning - Shuo Yang; Leyu Zhou; Zhehao Zhang; Shan Sun; Liang Guo (Journal of Transport Geography, 2024)

Complex unstructured-grid groundwater modeling using centroidal Voronoi tessellation refinement and curve fitting - Aya B.A. Mohamed; Shuo Yang; Ye-Hong Chen; Frank T.-C. Tsai; Alyssa Dausman (Journal of Hydrology, 2024)

Utilizing in situ construction of N-doped hierarchical porous carbon to achieve electronic control of highly dispersed Pd nanoparticles for efficient catalytic hydrogenation of CO2 to formic acid - Yan Wang; Anjie Yang; Yuantong Liu; Mengqin Yao; Fei Liu; Jun Ma; Shuo Geng (Journal of Environmental Chemical Engineering, 2024)

A cleaner-sustainable process for recovering valuable elements from steel slag with acetic acid: Leaching studies and multi-value-added products - Mingyuan Yang; Shuo Zhang; Yelei Wang; Zilong Li; Juan Wen; Xuejun Quan; Cunfang Lu (Journal of Environmental Chemical Engineering, 2024)

Enzyme-free intelligent films in electrochemistry of malathion with a binary architecture: Combined Cu2+ complexed carbon nitride nanosheets and poly(N,N-dimethylacrylamide) hydrogels - Xinyu Wang; Jiping Han; Ke Zhang; Ying Liu; Changyi Yang; Keren Shi; Lingchen Meng; Shuo Gu; Huiqin Yao (Journal of Environmental Chemical Engineering, 2024)

Synthesis of stable mesoporous Zr-MOFs using pyrazine-containing ligand for efficient capture of Pb(II) in wastewater - Lixiang Liu; Laidi Wu; Yue Chen; Yongfei Ma; Li Lin; Shuo Li; Xiujuan Yang; Hui Chen; Guojian Duan (Journal of Environmental Chemical Engineering, 2024)

Drying stress analysis and cracking prediction of the component of maize based on viscoelastic stress-strain model - Zhaohui Zheng; Liuyang Ren; Weijun Xie; Shuo Wei; Hanyu Fu; Pei Yang; Jingshen Xu; Deyong Yang (Innovative Food Science & Emerging Technologies, 2024)

Predicting soil organic carbon content using simulated insitu spectra and moisture correction algorithms in southern Xinjiang, China - Peimin Yang; Yu Wang; Bifeng Hu; Shuo Li; Songchao Chen; Defang Luo; Jie Peng (Geoderma Regional, 2024)

Insights into benzopyrene formation mechanism in flames: A density functional theory study - Zehong Li; Wei Zhang; Shuo Ning; Zhaohui Chen; Quanchang Zhang; Zhenzhu Ma; Xili Yang; Jincong Ou (Fuel, 2024)

Testing adulterated liquid-egg: developing rapid detection techniques based on colorimetry, electrochemistry, and interfacial fingerprinting - Shuo Yang; Fuming Yang; Wenhao Dou; Yuan Chi; Yujie Chi (Food Chemistry, 2024)

Carbon-dots encapsulated luminescent metal–organic frameworks@surface molecularly imprinted polymer: A facile fluorescent probe for the determination of chloramphenicol - Mingfei Pan; Jiaqing Sun; Yixin Wang; Jingying Yang; Zhijuan Wang; Lin Li; Shuo Wang (Food Chemistry, 2024)

Flash spinning polyethylene/Fe3O4 magnetic drive fibers for oil absorption underwater - Dengkun Shu; Xingyu Long; Pengju Zhao; Lang Wang; Zhenhua Li; Chunzu Cheng; Shuo Yang; Long Jiao; Peng Xi; Lei Xia; Chenyang Li; Bowen Cheng (Chemical Engineering Journal, 2024)

Preparation of an injectable and photocurable carboxymethyl cellulose/hydroxyapatite composite and its application in cranial regeneration - He Qiu; Jing Wang; Hong Hu; Lu Song; Zhanhong Liu; Yang Xu; Shuo Liu; Xiangdong Zhu; Hang Wang; Chongyun Bao; Hai Lin (Carbohydrate Polymers, 2024)

Effects of Rhizosphere Microorganisms Associated with Suaeda Salsa on the Growth and Salt Stress Resistance of Alfalfa - Jinxia Chen; Qian Zhang; Xihu Qie; Yajuan Che; Dantong Lv; Yuxuan Gao; Fuhong Miao; Shuo Li; Feng He; Juan Sun; Chao Yang (Journal of Soil Science and Plant Nutrition, 2024)

Amlodipine inhibits Synaptotagmin-4’s oncogenic activity on gastric cancer proliferation by targeting calcium signaling - Wen Huang; Shuo Yang; Minying Deng; Rongkui Luo; Huaiyu Liang; Yanyan Shen; Biyu Yang; Chen Xu; Yingyong Hou (Functional & Integrative Genomics, 2024)
Background: Gastric cancer (GC) remains a leading cause of cancer mortality globally. Synaptotagmin-4 (SYT4), a calcium-sensing synaptic vesicle protein, has been implicated in the oncogenesis of diverse malignancies. Purpose: This study delineates the role of SYT4 in modulating clinical outcomes and biological behaviors in GC. Methods: We evaluated SYT4 expression in GC specimens using bioinformatics analyses and immunohistochemistry. Functional assays included CCK8 proliferation tests, apoptosis assays via flow cytometry, confocal calcium imaging, and xenograft models. Western blotting elucidated MAPK pathway involvement. Additionally, we investigated the impact of the calcium channel blocker amlodipine on cellular dynamics and MAPK pathway activity. Results: SYT4 was higher in GC tissues, and the elevated SYT4 was significantly correlated with adverse prognosis. Both univariate and multivariate analyses confirmed SYT4 as an independent prognostic indicator for GC. Functionally, SYT4 promoted tumorigenesis by fostering cellular proliferation, inhibiting apoptosis, and enhancing intracellular Ca 2+ influx, predominantly via MAPK pathway activation. Amlodipine pre-treatment attenuated SYT4-driven cell growth and potentiated apoptosis, corroborated by in vivo xenograft assessments. These effects were attributed to MAPK pathway suppression by amlodipine. Conclusion: SYT4 emerges as a potential prognostic biomarker and a pro-oncogenic mediator in GC through a Ca 2+ -dependent MAPK mechanism. Amlodipine demonstrates significant antitumor effects against SYT4-driven GC, positing its therapeutic promise. This study underscores the imperative of targeting calcium signaling in GC treatment strategies.

Relating extreme precipitation events to atmospheric conditions and driving variables in China - Qianxi Ou; Tongtiegang Zhao; Shuo Wang; Yang Liu; Yongyan Wu; Bo Li; Xiaohong Chen (Climate Dynamics, 2024)

Numerical investigation on flow and heat transfer characteristics of a PCHE with liquid lead–bismuth eutectic and sCO2 as working fluids - Hong Liu; Zhigang Zhang; Shuo Yang; Guangliang Chen; Tenglong Cong; Haisu Du (Annals of Nuclear Energy, 2024)

Plasmon AgNPs/MoS2/ZnO nanorods array ternary heterojunctions enabling high-efficiency solar-light energy utilization for photocatalysis and recyclable SERS detection - Jingying Yang; Sixuan Chen; Mingfei Pan; Yumei Ding; Shuo Wang (Analytica Chimica Acta, 2024)

Competitive mechanism of salt-tolerance/degradation-performance of organic pollutant in bacteria: Na+/H+ antiporters contribute to salt-stress resistance but impact phenol degradation - Shenmei Sun; Shuo Wang; Yalin Yin; Yue Yang; Yijia Wang; Jingjing Zhang; Wei Wang (Water Research, 2024)

Neddylation inhibition affects early embryonic development by disrupting maternal-to-zygotic transition and mitochondrial function in mice - Mingxiao Liu; Zhiming Ding; Peihao Sun; Shuo Zhou; Hanxiao Wu; Lijun Huo; Liguo Yang; John S. Davis; Aixin Liang (Theriogenology, 2024)

Government digital transformation, resource curse and green total factor energy efficiency in Chinese cities - Fan Bie; Luyao Zhou; Shuo Liu; Tao Yang (Resources Policy, 2024)

Dynamic response and performance assessment of subsea sandwich pipelines with different interlayer subjected to underwater explosion - Hong Lin; Hao Xu; Lei Yang; Pingping Han; Shuo Zhang; Longcheng Wei; Guoming Chen (Process Safety and Environmental Protection, 2024)

Numerical simulation analysis of stable flow of hydrate slurry in gas-liquid-solid multiphase flow - Xiao-Fang Lv; Kai-Yue Xu; Yang Liu; Chuan-Shuo Wang; Ming-Guo Peng; Hui Du; Shuang-Cindy Cao; Qian-Li Ma; Shi-dong Zhou; Shang-Fei Song (Ocean Engineering, 2024)

A CFD-FEA coupled model for simulating dynamic response of offshore jacket platform under earthquake considering wind, wave, current and aftershock loads - Hong Lin; Haochen Luan; Alexander Moiseevish Uzdin; Shuo Zhang; Longcheng Wei; Lei Yang (Ocean Engineering, 2024)

The nonlinear influence of land conveyance on urban carbon emissions: An interpretable ensemble learning-based approach - Renlu Qiao; Zhiqiang Wu; Qingrui Jiang; Xiaochang Liu; Shuo Gao; Li Xia; Tianren Yang (Land Use Policy, 2024)

Effects of apple fiber on the physicochemical properties and baking quality of frozen dough during frozen storage - Shuo Yang; Xiujie Zhao; Tongxun Liu; Yongjian Cai; Xinlun Deng; Mouming Zhao; Qiangzhong Zhao (Food Chemistry, 2024)

Study on carbon footprint evaluation and carbon reduction path of cross-basin water transfer project – A case study of the Yellow River East diversion project in China - Yujie Zhang; Qingsong Wang; Jiong Zhang; Yue Xu; Shu Tian; Shuo Yang; Yuan Xu; Huibin Zhang; Xueliang Yuan; Qiao Ma; Chengqing Liu; Ziyang Li; et al. (Environmental Impact Assessment Review, 2024)

Surface Alloyed-Zn promotes stability of Cu-Au catalysts toward electrochemical CO2 reduction reaction - Yanyan Jia; Yiming Ma; Wei-En Yang; Yuankai Zhu; Xinyu Zhang; Shuo Xie; Ting-Wei Kuo; Sheng Dai; Kuan-Wen Wang (Chemical Engineering Journal, 2024)

Low-frequency Stimulation at the Subiculum Prevents Extensive Secondary Epileptogenesis in Temporal Lobe Epilepsy - Yujia Shen; Yiwei Gong; Xiaoli Da; Shajing Gao; Shuo Zhang; Minjuan Sun; Yuanzhi Yang; Xiaoyun Qiu; Menghan Li; Yang Zheng; Fan Fei; Yi Wang; et al. (Neuroscience Bulletin, 2024)

An Hsp70 promoter–based mouse for heat shock–induced gene modulation - Hangang Chen; Yangli Xie; Mei Zhang; Junlan Huang; Wanling Jiang; Ruobin Zhang; Can Li; Xiaolan Du; Hua Chen; Qiang Nie; Sen Liang; Qiaoyan Tan; et al. (Journal of Molecular Medicine, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Heterogeneous electric vehicle market resilience and underlying contributors: Evidence from China - Shuo Yang; Wen Wen; Peng Zhou (Transportation Research Part D: Transport and Environment, 2024)

Mixed plantations with N-fixing tree species maintain ecosystem C:N:P stoichiometry: Implication for sustainable production - Xianyu Yao; Dafeng Hui; Shuo Xing; Qianchun Zhang; Jingwen Chen; Zihua Li; Yang Xu; Qi Deng (Soil Biology and Biochemistry, 2024)

Exploring the contributions of Ebike ownership, transit access, and the built environment to car ownership in a developing city - Shan Sun; Liang Guo; Shuo Yang; Jason Cao (Journal of Transport Geography, 2024)

Integration of bimetallic CuCo into N-doping SiC hollow nanoreactor for pollutant removal coupled solar-driven cleanwater regeneration - Rongrong Du; Hongyang Zhu; Shuo Wang; Hongyao Zhao; Mengting Liu; Yanyun Wang; Yiyan Song; Fu Yang (Journal of Environmental Chemical Engineering, 2024)

Ascertaining sensitive exposure biomarkers of various metal(loid)s to embryo implantation - Mengyuan Ren; Tianxiang Wu; Shuo Yang; Ning Gao; Changxin Lan; Han Zhang; Weinan Lin; Shu Su; Lailai Yan; Lili Zhuang; Qun Lu; Jia Xu; et al. (Environmental Pollution, 2024)

Factors influencing the intensity of cross-front transport: An example from the offshore transport around the Shandong Peninsula, China - Xiaomei Xu; Yong Shi; Charlie Thompson; Jixuan Lyu; Shuo Zhang; Shengjing Liu; Guang Yang; Tao Liu; Jianhua Gao (Continental Shelf Research, 2024)

High energy storage performance of (1-x)Ba0.5Sr0.5TiO3-xK0.5Na0.5NbO3 ceramics via a combined strategy of fine grains and multiphase polar nanoregions - Jielin Zha; Jiaxun Liu; Yulong Yang; Xiaomei Lu; Xueli Hu; Shuo Yan; Zijing Wu; Min Zhou; Fengzhen Huang; Xuenong Ying; Jinsong Zhu (Chemical Engineering Journal, 2024)

In-situ electron capture by surface Co-Ci to facilitate the solar water splitting of Fe2O3 - Chang Li; Cheng Lu; Ye Zhu; Shuo Li; Yong Feng; Yiliu Yang; Bai Xu; Kun Feng; Jun Zhong (Chemical Engineering Journal, 2024)

Solid waste-derived solar desalination devices: Enhanced efficiency in water vapor generation and diffusion - Jiahui Yu; Chenxi Wang; Shu Liu; Shuo Yang; Xingmin Du; Shuai Liu; Changxiang Shao; Huijun Kong; Baolei Wang; Tao Wu; Chenwei Li (Chemical Engineering Journal, 2024)

Regulating framework aluminum location towards boosted light olefins generation in ex-situ catalytic pyrolysis of low-density polyethylene - Ting Wang; Xiang Feng; Dong Lin; Yan Li; Jingyuan Shang; Jinqing Zhang; Shuo Li; Yibin Liu; Hui Zhao; Zhe Ma; Xiaobo Chen; Xingong Zhang; et al. (Chemical Engineering Journal, 2024)

Exploring the mechanism of clomiphene citrate to improve ovulation disorder in PCOS rats based on follicular fluid metabolomics - Yiqing He; Xi Wang; Quan Liu; Huiping Liu; Shuo Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Erratum to: Molecular dynamics simulation reveals DNA-specific recognition mechanism via c-Myb in pseudo-palindromic consensus of mim-1 promoter - Jinru Weng; Shuo Yang; Jinkang Shen; Hongsen Liu; Yuzi Xu; Dongyun Hao; Shan Wang (Journal of Zhejiang University-SCIENCE B, 2024)

Semaphorin 3 a restores the ability of type 1 regulatory T cells to suppress food allergy - Panpan Gao; Shuo Song; Yanan Wang; Huazhen Liu; Xiangyu Wang; Qing shu; Pingchang Yang; Pengyuan Zheng (Immunologic Research, 2024)

Genome-wide identification and quantification of salinity-responsive Na+/K+-ATPase α-subunits in three salmonids - Yue Su; Shuang-En Yu; Yong-Xu Sun; Liang Zhang; Yue Tan; Yu-Yang Zhang; Shuo Wang; Yan-Gen Zhou; Li-Sha Hu; Yun-Wei Dong (Aquaculture, 2024)

Individual and synergistic associations among transit allowance, land use, and transit commuting - Shan Sun; Shuo Yang; Liang Guo; Xinyu (Jason) Cao (Transportation Research Part D: Transport and Environment, 2024)

Carbon capture and utilization by algae with high concentration CO2 or bicarbonate as carbon source - Yi Yang; Shuo Tang; J. Paul Chen (Science of The Total Environment, 2024)

Construction of novel tandem reaction system coupling H2O2 production with in situ bleaching over Au/TiO2 photocatalyst with different metal-support interactions - Hexin Zhou; Bing Li; Jun Liu; Wenxiu Yang; Wei Wang; Xuemin Hu; Shuo Wang (Process Safety and Environmental Protection, 2024)

Shift in the quantitative relationship between sedimentary records and catchment floods influenced by dam construction - Shengjing Liu; Hui Sheng; Tao Liu; Zhenyu Zhang; Zhimin Zhang; Yong Shi; Shuo Zhang; Xiaomei Xu; Jixuan Lyu; Guang Yang; Zhengjin Tao; Jianhua Gao (Journal of Hydrology, 2024)

Enhanced detection of acrylamide using a versatile solid-state upconversion sensor through spectral and visual analysis - Yawen Rong; Md Mehedi Hassan; Jizhong Wu; Shuo Chen; Wancheng Yang; Yunhao Li; Jiaji Zhu; Jun Huang; Quansheng Chen (Journal of Hazardous Materials, 2024)

Whole blood cadmium levels and depressive symptoms in Chinese young adults: A prospective cohort study combing metabolomics - Liu Yang; Qingxia Yu; Siqi Dou; Xinyuan Li; Shuo Wen; Jia Zhang; Mingyu Feng; Lailai Yan; Chengshuai Zhang; Shanshan Li; Peng Lu; Yuming Guo (Journal of Hazardous Materials, 2024)

A case study for efficient magma mixing: Constraints from early Paleozoic high Ba–Sr granitoids in the North Qinling Orogen, Central China - Leran Hao; Debin Yang; Wenliang Xu; Anqi Wang; Yikang Quan; Xiangyu Yan; Shuo Wang; Feng Wang (Journal of Asian Earth Sciences, 2024)

Partial organic substitution for synthetic fertilizer improves soil fertility and crop yields while mitigating N2O emissions in wheat-maize rotation system - Gong Wu; Shuo Yang; Chong-sheng Luan; Qi Wu; Lei-li Lin; Xiao-xiao Li; Zhao Che; De-bao Zhou; Zhao-rong Dong; He Song (European Journal of Agronomy, 2024)

Accelerating the generation of NiOOH by in-situ surface phosphating nickel sulfide for promoting the proton-coupled electron transfer kinetics of urea electrolysis - Xin Guo; Longyu Qiu; Menggang Li; Fenyang Tian; Xue Ren; Sheng Jie; Shuo Geng; Guanghui Han; Yarong Huang; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2024)

A radionuclide-labeled nanomedicine for STING pathway activation- and oxygenation-augmented orthotopic cancer radioisotope-immunotherapy - Zhisheng Luo; Ming Zhou; Ying Peng; Lu Hao; Jinhui Yang; Peng Liu; Shuo Hu (Chemical Engineering Journal, 2024)

Thermally managed and fireproof composite aerogels for safer and year-round energy saving - Wei Cai; Zhaoxin Li; Heng Xie; Wei Wang; Tianyang Cui; Bicheng Lin; Liangyuan Qi; Xin Hu; Yu Du; Yang Ming; Shuo Shi; Daming Chen; et al. (Chemical Engineering Journal, 2024)

Circ DENND4C inhibits pyroptosis and alleviates ischemia-reperfusion acute kidney injury by exosomes secreted from human urine-derived stem cells - Boxin Yang; Junxiong Wang; Jiao Qiao; Qian Zhang; Qi Liu; Yuan Tan; Qingchen Wang; Wenyuan Sun; Weimin Feng; Zhongxin Li; Chong Wang; Shuo Yang; et al. (Chemico-Biological Interactions, 2024)

An innovative fluorescent probe based on dicyanoisoflurone derivatives for differential detection of Hg2+ and Cu2+ and its applications in bacteria, cell imaging and food analysis - Yixuan Yao; Jinli Ma; Shuo Xing; Fudong Zeng; Liangqiang Wu; Yapeng Li; Jianshi Du; Qingbiao Yang; Yaoxian Li (Analytica Chimica Acta, 2024)

Use of ChatGPT on Taiwan’s Examination for Medical Doctors - Yung-Shuo Kao; Wei-Kai Chuang; Jen Yang (Annals of Biomedical Engineering, 2024)

Aircraft Observation and Simulation of the Supercooled Liquid Water Layer in a Warm Conveyor Belt over North China - Jiefan Yang; Fei Yan; Hengchi Lei; Shuo Jia; Xiaobo Dong; Xiangfeng Hu (Advances in Atmospheric Sciences, 2024)

Studies on the transfer effect of aged polyethylene microplastics in soil-plant system - Shuo Yang; Ying Zhang; Yi Chen; Yuping Zeng; Xinyao Yan; Xiao Tang; Shengyan Pu (Chemosphere, 2024)

DNA methylation reprogramming mediates transgenerational diabetogenic effect induced by early-life p,p’-DDE exposure - Shuo Wang; Jingjing Wu; Zhong Chen; Wei Wu; Liping Lu; Yuzhou Cheng; Shuqi Li; Liangjing Chen; Xiaohua Tan; Lei Yang; Charles Wang; Yang Song (Chemosphere, 2024)

Effects of torrefaction pretreatment on fuel quality and combustion characteristics of biomass: A review - Xu Yang; Zhong Zhao; Yaying Zhao; Li Xu; Shuo Feng; Zhuozhi Wang; Lei Zhang; Boxiong Shen (Fuel, 2024)

Determination of CF3CHFCF3 suppression effects on premixed hydrogen-methane deflagration via experiment and simulation - Hongfu Mi; Peng Shao; Nan Luo; Shuo Wang; Yang Wang; Xinsheng Jiang; Wenhe Wang; Yulong Duan; Chi-Min Shu (Fuel, 2024)

Carbon dots-based fluorescent molecularly imprinted photonic crystal hydrogel strip: Portable and efficient strategy for selective detection of tetracycline in foods of animal origin - Mingfei Pan; Yueyao Wang; Jingying Yang; Huilin Li; Xintong Han; Shuo Wang (Food Chemistry, 2024)

Magnetic-fluorescent immunosensing platform applying AuNPs heterogeneous MIL-53(Al) composite for efficient detection of zearalenone - Huilin Li; Jingying Yang; Ran Han; Yueyao Wang; Xintong Han; Shuo Wang; Mingfei Pan (Food Chemistry, 2024)

Restricted colloidal-bound phosphorus release controlled by alternating flooding and drying cycles in an alkaline calcareous soil - Shuai Ding; Shuai Zhang; Yang Wang; Shuo Chen; Qing Chen (Environmental Pollution, 2024)

A stiff and tough triple-shape memory hydrogel triggered at body temperature by hydrophobic association and electrostatic interaction - Lei Yang; Shuo Li; Zijian Zhao; Jie Wang; Xiaoniu Yang; Hongying Lv (Chemical Engineering Journal, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Unveiling the mechanism of electrocatalytic oxidation of glycerol by in-situ electrochemical spectroscopy - Lixiong Xu; Yifan Yang; Chenyue Li; Rongqian Ning; Jun Ma; Mengqin Yao; Shuo Geng; Fei Liu (Chemical Engineering Journal, 2024)

OsMKK1 is a novel element that positively regulates the Xa21-mediated resistance response to Xanthomonas oryzae pv. oryzae in rice - ZeXi Yang; Zheng Zhu; Yalu Guo; Jinping Lan; Jianshuo Zhang; Shuo Chen; Shijuan Dou; Ming Yang; Liyun Li; Guozhen Liu (Plant Cell Reports, 2024)

A prognostic marker LTBP1 is associated with epithelial mesenchymal transition and can promote the progression of gastric cancer - Xinju Jiang; Shengjie Yin; Xin Yin; Yufei Wang; Tianyi Fang; Shuo Yang; Xiulan Bian; Guoli Li; Yingwei Xue; Lei Zhang (Functional & Integrative Genomics, 2024)

Prolonged Exposure to Plant Volatiles does not Significantly Affect Pban Expression and Mating Behavior in Diamondback Moth [Plutella Xylostella (Lepidoptera: Plutellidae)] - Houjun Tian; Ruibin Xu; Heng Li; Shuo Lin; Yixin Chen; Yong Chen; Guang Yang; Hui Wei (Journal of Chemical Ecology, 2024)

Multi-enzymatic systems synergize new RCA technique amplified super-long dsDNA from DNA circle - Qiang Zhou; Xianlong Ding; Wanqing Du; Hongjie Wang; Shuo Wu; Jun Li; Shouping Yang (Analytica Chimica Acta, 2024)

Species pool, local assembly processes: Disentangling the mechanisms determining bacterial α‐ and β‐diversity during forest secondary succession - Xiao Zhang; Handan Dai; Yongtao Huang; Kuan Liu; Xingang Li; Shuoxin Zhang; Shenglei Fu; Shuo Jiao; Chunbo Chen; Biao Dong; Zhu Yang; Yang Cui; et al. (Molecular Ecology, 2024)
Across ecology, and particularly within microbial ecology, there is limited understanding how the generation and maintenance of diversity. Although recent work has shown that both local assembly processes and species pools are important in structuring microbial communities, the relative contributions of these mechanisms remain an important question. Moreover, the roles of local assembly processes and species pools are drastically different when explicitly considering the potential for saturation or unsaturation, yet this issue is rarely addressed. Thus, we established a conceptual model that incorporated saturation theory into the microbiological domain to advance the understanding of mechanisms controlling soil bacterial diversity during forest secondary succession. Conceptual model hypotheses were tested by coupling soil bacterial diversity, local assembly processes and species pools using six different forest successional chronosequences distributed across multiple climate zones. Consistent with the unsaturated case proposed in our conceptual framework, we found that species pool consistently affected α‐diversity, even while local assembly processes on local richness operate. In contrast, the effects of species pool on β‐diversity disappeared once local assembly processes were taken into account, and changes in environmental conditions during secondary succession led to shifts in β‐diversity through mediation of the strength of heterogeneous selection. Overall, this study represents one of the first to demonstrate that most local bacterial communities might be unsaturated, where the effect of species pool on α‐diversity is robust to the consideration of multiple environmental influences, but β‐diversity is constrained by environmental selection.

Multiple spatial scales of bacterial and fungal structural and functional traits affect carbon mineralization - Zhiyuan Ma; Shuo Jiao; Kaikai Zheng; Haowei Ni; Dong Li; Na Zhang; Yunfeng Yang; Jizhong Zhou; Bo Sun; Yuting Liang (Molecular Ecology, 2024)
Studying the functional heterogeneity of soil microorganisms at different spatial scales and linking it to soil carbon mineralization is crucial for predicting the response of soil carbon stability to environmental changes and human disturbance. Here, a total of 429 soil samples were collected from typical paddy fields in China, and the bacterial and fungal communities as well as functional genes related to carbon mineralization in the soil were analysed using MiSeq sequencing and GeoChip gene microarray technology. We postulate that CO 2 emissions resulting from bacterial and fungal carbon mineralization are contingent upon their respective carbon consumption strategies, which rely on the regulation of interactions between biodiversity and functional genes. Our results showed that the spatial turnover of the fungal community was 2–4 times that of the bacterial community from hundreds of meters to thousands of kilometres. The effect of spatial scale exerted a greater impact on the composition rather than the functional characteristics of the microbial community. Furthermore, based on the establishment of functional networks at different spatial scales, we observed that both bacteria and fungi within the top 10 taxa associated with carbon mineralization exhibited a prevalence of generalist species at the regional scale. This study emphasizes the significance of spatial scaling patterns in soil bacterial and fungal carbon degradation functions, deepening our understanding of how the relationship between microbial decomposers and soil heterogeneity impacts carbon mineralization and subsequent greenhouse gas emissions.

Penicillium raperi causes rot disease on Morchella sextelata in Heilongjiang Province, China - Xi Xu; Chunbo Yang; Shuo Wang; Chenyang Jiao; Jingzheng Sun; Xiaoya Fan; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (Crop Protection, 2024)

Tigecycline-resistance mechanisms and biological characteristics of drug-resistant Salmonella Typhimurium strains in vitro - Lin Li; Longbo Wang; Shuo Yang; Yanfang Zhang; Yiming Gao; Qianyu Ji; Linran Fu; Qiling Wei; Feifei Sun; Shaoqi Qu (Veterinary Microbiology, 2024)

Additive manufacturing thermoplastic recycling: Profit-driven planning and optimization - Lei Di; Yiran Yang; Shuo Wang (Journal of Cleaner Production, 2024)

LED-driven photocatalytic degradation of tetracycline by chromite ore processing residue (COPR): Mechanism, pathway, toxicity assessment - Shuo Zhang; Cunfang Lu; Yelei Wang; Cheng Tian; Peng Chen; Mingyuan Yang; Min Zhang; Rui Xu; Yuanyuan He; Zilong Li (Journal of Cleaner Production, 2024)

Research progress on the construction of oxygen vacancy defects and application in photocatalytic oxidation of elemental mercury - Xin Yang; Zijian Xiang; Jiang Wu; Ping He; Yongfeng Qi; Shuo Chen; Yizheng Lu; Rui Xie; Zhengyu Liu; Chuman He (Fuel, 2024)

An in-situ blocking strategy for improved anti-interference inspection of AFB1 based on hollow covalent organic framework capsules with commodious and undisturbed microenvironment - Lu Yang; Jing Wang; Chun-Yang Li; Man-Man Wang; Jing-Min Liu; Shuo Wang (Food Chemistry, 2024)

“Fluorescence-wavelength” label-free POCT tandem with “fluorescence-photothermal” nanobody-immunosensor for detecting BSA and β-lactoglobulin - Shijie Li; Linqing Nie; Lu Yang; Dancai Fan; Junping Wang; Yaozhong Hu; Yan Zhang; Shuo Wang (Food Chemistry, 2024)

Porous polypyrrole Nanotube-Based Organohydrogels: Versatile materials for robust electromagnetic interference shielding in harsh environments - Lingsai Meng; Shuo Yang; Yu Ma; Yupeng Zou; Yang Zhang; Gang Chen; Chengjun Dong; Hongtao Guan (Chemical Engineering Journal, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Genetic diversity of RNA viruses infecting invertebrate pests of rice - Haoran Wang; Shufen Chao; Qing Yan; Shu Zhang; Guoqing Chen; Chonghui Mao; Yang Hu; Fengquan Yu; Shuo Wang; Liang Lv; Baojun Yang; Jiachun He; et al. (Science China Life Sciences, 2024)

Case Studies of the Microphysical and Kinematic Structure of Summer Mesoscale Precipitation Clouds over the Eastern Tibetan Plateau - Shuo Jia; Jiefan Yang; Hengchi Lei (Advances in Atmospheric Sciences, 2024)

The neglected roles of adjacent natural ecosystems in maintaining bacterial diversity in agroecosystems - Ziheng Peng; Yunfeng Yang; Yu Liu; Lianyan Bu; Jiejun Qi; Hang Gao; Shi Chen; Haibo Pan; Beibei Chen; Chunling Liang; Xiaomeng Li; Yining An; et al. (Global Change Biology, 2024)
A central aim of community ecology is to understand how local species diversity is shaped. Agricultural activities are reshaping and filtering soil biodiversity and communities; however, ecological processes that structure agricultural communities have often overlooked the role of the regional species pool, mainly owing to the lack of large datasets across several regions. Here, we conducted a soil survey of 941 plots of agricultural and adjacent natural ecosystems (e.g., forest, wetland, grassland, and desert) in 38 regions across diverse climatic and soil gradients to evaluate whether the regional species pool of soil microbes from adjacent natural ecosystems is important in shaping agricultural soil microbial diversity and completeness. Using a framework of multiscales community assembly, we revealed that the regional species pool was an important predictor of agricultural bacterial diversity and explained a unique variation that cannot be predicted by historical legacy, large‐scale environmental factors, and local community assembly processes. Moreover, the species pool effects were associated with microbial dormancy potential, where taxa with higher dormancy potential exhibited stronger species pool effects. Bacterial diversity in regions with higher agricultural intensity was more influenced by species pool effects than that in regions with low intensity, indicating that the maintenance of agricultural biodiversity in high‐intensity regions strongly depends on species present in the surrounding landscape. Models for community completeness indicated the positive effect of regional species pool, further implying the community unsaturation and increased potential in bacterial diversity of agricultural ecosystems. Overall, our study reveals the indubitable role of regional species pool from adjacent natural ecosystems in predicting bacterial diversity, which has useful implication for biodiversity management and conservation in agricultural systems.

Geographical, climatic, and soil factors control the altitudinal pattern of rhizosphere microbial diversity and its driving effect on root zone soil multifunctionality in mountain ecosystems - Yi Yang; Kaiyang Qiu; Yingzhong Xie; Xiaocong Li; Shuo Zhang; Wangsuo Liu; Yeyun Huang; Luyao Cui; Siyao Wang; Pingan Bao (Science of The Total Environment, 2023)

Numerical study on weakening vortex-induced vibration of semi-ring diversion type component - Aolin Gu; Weihong Peng; Zefeng Li; Chenhua Hu; Shuo Yang; Qiqi Zhang (Ocean Engineering, 2023)

Winter storms drive offshore transport and modulate phytoplankton blooms in Northern Taiwan, China - Tao Liu; Yong Shi; Xiaomei Xu; Shengjing Liu; Jixuan Lyu; Shuo Zhang; Guang Yang; Chunyu Ren; Hui Sheng; Jianhua Gao (Journal of Hydrology, 2023)

Experimental study on P-wave response characteristics of hot dry rock under high temperature and high confining pressure - Song Deng; Yixin Zhang; Xiaopeng Yan; Shuo Yang; Chaowei Li; Haoping Peng (Geomechanics for Energy and the Environment, 2023)

Experimental study on the effects of injection pressure on the combustion in a SI aviation piston engine fueled with kerosene - Shuo Zhang; Zhenfeng Zhao; Lei Wang; Chuncun Yu; Zhenhuan Yang; Shangxue Wang (Fuel, 2023)

Mechanistic investigation of Sm doping effects on SO2 resistance of W-Zr-ZSM-5 catalyst for NH3-SCR - Shuo Feng; Wenwen Kong; Yanli Wang; Yuye Xing; Zhuozhi Wang; Jiao Ma; Boxiong Shen; Long Chen; Jiancheng Yang; Zhaoming Li; Chenguang Zhang (Fuel, 2023)

Green tea polyphenols alleviate β-conglycinin-induced anaphylaxis by modulating gut microbiota in rats - Yang Zhou; Shugui Zheng; Shuo Yang; Jiguang Li; Kai Yang; Junfeng Han; Shuang Duan (Food Bioscience, 2023)

Effects of thermal environment on body temperature rhythm and thermal sensation before and after getting into bed: A laboratory study in Shanghai, China - Xinbo Xu; Shuo Li; Yuxin Yang; Zhiwei Lian (Energy and Buildings, 2023)

S-scheme SnO/TiO2 heterojunction with high hole mobility for boosting photocatalytic degradation of gaseous benzene - Shuo Yang; Qipeng Lu; Faguo Wang; Yuanhong Zhi; Jingyue Chen; Yihan Wang; Han Zhang; Haiqing Yin; Peng Sun; Wenbin Cao (Chemical Engineering Journal, 2023)

Selective removal of heavy metals from wastewater using polyphenol nano-microspheres: Enhancing sequestration and regeneration performance through pH-responsive coordinated structural changes - Manyu Zhang; Razanajatovo Mamitiana Roger; Yaran Song; Shuo Wang; Yujia Yang; Qiuming Peng; Tifeng Jiao; Qingrui Zhang (Chemical Engineering Journal, 2023)

Transcriptome sequencing identifies prognostic genes involved in gastric adenocarcinoma - Mingyue Li; Miao Bai; Yulun Wu; Shuo Yang; Lihua Zheng; Luguo Sun; Chunlei Yu; Yanxin Huang (Molecular and Cellular Biochemistry, 2023)

A 3D organized point cloud clustering algorithm for seismic fault data based on region growth - Lihong Zhao; Minghao Cai; Renwei Ding; Yujie Zhang; Shuo Zhao; Jinwei Zhang; Jing Yang (Computational Geosciences, 2023)

Real-time observation of magnetization and magnon dynamics in a two-dimensional topological antiferromagnet MnBi2Te4 - F. Michael Bartram; Meng Li; Liangyang Liu; Zhiming Xu; Yongchao Wang; Mengqian Che; Hao Li; Yang Wu; Yong Xu; Jinsong Zhang; Shuo Yang; Luyi Yang (Science Bulletin, 2023)

Marine ecological effect of typhoon influenced by the frequency-phases of ENSO and anthropogenic activity: the East China Sea example - Shuo Zhang; Shengjing Liu; Xiaomei Xu; Jixuan Lyu; Bian Zha; Guang Yang; Tao Liu; Yong Shi; Yang Yang; Jianhua Gao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Long-term PM2.5 concentration prediction based on improved empirical mode decomposition and deep neural network combined with noise reduction auto-encoder- A case study in Beijing - Mengfan Teng; Siwei Li; Jie Yang; Shuo Wang; Chunying Fan; Yu Ding; Jiaxin Dong; Hao Lin; Shansi Wang (Journal of Cleaner Production, 2023)

Effect of Fe-loading in iron-based catalysts for the CH4 decomposition to H2 and nanocarbons - Miao Yang; Shuo Li; Yimin Deng; Jan Baeyens; Huili Zhang (Journal of Environmental Management, 2023)

Nanomaterial-based magnetic surface molecularly imprinted polymers for specific extraction and efficient recognition of dibutyl phthalate - Shan Wang; Jingying Yang; Jiaqing Sun; Kaixin Liu; Xiaoqian Xie; Liping Hong; Shuo Wang; Mingfei Pan (Food Chemistry, 2023)

Reconstructing annual XCO2 at a 1 km×1 km spatial resolution across China from 2012 to 2019 based on a spatial CatBoost method - Chao Wu; Yuechuang Ju; Shuo Yang; Zhenwei Zhang; Yixiang Chen (Environmental Research, 2023)

Kinetic characterization of gas mixture separation by hydrate method with 1,3-dioxolane and multi-walled carbon nanotubes complex synergistic system - Xiao-Fang Lv; Xing-Ya Ni; Jing Guo; Jiang-Jiang Zhang; Yan-Yun Xiao; Yang Liu; Chuan-Shuo Wang; Shi-Dong Zhou; Shang-Fei Song (Chemical Engineering Journal, 2023)

Research on the path to improve the level of straw resource utilization: taking Shandong Province as an example - Shuo Yang; Yuan Xu; Qingsong Wang; Yujie Zhang; Shu Tian; Yue Xu; Haichao Ma; Xueliang Yuan; Qiao Ma; Huibin Zhang; Zhaopeng Xu (Environment, Development and Sustainability, 2023)

Numerical study on the heat transfer characteristics of a microchannel heat exchanger with liquid lead–bismuth eutectic and supercritical CO2 as working fluids - Hong Liu; Zhigang Zhang; Haisu Du; Tenglong Cong; Shuo Yang (Annals of Nuclear Energy, 2023)

Changing maize hybrids helps adapt to climate change in Northeast China: revealed by field experiment and crop modelling - Jin Zhao; Zhijuan Liu; Shuo Lv; Xiaomao Lin; Tao Li; Xiaoguang Yang (Agricultural and Forest Meteorology, 2023)

Land-use conflict identification in urban fringe areas using the theory of leading functional space partition - Shuo Yang; Shibin Dou; Chenxi Li (The Social Science Journal, 2023)

Fusing vegetation index and ridge segmentation for robust vision based autonomous navigation of agricultural robots in vegetable farms - Shuo Wang; Daobilige Su; Yiyu Jiang; Yu Tan; Yongliang Qiao; Shenghui Yang; Yuliang Feng; Nan Hu (Computers and Electronics in Agriculture, 2023)

High-throughput horticultural phenomics: The history, recent advances and new prospects - Moran Zhang; Shengyong Xu; Yutong Han; Dongping Li; Shuo Yang; Yuan Huang (Computers and Electronics in Agriculture, 2023)

Research on a new-designed Venturi ejector and dazomet particle motion characteristics for dilute-phase pneumatic conveying systems based on CFD-DEM - Haolin Ma; Chunjiang Zhao; Shuo Yang; Si Li; Xiaohe Sun; Changyuan Zhai (Computers and Electronics in Agriculture, 2023)

SIRT1 reduction contributes to doxorubicin–induced oxidative stress and meiotic failure in mouse oocytes - Jun Han; Shuo Wang; Huarong Wang; Tuo Zhang; Ye Yang; Ting Zhao; Ziqi Chen; Guoliang Xia; Chao Wang (Toxicology and Applied Pharmacology, 2023)

Insight into the effect of a heavy metal mixture on neurological damage in rats through combined serum metabolomic and brain proteomic analyses - Jie Xie; Fankun Zhou; Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Shuo Yang; Jiajun Li; Xin Wan; Lingyu Yan; Peishan Liu; Hui Cheng; et al. (Science of The Total Environment, 2023)

Natural resources governance and geopolitical risks: A literature review and bibliometric analysis - Jiangli Yu; Shuo Wang; Wantong Yang (Resources Policy, 2023)

Multidisciplinary design optimization of dynamic positioning system for semi-submersible platform - Yongliang Yuan; Qianlong Shen; Wenhui Xi; Shuo Wang; Jianji Ren; Jiangong Yu; Qingkang Yang (Ocean Engineering, 2023)

Comparative analyses of covariance matrix adaptation and iterative ensemble smoother on high-dimensional inverse problems in high-resolution groundwater modeling - Shuo Yang; Frank T.-C. Tsai; Peter Bacopoulos; Christopher E. Kees (Journal of Hydrology, 2023)

A new quantitative insight: Interaction of polyethylene microplastics with soil - microbiome - crop - Ying Zhang; Shuo Yang; Yuping Zeng; Yi Chen; Hanshuang Liu; Xinyao Yan; Shengyan Pu (Journal of Hazardous Materials, 2023)

Simultaneous degradation of aflatoxin B1 and zearalenone by Porin and Peroxiredoxin enzymes cloned from Acinetobacter nosocomialis Y1 - Tosin Victor Adegoke; Bolei Yang; Xiaoyu Tian; Shuo Yang; Yuan Gao; Junning Ma; Gang Wang; Peidong Si; Runyan Li; Fuguo Xing (Journal of Hazardous Materials, 2023)

How does energy poverty eradication promote common prosperity in China? The role of labor productivity - Kangyin Dong; Shuo Wei; Yang Liu; Jun Zhao (Energy Policy, 2023)

Portable smartphone-assisted fluorescence-colorimetric multidimensional immunosensing microarray based on NH2-UiO-66@PtNPs multifunctional composite for efficient and visual detection of amantadine - Huilin Li; Jingying Yang; Xiaochun Hu; Ran Han; Shuo Wang; Mingfei Pan (Chemical Engineering Journal, 2023)

Oral administration of sophoricoside (SOP) inhibits neuronal damage and neuroinflammation to curb neurodegeneration in Parkinson's disease - Hefei Wang; Dewei He; Zhe Li; Xiyu Gao; Shuo Yang; Mingchi Cui; Bojian Ye; Bingxu Huang; Shoupeng Fu; Dianfeng Liu (Chemico-Biological Interactions, 2023)

Mycobacteriaceae Phenome Atlas (MPA): A Standardized Atlas for the Mycobacteriaceae Phenome Based on Heterogeneous Sources - Wan Liu; Hui Cen; Zhile Wu; Haokui Zhou; Shuo Chen; Xilan Yang; Guoping Zhao; Guoqing Zhang (Phenomics, 2023)
The bacterial family Mycobacteriaceae includes pathogenic and nonpathogenic bacteria, and systematic research on their genome and phenome can give comprehensive perspectives for exploring their disease mechanism. In this study, the phenotypes of Mycobacteriaceae were inferred from available phenomic data, and 82 microbial phenotypic traits were recruited as data elements of the microbial phenome. This Mycobacteriaceae phenome contains five categories and 20 subcategories of polyphasic phenotypes, and three categories and eight subcategories of functional phenotypes, all of which are complementary to the existing data standards of microbial phenotypes. The phenomic data of Mycobacteriaceae strains were compiled by literature mining, third-party database integration, and bioinformatics annotation. The phenotypes were searchable and comparable from the website of the Mycobacteriaceae Phenome Atlas (MPA, https://www.biosino.org/mpa/ ). A topological data analysis of MPA revealed the co-evolution between Mycobacterium tuberculosis and virulence factors, and uncovered potential pathogenicity-associated phenotypes. Two hundred and sixty potential pathogen-enriched pathways were found by Fisher's exact test. The application of MPA may provide novel insights into the pathogenicity mechanism and antimicrobial targets of Mycobacteriaceae.

PLK3 promotes the proneural–mesenchymal transition in glioblastoma via transcriptional regulation of C5AR1 - Shuo Yu; Lin Lv; Yang Li; Qian Ning; Tingting Liu; Tinghua Hu (Molecular Biology Reports, 2023)

Hippocampal LIMK1-mediated Structural Synaptic Plasticity in Neurobehavioral Deficits Induced by a Low-dose Heavy Metal Mixture - Fankun Zhou; Lu Ouyang; Qi Li; Shuo Yang; Sisi Liu; Han Yu; Qiyue Jia; Shaoqi Rao; Jie Xie; Guihua Du; Chang Feng; Guangqin Fan (Molecular Neurobiology, 2023)

Molecular dynamics simulation reveals DNA-specific recognition mechanism via c-Myb in pseudo-palindromic consensus of mim-1 promoter - Jinru Weng; Shuo Yang; Jinkang Shen; Hongsen Liu; Yuzi Xu; Dongyun Hao; Shan Wang (Journal of Zhejiang University-SCIENCE B, 2023)

Study on the thermal release characteristics and the correlation transformation mechanism of microscopic active groups of oxidized coal combustion in a deep mined-out area - Hui-yong Niu; Qing-qing Sun; Shuo-peng Li; Si-wei Sun; Yun-chuan Bu; Yan-xiao Yang; Zi-hao Mao; Meng Tao (Science of The Total Environment, 2023)

Investigation on bubble load characteristics of near-field underwater explosion - Zhichao Lai; Shuo Deng; Jian Qin; Hui Chi; Xiangyao Meng; Xiaoqiang Yang; Ruiyuan Huang (Ocean Engineering, 2023)

Possible mechanism underlying the millennial scale variation of offshore suspended sediment transport in the North Yellow Sea - Yong Shi; Jiabi Du; Xiaomei Xu; Hui Sheng; Jixuan Lyu; Shuo Zhang; Shengjing Liu; Guang Yang; Tao Liu; Jianhua Gao (Marine Geology, 2023)

Petrography and geochemistry of the Permian-Triassic boundary interval, Kangjiaping section, South China: Implication for the drastic marine environment change - Xiao'er Zhu; Ting Liang; Zhenkui Jin; Shuo Yi; Yang Li; Hangshan Lei; Jiayu Li (Marine and Petroleum Geology, 2023)

Insights into the effect of Si/Al ratio on Isobutane/1-butene ratio in the pore of H-BEA zeolite in C4 alkylation process - Shuo Li; Xiaoqiang Zhang; Shijia Dong; Yupeng Du; Xiaoping Chen; Pengzhao Wang; Xiang Feng; Chaohe Yang (Fuel, 2023)

Investigation on the mechanism of Nb and Si co-doping on low SO3 generation from V-based catalyst during NH3-SCR process - Shuo Feng; Bo Wang; Yuye Xing; Wenwen Kong; Jiao Ma; Chenguang Zhang; Zhaoming Li; Boxiong Shen; Zhuozhi Wang; Long Chen; Jiancheng Yang (Fuel, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Analysis of Nord Stream explosions using seismic recordings - Yang Shen; Xiao-Lin Hu; Tong-Dong Wang; Wei Zhu; Quan-Shi Guo; Shuo Yang; Qiang Lu; De-Zhi Zhang; Wei-Guo Xiao (Applied Geophysics, 2023)

Experimental study on a -86 °C cascade refrigeration unit with environmental-friendly refrigerants R290-R170 - Zhan Liu; Kaifeng Yuan; Yunzhi Ling; Haihui Tan; Shuo Yang (Environmental Science and Pollution Research, 2023)

Association between multiple metal(loid)s exposure and renal function: a cross-sectional study from southeastern China - Guihua Du; Xiaoguang Song; Fankun Zhou; Lu Ouyang; Qi Li; Shiying Ruan; Shuo Yang; Shaoqi Rao; Xin Wan; Jie Xie; Chang Feng; Guangqin Fan (Environmental Science and Pollution Research, 2023)

Recent advances in biodegradation of emerging contaminants - microplastics (MPs): Feasibility, mechanism, and future prospects - Shuo Li; Yalun Yang; Shanshan Yang; Heshan Zheng; Yongjie Zheng; Jun M; Dillirani Nagarajan; Sunita Varjani; Jo-Shu Chang (Chemosphere, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

The reservoirs gradually changed the distribution, source, and flux of particulate organic carbon within the Changjiang River catchment - Jixuan Lyu; Yong Shi; Shuo Zhang; Shengjing Liu; Tao Liu; Xiaomei Xu; Guang Yang; Jianhua Gao (Journal of Hydrology, 2023)

Experimental investigation on the cooling performance of direct and secondary loop CO2 air conditioning systems for electric vehicles - Shuo Zong; Xiang Yin; Tongyu Miao; Shucheng Zhang; Xu Yang; Feng Cao (International Journal of Refrigeration, 2023)

Unveiling the CeO2 morphology effect in Pd-CeO2/C heterostructures catalysts for formic acid dehydrogenation - Zhongchun Yuan; Tingting Cao; Min Deng; Jun Ma; Shuo Geng; Chunliang Yang; Yuan Ren; Mengqin Yao; Fei Liu; Xiaodan Wang (Fuel, 2023)

Blue/red dual emission based ratiometric fluorescent intelligent labels for real-time food freshness monitoring - Shuo Yang; Jiang Lou; Limin Jing; Qijun Ding; Xia Li; Yifei Jiang; Zhuqing Liu; Wenjia Han (Food Control, 2023)

Migration of hazardous substances during peanut oil squeezing for their dietary assessment - Bolei Yang; Xiaohua Yu; Jihao Shan; Xiaoyu Tian; Tosin Victor Adegoke; Shuo Yang; Gang Wang; Bowen Tai; Junning Ma; Qiang Yu; Fuguo Xing (Food Control, 2023)

Influence of sodium hypochlorite/ultrasonic pretreatment on sewage sludge and subsequent hydrothermal liquefaction: Study on reaction mechanism and properties of bio-oil - Shuo Zhang; Xiangyu Guo; Zhe Zhu; Zhiqiang Sun; Jinjun Yang; Junying Zhao; Lie Shen; Lasse Rosendahl; Guanyi Chen (Biomass and Bioenergy, 2023)

M2 Macrophage-Derived Exosomal Ferritin Heavy Chain Promotes Colon Cancer Cell Proliferation - Zilu Cui; Wenkun Li; Yadan Wang; Mengran Zhao; Kuiliang Liu; Yi Yang; Shuo Teng; Nan Zhang; Li Min; Peng Li; Shutian Zhang; Junxuan Xu; et al. (Biological Trace Element Research, 2023)

Research on the path of industrial sector's carbon peak based on the perspective of provincial differentiation: a case study from China - Yujie Zhang; Qingsong Wang; Shu Tian; Yue Xu; Xueliang Yuan; Qiao Ma; Haichao Ma; Shuo Yang; Yuan Xu; Chengqing Liu (Environment, Development and Sustainability, 2023)

Development of an LC-MS/MS method for the determination of multiple mycotoxins in human urine - Mobing Chen; Wei Liu; Ping Xiang; Linhao Xu; Yiling Tang; Ran Kong; Shuo Yang; Hui Yan; Bin Di (Food Additives & Contaminants: Part A, 2023)

Impact of extreme rainfall on non-point source nitrogen loss in coastal basins of Laizhou Bay, China - Meng Jiang; Hui Peng; Shengkang Liang; Shuo Wang; Latif Kalin; Enis Baltaci; Yang Liu (Science of The Total Environment, 2023)

Effects of dietary adenosine and adenosine 5′-monophosphate supplementation on carcass characteristics, meat quality, and lipid metabolism in adipose tissues of finishing pigs - Sujuan Rao; Zhijuan Cui; Longmiao Zhang; Shuo Ma; Shuangbo Huang; Li Feng; Yiling Chen; Jinxi Luo; Jinfeng Li; Shiyu Qian; Hanting Liu; Yanzhi Liu; et al. (Meat Science, 2023)

Effect of boron and nitrogen modulation in metal atoms anchoring on flower-like carbon superstructure for efficient ammonia electrosynthesis - Yanchao Zhao; Shuo Zhang; Cong Han; Qian Lu; Qiuju Fu; Huimin Jiang; Lingzhi Yang; Yanlong Xing; Qiuju Zheng; Jianxing Shen; Liting Yan; Xuebo Zhao (Chemical Engineering Journal, 2023)

The pivotal role of MYB transcription factors in plant disease resistance - Yongbo Yu; Shuo Zhang; Yang Yu; Na Cui; Guangchao Yu; Hongyan Zhao; Xiangnan Meng; Haiyan Fan (Planta, 2023)

Review: Synthesis of metal organic framework-based composites for application as immunosensors in food safety - Mingfei Pan; Huilin Li; Jingying Yang; Yixin Wang; Yueyao Wang; Xintong Han; Shuo Wang (Analytica Chimica Acta, 2023)

Quantified trend of photosynthetic rate along the depth of microalgae biofilm - Lin-Lan Zhuang; Wanqing Tian; Yanan Yang; Shuhan Ge; Peihua Li; Shuo Sun; Jian Zhang; Shuang Liang (Science of The Total Environment, 2023)

Hollow-structured molecularly imprinted polymers enabled specific enrichment and highly sensitive determination of aflatoxin B1 and sterigmatocystin against complex sample matrix - Lu Yang; Jing Wang; Chun-Yang Li; Qisijing Liu; Jin Wang; Jing Wu; Huan Lv; Xue-Meng Ji; Jing-Min Liu; Shuo Wang (Journal of Hazardous Materials, 2023)

Carbon and H2 recoveries from plastic waste by using a metal-free porous biocarbon catalyst - Yanghao Jin; Hanmin Yang; Shuo Guo; Ziyi Shi; Tong Han; Ritambhara Gond; Pär G. Jönsson; Weihong Yang (Journal of Cleaner Production, 2023)

Blending n-octanol with biodiesel for more efficient and cleaner combustion in diesel engines: A modeling study - Jing Li; Yifei Liang; Shuo Wang; Shaohua Wu; Wenming Yang; Rui Liu (Journal of Cleaner Production, 2023)

Alkanolamines-activated steel slag for stabilization/solidification of heavy metal contaminated soil - Bin Zeng; Zhi Zhang; Shuo Yang; Liwu Mo; Fei Jin (Journal of Environmental Chemical Engineering, 2023)

Effects of Different Nitrogen Types on Nitrogen Use Efficiency, Field Water Quality, and Soil Microbial Community in the Rice–Crayfish Co-Culture System - Fei Huang; Shuo Yang; Xibin Nie; Jintao Li; Yang Hu; Xuan Li; Zijuan Ding; Jun Hou; Xuexia Wang (Journal of Soil Science and Plant Nutrition, 2023)

The Supplement of Magnesium Element to Inhibit Colorectal Tumor Cells - Heng Li; Xiaonan Feng; Hai Li; Shuo Ma; Wei Song; Bao Yang; Tao Jiang; Chun Yang (Biological Trace Element Research, 2023)
Magnesium ions are essential elements to the human body, with a daily intake of about 350 mg for an adult. Recently, a meta-analysis reported that magnesium ion intake is related to a reduced risk of colorectal tumors. In addition, implantation of biodegradable magnesium pins after colorectal tumor resection could potentially inhibit the residual tumor cells. These impressive results implied that magnesium ions possess inhibitory properties against colorectal carcinoma. However, this hypothesis has yet to be confirmed by experimental results. In this work, different concentrations of magnesium ions were modulated to investigate their inhibitory effects on cell viability through cell cycle arrest, subsequently inducing apoptosis by activating the caspase-3 pathway. The animal experiments revealed that magnesium injection restricted tumor growth after 3 weeks of treatment compared to the control group. According to the immunohistochemistry and transmission electron microscopy results, the remarkable effect may be attributed to promoting the apoptotic rate of tumor cells. The evidence highlights the potential for the clinical use of magnesium implants to inhibit the growth of residual cells after colorectal tumor surgery.

Genome-wide identification and characterization of long non-coding RNA in barley roots in response to Piriformospora indica colonization - Liang Li; Nannan Guo; Tiance Liu; Shuo Yang; Xinting Hu; Shuo Shi; Si Li (Plant Science, 2023)

An efficient cellular image-based platform for high-content screening of neuroprotective agents against chemotherapy-induced neuropathy - Yang-Chen Chang; Yi-Ching Lo; Hsun-Shuo Chang; Hui-Ching Lin; Chien-Chih Chiu; Yih-Fung Chen (NeuroToxicology, 2023)

Influencing factors identification and the nested structure analysis of heavy metals in soils in entire city and surrounding the multiple pollution sources - Pengwei Qiao; Shuo Wang; Mei Lei; Guanghui Guo; Jun Yang; Yan Wei; Yaling Gou; Peizhong Li; Zhongguo Zhang (Journal of Hazardous Materials, 2023)

Elucidating effect of acid strength on isomerization mechanisms of butene over solid acid catalysts in C4 alkylation - Xiaoqiang Zhang; Hao Li; Yupeng Du; Xiaoping Chen; Pengzhao Wang; Lei Wang; Xiang Feng; Chaohe Yang; Shuo Li (Fuel, 2023)

Comparative study of the negative bending behaviour of corrugated web steel–concrete composite beams using NC, ECC and UHPC - Fangwen Wu; Zhou Fan; Lanqing He; Shuo Liu; Jian Zuo; Fei Yang (Engineering Structures, 2023)

Single-cell-resolution transcriptome map revealed novel genes involved in testicular germ cell progression and somatic cells specification in Chinese tongue sole with sex reversal - Hong-Yan Wang; Xiang Liu; Jian-Yang Chen; Yingyi Huang; Yifang Lu; Fujian Tan; Qun Liu; Mingming Yang; Shuo Li; Xianghui Zhang; Yating Qin; Wenxiu Ma; et al. (Science China Life Sciences, 2023)

Endothelial hyperactivation of mutant MAP3K3 induces cerebral cavernous malformation enhanced by PIK3CA GOF mutation - Ran Huo; Yingxi Yang; Yingfan Sun; Qiuxia Zhou; Shaozhi Zhao; Zongchao Mo; Hongyuan Xu; Jie Wang; Jiancong Weng; Yuming Jiao; Junze Zhang; Qiheng He; et al. (Angiogenesis, 2023)

Dual photoluminescence emission carbon dots for ratiometric optical dual-mode and smartphone-integrated visual detection of mercury ion - Dan Chang; Lin Li; Xiaorui Dong; Hu Shi; Shuo Wang; Zhonghua Zhao; Liuliu Lv; Yongxing Yang; Lihong Shi (Journal of Environmental Chemical Engineering, 2023)

Recent research progress of electrocatalytic reduction technology for nitrate wastewater: A review - Shuo Meng; Yan Ling; Mingyu Yang; Xianguang Zhao; Ahmed I. Osman; Ala’a H. Al-Muhtaseb; David W. Rooney; Pow-Seng Yap (Journal of Environmental Chemical Engineering, 2023)

A reliable upconversion nanoparticle-based immunochromatographic assay for the highly sensitive determination of olaquindox in fish muscle and water samples - Zhenhua Wen; Xuelian Hu; Rongfang Yan; Wenxiu Wang; He Meng; Yang Song; Shuo Wang; Xianghong Wang; Yiwei Tang (Food Chemistry, 2023)

Improving the performance of nanogenerators via micro-capacitors and enhanced dipoles - Binbin Zhao; Lulu Lei; Yanfang Zhu; Zefei Cheng; Yansong Liu; Shuo Wang; Mingjia Liu; Tao Yu; Weidong Yang; Yan Li (Chemical Engineering Journal, 2023)

Aircraft observation of fast initiation of mixed phase precipitation in convective cloud over the Tibetan Plateau - Delong Zhao; Minghuai Wang; Daniel Rosenfeld; Baojun Chen; Dantong Liu; Xuexu Wu; Kang Hu; Shuo Ding; Yannian Zhu; Yi Zeng; Yi Qu; Yang Gao; et al. (Atmospheric Research, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Study on the evolution and dominant mechanism of frost heave pressure in the fracture of rock masses - Jinmeng Yang; Lanhao Zhao; Zhenzhong Shen; Shuo Sun (Arabian Journal of Geosciences, 2023)

Processes controlling the distributions and cycling of dissolved aluminum and manganese in the northeastern Indian Ocean - Yichao Yang; Lei Li; Jingling Ren; Shuo Jiang; Jing Zhang (Frontiers in Marine Science, 2023)
Aluminum and manganese are both key parameters in the GEOTRACES program. Data on dissolved aluminum (dAl) and dissolved manganese (dMn) relative to their geochemical behavior remain limited in the northeastern Indian Ocean (IO; including the Bay of Bengal (BoB) and equatorial Indian Ocean (Eq. IO)). Seawater samples collected in the BoB and Eq. IO during the spring inter-monsoon period (7 March to 9 April) of 2017 were analyzed to investigate the behavior and main processes controlling the distributions of dAl and dMn in the northeastern IO. The average concentrations of dAl and dMn in the mixed layer of the BoB were 16.6 and 6.7 nM, respectively. A modified 1-D box-model equation was utilized to estimate the contributions of different sources to dAl and dMn in the mixed layer. Al released from the desorption of and/or dissolution of the lithogenic sediments discharged by the Ganga–Brahmaputra (G-B) river system predominantly controlled the dAl distributions in the mixed layer of the BoB, while the desorption from the lithogenic sediments only contributed approximately 13%–21% dMn. Additional dMn input from the advection of Andaman Sea water and photo-reduction–dissolution of particulate Mn(IV) contributed more than 60% dMn in the mixed layer of the BoB. dAl and dMn in the surface mixed layer of the Eq. IO were mainly affected by the mixing of dAl- and dMn-enriched BoB surface water and low-dAl, low-dMn southern Arabian Sea surface water. Considering water mass properties and dAl concentrations, the distributions of dAl in the intermediate water (750–1,500 m) of northeastern IO were controlled by the mixing of Red Sea Intermediate Water, Indonesian Intermediate Water, and intermediate water of the BoB. Different from dAl, the apparent oxygen utilization relationship with dMn concentrations indicated that the regeneration of lithogenic particles under hypoxic conditions played a more important role than the remineralization of settling organic particles in controlling dMn distributions in the subsurface and intermediate water body (100–1,000 m) of the BoB and that remineralization of biogenic particles mattered to dMn in the subsurface of the Eq. IO.

Numerical study on drying uniformity of bulk corn kernels during radio frequency-assisted hot air drying - Shuo Wei; Weijun Xie; Zhaohui Zheng; Liuyang Ren; Deyong Yang (Biosystems Engineering, 2023)

Morphological measurement for carrot based on three-dimensional reconstruction with a ToF sensor - Weijun Xie; Shuo Wei; Deyong Yang (Postharvest Biology and Technology, 2023)

Experimental study on fracture characteristics of coal due to liquid nitrogen fracturing - Shengcheng Wang; Shanjie Su; Dengke Wang; Peng Hou; Yi Xue; Xin Liang; Chengzheng Cai; Xianghe Gao; Yuhao Jin; Shuo Yang; Xuan Jiang (Geomechanics for Energy and the Environment, 2023)

Environmental impact assessment of VOC emissions from biomass gasification power generation system based on life cycle analysis - Yunqi Sun; Shuo Wang; Qing Yang; Jianlan Li; Liang Wang; Shihong Zhang; Haiping Yang; Hanping Chen (Fuel, 2023)

ZIF-8 sacrificial-templated hollow COF architectures enabled highly efficient enrichment, determination and regulation of food hazards from infant formulas - Lu Yang; Lin-Qing Nie; Jing Wang; Chun-Yang Li; Jin Wang; Jing-Min Liu; Shuo Wang (Food Chemistry, 2023)

A sensitive sensing system based on fluorescence dipeptide nanoparticles for sulfadimethoxine determination - Rongfang Yan; Zhenhua Wen; Xuelian Hu; Wenxiu Wang; He Meng; Yang Song; Shuo Wang; Yiwei Tang (Food Chemistry, 2023)

Associations between exposure to phthalates and subclinical hypothyroidism in pregnant women during early pregnancy: A pilot case-control study in China - Zheng Yang; Danping Shan; Tao Zhang; Ludi Li; Shuo Wang; Ruihu Du; Yingzi Li; Shaowei Wu; Lei Jin; Yi Zhao; Xuejun Shang; Qi Wang (Environmental Pollution, 2023)

Vibration suppression of nonlinear laminated composite plates using internal oscillator-enhanced nonlinear energy sinks - Wei-Xing Zhang; Wei Zhang; Dong-Shuo Yang; Zhong Luo; Xiang-Ying Guo (Engineering Structures, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

A Data-Driven Intelligent Prediction Approach for Collision Responses of Honeycomb Reinforced Pipe Pile of the Offshore Platform - Lei Yang; Hong Lin; Chang Han; Hassan Karampour; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2023)
The potential collision between the ship and the pipe piles of the jacket structure brings huge risks to the safety of an offshore platform. Due to their high energy-absorbing capacity, honeycomb structures have been widely used as impact protectors in various engineering applications. This paper proposes a data-driven intelligent approach for the prediction of the collision response of honeycomb-reinforced structures under ship collision. In the proposed model, the artificial neural network (ANN) is combined with the dynamic particle swarm optimization (DPSO) algorithm to predict the collision responses of honeycomb reinforced pipe piles, including the maximum collision depth (δmax) and maximum absorption energy (Emax). Furthermore, a data-driven evaluation method, known as grey relational analysis (GRA), is proposed to evaluate the collision responses of the honeycomb-reinforced pipe piles of offshore platforms. Results of the case study demonstrate the accuracy of the DPSO-BP-ANN model, with measured mean-square-error (MSE) of 5.06 × 10−4 and 4.35 × 10−3 and R2 of 0.9906 and 0.9963 for δmax and Emax, respectively. It is shown that the GRA method can provide a comprehensive evaluation of the performance of a honeycomb structure under impact loads. The proposed model provides a robust and efficient assessment tool for the safe design of offshore platforms under ship collisions.

Life cycle carbon emissions from road infrastructure in China: A region-level analysis - Yuzhao Han; Hui Li; Jiawen Liu; Ning Xie; Ming Jia; Yang Sun; Shuo Wang (Transportation Research Part D: Transport and Environment, 2023)

The PM2.5 concentration reduction improves survival rate of lung cancer in Beijing - Lei Yang; Ning Wang; Shuo Liu; Qingyang Xiao; Guannan Geng; Xi Zhang; Huichao Li; Yixuan Zheng; Fuyu Guo; Qingyu Li; Jiajianghui Li; Aiguo Ren; et al. (Science of The Total Environment, 2023)

A review of potential antibacterial activities of nisin against Listeria monocytogenes: the combined use of nisin shows more advantages than single use - Mengjie Wu; Yue Ma; Xin Dou; Muhammad Zohaib Aslam; Yangtai Liu; Xuejuan Xia; Shuo Yang; Xiang Wang; Xiaojie Qin; Takashi Hirata; Qingli Dong; Zhuosi Li (Food Research International, 2023)

Cotransport of microplastics and sulfanilamide antibiotics in groundwater: The impact of MP/SA ratio and aquifer media - Shuo Li; Mingxiang Yang; Hao Wang; Yunzhong Jiang (Environmental Research, 2023)

Intracellularly-photosensitized bio-hybrid with biogenic quantum dots for enhanced wastewater denitrification - Shuo Cui; Yang Si; Xian-Zhong Fu; Hui-Hui Li; Xue-Meng Wang; Wen-Zheng Du; Lang Teng; Ru-Li He; Hou-Qi Liu; Ruquan Ye; Wen-Wei Li (Chemical Engineering Journal, 2023)

Nondestructive neutron imaging diagnosis of acidic gas reduction catalyst after 400-Hour operation in natural gas furnace - Zhiming Gao; Yuxuan Zhang; Shuo Qian; Weiwei Yang; Zili Wu; Kyle Gluesenkamp; Kashif Nawaz; Anthony Gehl (Chemical Engineering Journal, 2023)

Engineering electron redistribution of bimetallic phosphates with CeO2 enables high-performance overall water splitting - Xin Guo; Menggang Li; Longyu Qiu; Fenyang Tian; Lin He; Shuo Geng; Yequn Liu; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2023)

Separation of a new triterpenoid saponin together with six known ones from Clematis tangutica (Maxim.) Korsh and evaluation of their cytotoxic activities - Yangfei Wei; Tao Chen; Shuo Wang; Cheng Shen; Shuping Yan; Zhibo Song; Yarong Liu; Fengmei Yang; Ping Hai; Yulin Li (Natural Product Research, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

Load Characteristics and Extreme Response of Straight-Bladed Floating VAWT Using a Fully Coupled Model - Wenping Luo; Weiqin Liu; Meng Yang; Shuo Chen; Xuemin Song; Weiguo Wu (Journal of Marine Science and Engineering, 2023)
Operating Offshore Floating Vertical Axis Wind Turbines (OF-VAWT) have the potential to perform well in the deep-sea area. Some researchers gave performance prediction by developing simplified computing models. However, these models have imperfections in considering load and motion nonlinearity, especially in extreme environments. In this work, a numerical model is developed composed of Computational Fluid Dynamics (CFD) and Dynamic Fluid Body Interaction (DFBI) to acquire the aero-hydrodynamic load and performance of OF-VAWT in general and extreme environments. Unsteady Reynolds-Averaged Navier-Stokes (URANS), SST k-ω and Eulerian Multi-Phase (EMP) models are combined to generate a gas-liquid two-phase flow field; the Volume of Fluid (VOF) model is employed to capture free-surface and make numerical wind-wave. DFBI superposition motion technology is proposed for local motion definition and motion solution, and overset with sliding meshes is introduced to achieve the grid motion. The numerical approach is verified by the tunnel and tank experimental data from the available literature. Simulation results of general cases, such as variable wind speed, wave height and wave length, are compared to discuss the effect of environmental parameters on load and performance. Comparison shows that this straight-bladed OF-VAWT is more susceptible to wind speed. Furthermore, the aerodynamic load generated by the shut-down rotor is still significant in extreme environment, which has implications for the development of OF-VAWT controller.

ATM deficiency aggravates the progression of liver fibrosis induced by carbon tetrachloride in mice - Ming Li; Zhifeng Yang; Zhaoyuan Song; Cunxiang Bo; Shuo Wang; Qiang Jia (Toxicology, 2023)

Process, influencing factors, and simulation of the lateral transport of heavy metals in surface runoff in a mining area driven by rainfall: A review - Pengwei Qiao; Shuo Wang; Jiabin Li; Qianyun Zhao; Yan Wei; Mei Lei; Jun Yang; Zhongguo Zhang (Science of The Total Environment, 2023)

Source-soil-rice-human multi-objective optimization to minimize the cadmium intake risk to consumers of field planting rice - Yang Yang; Shuo Niu; Tianqi Wang; Meie Wang; Weiping Chen; Yanling Li; Yating Dai (Journal of Hazardous Materials, 2023)

Environmental trade-offs and externalities of electrochemical-based batteries: Quantitative analysis between lithium-ion and vanadium redox flow units - Wen-Shuo Tsai; Chihchi Huang; Chien-Chung Huang; Chang-Chung Yang; Mengshan Lee (Journal of Environmental Management, 2023)

Development of a web-based modelling framework for harmful algal blooms transport simulation using open-source technologies - Rufu Qin; Shuo Yang; Zhounan Xu; Tongfang Hong (Journal of Environmental Management, 2023)

Diurnal variation of the fair-weather atmospheric electric field in Binchuan, China - Jiahao Wu; Ziming Zou; Tao Chen; Yunlong Li; Yang Lu; Shuo Ti; Lei Li (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Study on energy management model of integrated New Energy-Storage-Charging system considering the influence of uncertainties - Huanan Liu; Jing Jiang; Shuo Zhan; Xiuyu Yang; Dongmin Yu; Gangui Yan (Fuel, 2023)

Development of a recombinant adenovirus-vectored vaccine against both infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss) - Shouhu Li; Xincang Li; Rui Yuan; Xiaoxue Chen; Shouxu Chen; Yu Qiu; Qingfeng Yang; Meng Wang; Jiangao Shi; Shuo Zhang (Fish & Shellfish Immunology, 2023)

Effect of Ginkgo biloba leaves on the removal efficiency of Cr(VI) in soil and its underlying mechanism - Hefeng Xu; Yanling Fan; Xu Xia; Zengjun Liu; Shuo Yang (Environmental Research, 2023)

Recent progress on key materials and technical approaches for electrochemical lithium extraction processes - Xiaoyu Zhao; Shuo Yang; Yongdan Hou; Haoqiang Gao; Yanfei Wang; Daniel A. Gribble; Vilas G. Pol (Desalination, 2023)

The elaborately-designed Z-scheme Fe-g-C3N4/α-Fe2O3 photocatalytic platform equipping with active N-Fe-O bridges for enhanced synergistic removal of tetracycline and Cr(VI) via photoinduced electron transfer process - Shi-Wen Lv; Qiuyu Zheng; Lingjie Ye; Chun-Yang Li; Jing-Min Liu; Yanqing Cong; Shuo Wang (Chemical Engineering Journal, 2023)

Ultrafast Self-propelling directionally water transporting wood via cell wall reshaping for water manipulation - Zhe Qiu; Fanjun Yu; Dan Xu; Zengbin Wang; Junya Huang; Shuo Wang; Yanxiao Yang; Yonggui Wang; Jian Li; Zefang Xiao; Yanjun Xie; Kai Zhang (Chemical Engineering Journal, 2023)

Generation of abundant oxygen vacancies in Fe doped δ-MnO2 by a facile interfacial synthesis strategy for highly efficient catalysis of VOCs oxidation - Shuo Yang; Zitao Qi; Yuce Wen; Xiaoxiang Wang; Shihan Zhang; Wei Li; Sujing Li (Chemical Engineering Journal, 2023)

A full range of defect passivation strategy targeting efficient and stable planar perovskite solar cells - Yansen Sun; Shuo Yang; Zhenyu Pang; Haipeng Jiang; Shaohua Chi; Xiaoxu Sun; Lin Fan; Fengyou Wang; Xiaoyan Liu; Maobin Wei; Lili Yang; Jinghai Yang (Chemical Engineering Journal, 2023)

Biological saccharification coupled with anaerobic digestion using corn straw for sustainable methane production - Chengjiao Xu; Bowen Wu; Peichao Zhao; Yue Wang; Hua Yang; Yaozu Mi; Yang Zhou; Tian Ma; Shuo Zhang; Linxuan Wu; Lei Chen; Hailian Zang; et al. (Bioresource Technology, 2023)

Microbial production of valuable chemicals by modular co-culture strategy - Shuo Zhao; Fangfang Li; Fan Yang; Qianqian Ma; Liwen Liu; Zhaosong Huang; Xiangyu Fan; Qiang Li; Xiaoli Liu; Pengfei Gu (World Journal of Microbiology and Biotechnology, 2023)

Functionalized photosensitive metal-organic framework as a theranostic nanoplatform for turn-on detection of MicroRNA and photodynamic therapy - Chan Yang; Kun Wang; Shuo Tian; Liuting Mo; Weiying Lin (Analytica Chimica Acta, 2023)

Transcriptome‐based analyses of adaptive divergence between two closely related spruce species on the Qinghai–Tibet plateau and adjacent regions - Shuo Feng; Wei Wan; Yang Li; DongLei Wang; Guangpeng Ren; Tao Ma; Dafu Ru (Molecular Ecology, 2023)
Speciation among populations connected by gene flow is driven by adaptation to different environments, but underlying gene–environment associations remain largely unknown. Here, 162 individuals from 32 populations were sampled to obtain 191,648 independent single nucleotide polymorphisms (SNPs) across the genomes of two closely related spruce species, Picea asperata and Picea crassifolia , which occur on the Qinghai–Tibet Plateau and in surrounding regions. Using the SNP data set, genotype–environment associations and demographic modelling were used to examine local adaptation and genetic divergence between these two species. While morphologically similar, the two Picea species were genetically differentiated in multiple analyses. These species diverged despite continuous gene flow, and their initial divergence was dated back to the late Quaternary. The effective population sizes of both species have expanded since their divergence, as confirmed by niche distribution simulations. A total of 6365 genes were associated with the tested environmental variables; of these, 41 were positively selected in P. asperata and were mainly associated with temperature, while 83 were positively selected in P. crassifolia and were primarily associated with precipitation. These results deepen our understanding of the adaptive divergence and demographic histories of these two spruce species and highlight the importance of genomic data in deciphering the environmental selection underlying Quaternary interspecific divergence.

Genome-Wide Identification Reveals the Potential Functions of the bZIP Gene Family in Common Bean (Phaseolus vulgaris) in Response to Salt Stress During the Sprouting Stage - Qi Zhang; Wen-jing Zhang; Zhen-gong Yin; Wei-jia Li; Chun-Yang Xia; Hao-Yue Sun; Yi-Ming Yang; Hong-Bin Wu; Shuo Zhang; Hao-hao Zhao; Wen-Hui Zhang; Yong-xia Guo; et al. (Journal of Plant Growth Regulation, 2022)

Monthly runoff prediction by a multivariate hybrid model based on decomposition-normality and Lasso regression - Yan Kang; Xiao Cheng; Peiru Chen; Shuo Zhang; Qinyu Yang (Environmental Science and Pollution Research, 2022)

Numerical Investigation on Performance Optimization of Offshore Sandwich Blast Walls with Different Honeycomb Cores Subjected to Blast Loading - Hong Lin; Chang Han; Lei Yang; Lin Zhang; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2022)
As an important protective facility on offshore platform, the blast wall is of great significance in resisting oil and gas explosions. Honeycomb structures are widely used due to their unique deformation and mechanical properties under dynamic impact loads. The aim of this research is to develop an optimized design for an offshore sandwich blast wall with different honeycomb cores. The uniqueness of this paper is providing the quantitative optimization scheme for topological configurations and unit cell geometric parameters of honeycomb structures according to mass consistency and the proposed synthetic evaluation index of anti-blast performance. By using the numerical simulation software ANSYS/LS-DYNA, the CONWEP algorithm was first validated and then adopted to conduct the dynamical performance analysis of the honeycomb blast wall. For comparison purposes, simulating studies on a series of different blast walls were carried out by considering various influential parameters. According to different criteria, the blast resistance of the sandwich honeycomb structures was evaluated. It is found that the sandwich plate with concave arc honeycomb core has the best anti-blast performance compared to that of arrow honeycomb core and concave hexagonal honeycomb core. For the concave arc honeycomb structure, the geometric parameters such as concave angle and aspect ratio of honeycomb unit cell have great influence on the blast-resistance performance. Moreover, the concave arc honeycomb structure with positive gradient arrangement has better anti-blast performance than the negative one. The curved blast wall with the curvature of 1/20 achieves better anti-blast performance than the flat blast wall.

Local domestication of soybean leads to strong root selection and diverse filtration of root-associated bacterial communities - Wen Luo; Jieli Wang; Yuanli Li; Chang Wang; Shanshan Yang; Shuo Jiao; Gehong Wei; Weimin Chen (Plant and Soil, 2022)

Core phylotypes enhance the resistance of soil microbiome to environmental changes to maintain multifunctionality in agricultural ecosystems - Shuo Jiao; Jiejun Qi; Chujie Jin; Yu Liu; Yang Wang; Haibo Pan; Shi Chen; Chunling Liang; Ziheng Peng; Beibei Chen; Xun Qian; Gehong Wei (Global Change Biology, 2022)
Agricultural ecosystems are facing increasing environmental changes. Revealing ecological stability of belowground organisms is key to developing management strategies that maintain agricultural ecosystem services in a changing world. Here, we collected soils from adjacent pairs of maize and rice fields along large spatial scale across Eastern and Southeast China to investigate the importance of core microbiota as a predictor of resistance of soil microbiome (e.g. bacteria, fungi and protist) to climate changes and nutrient fertilization, and their effect on multiple ecosystem functions, representing key services for crop growth and health in agro‐ecosystems. Soil microbiome in maize soils exhibited stronger resistance than that in rice soils, by considering multiple aspects of the resistance index, for example, community, phylogenetic conservation and network complexity. Community resistance of soil microbiome showed a geographic pattern, with higher resistance at lower latitudes, suggesting their stronger resistance in warmer regions. Particularly, we highlighted the role of core phylotypes in enhancing the community resistance of soil microbiome, which was essential for the maintenance of multifunctionality in agricultural ecosystems. Our results represent a significant advance in linking core phylotypes to community resistance and ecosystem functions, and therefore forecasting agro‐ecosystems dynamics in response to ongoing environmental changes. These suggest that core phylotypes should be considered a key factor in enhancing agricultural sustainability and crop productivity under global change scenarios.

Dynamic design and analysis of subsea CO2 discharging flowline for cargo submarines used for CCS in low-carbon and renewable energy value chains - Tianjiao Dai; Shuo Yang; Yihan Xing; Yucong Ma (Frontiers in Marine Science, 2022)
Developing offshore low carbon and renewable energy value chains to realize a net-zero energy future requires combining offshore renewable energy and carbon capture storage (CCS) solutions. The subsea shuttle tanker (SST) was presented in recently published works to accelerate the adoption of offshore CCS systems. The SST is a novel underwater vessel designed to transport CO 2 autonomously from offshore facilities to subsea wells for direct injection at marginal fields using a flowline connected. The SST will be subjected to stochastic currents and experience dynamic responses during this offloading process. The offloading flowline must be designed to handle this dynamic response. As such, this paper establishes the baseline design for this flowline. The cross-section and global configuration designs drive the flowline design. For the cross-section design, the pressure containment, collapse and local buckling criteria defined in DNV-OS-F101 are applied to validate the required structural capacity at specified water depths. For the configuration design, the principle factors concerning the water depth, internal flow rate, and current speed are investigated to further validate the stress capacity according to the allowed von Mises stress level for a more robust baseline design. Finally, the flowline connecting and disassembly methodology is proposed, and the critical factor of well-coordinated speed between flowline and SST is investigated to avoid overbending during the lifting and lowering phases.

Variation in soybean root-associated microbiome between lateral roots with and without nodules - Jiamin Gao; Shi Chen; Yang Wang; Jiejun Qi; Xiaomeng Li; Gehong Wei; Shuo Jiao (Plant and Soil, 2022)

PM2.5 concentration prediction based on WD-SA-LSTM-BP model: a case study of Nanjing city - Shuo Hu; Pengfei Liu; Yunxia Qiao; Qing Wang; Ying Zhang; Yuan Yang (Environmental Science and Pollution Research, 2022)

Age, Growth and Maturation of Largehead Hairtail (Trichiurus japonicus) in the East China Sea - Shuo Cheng; Peng Sun; Yang Liu; Qi Chen; Zhengtong Shi; Runlong Sun (Journal of Ocean University of China, 2022)

Identifying Visual Attention Features Accurately Discerning Between Autism and Typically Developing: a Deep Learning Framework - Jin Xie; Longfei Wang; Paula Webster; Yang Yao; Jiayao Sun; Shuo Wang; Huihui Zhou (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Dynamic Performance and Crashworthiness Assessment of Honeycomb Reinforced Tubular Pipe in the Jacket Platform under Ship Collision - Hong Lin; Chang Han; Lei Yang; Hassan Karampour; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2022)
The collision between the pipe legs of jacket platforms and bypassing ships is of great concern for the safety assessment of platforms. Honeycomb structures have been widely used owing to their unique deformation and mechanical properties under dynamic impact loads. In this paper, two typical honeycomb structures, namely hexagonal honeycomb and arrow honeycomb, were constructed for the impact protection of inclined pipe legs in jacket platforms, and the present study aimed to assess the dynamical performance and crushing resistance of the designed honeycomb reinforced structure under ship collision by using the numerical simulation software ANSYS/LS-DYNA. The dynamical performance of the honeycomb reinforced pipe leg was investigated considering various influential parameters, including the impact velocity and impact direction. The crashworthiness of the two types of honeycomb was evaluated and compared by different criteria, namely the maximum impact depth (δmax), specific energy absorption (SEA) and the proposed index offset sliding (OS). The results demonstrated that both the hexagonal honeycomb structure and the arrow honeycomb structure can reduce the damage of inclined pipe legs caused by ship collision, while the hexagonal honeycomb can provide the better anti-collision capacity, which can well reduce the offset sliding and better protect the pipe leg from ship collision.

Cross-Front Transport Triggered by Winter Storms Around the Shandong Peninsula, China - Xiaomei Xu; Jianhua Gao; Yong Shi; Xiaodong Wu; Jixuan Lv; Shuo Zhang; Shengjing Liu; Tao Liu; Guang Yang (Frontiers in Marine Science, 2022)
Ocean fronts are widespread on the eastern China shelf, especially in winter and early spring. Previous studies have shown that sediments on the northern coast of the Shandong Peninsula could penetrate the coastal fronts and deposit on the southern coast of the Liaodong Peninsula, and this cross-front transport process is closely related to winter storms. However, the detailed mechanisms of cross-front transport remain unclear. In this study, through realistic numerical modeling and physical mechanism analysis, a dynamic mechanism involving cross-front transport triggered by winter storms was proposed, and two locations with the highest probability of frontal instability around the Shandong Peninsula were identified. In detail, forced by winter storms, the Lubei Coastal Current significantly intensifies first and causes frontal inertial instability in the early stage of the winter storm, favoring cross-front exchange between both sides of the front. Then, serving as a compensation current, the Yellow Sea Warm Current intensifies in the late stage of the winter storm, leading to the northward transport of the materials out of the front. Furthermore, the intensity, distance, and path of the cross-front transport under varying winter storms are also investigated. The winter storm, with longer duration, greater wind speed, and westward wind direction, tends to trigger stronger cross-front transport and longer transport distance. Transport paths also differ under different winter storms. This study provides a theoretical explanation for cross-front transport and analyzes the role of winter storms in it, providing some new ideas for nearshore materials dispersal to the sea, which is of great significance for future studies on pollutant diffusion, nutrient distribution, and sediment transport in coastal areas.

Burch colposuspension for stress urinary incontinence: a 14-year prospective follow-up - Yang Ye; Yuan Wang; Weijie Tian; Zhibo Zhang; Shuo Liang; Xiaochen Song; Jianbin Guo; Qianqian Gao; Honghui Shi; Zhijing Sun; Juan Chen; Jinghe Lang; et al. (Science China Life Sciences, 2022)

Rhodohalobacter sulfatireducens sp. nov., isolated from a marine solar saltern - Yu-Sheng Wang; Yu-Yan Yue; Yi-Lin Bai; Xu-Yang Zhang; Shuo Wang; Zong-Jun Du (Archives of Microbiology, 2022)

Quantifying soil nitrous oxide emissions in spring freezing-thawing period over different vegetation types in Northeast China - Bin Wu; Chang-cheng Mu; Hui Liu; Ya-kun Xu; Yue Zhang; Jia-shuo Yang; Wen-nian Xu (Journal of Mountain Science, 2022)

Retiboletus atrofuscus (Boletaceae, Boletales), a new species from China - Fan Zhou; Yang Gao; Hai-Yan Song; Hai-Jing Hu; Shuo-Xi Li; Jin-Hao Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Correction to: Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Contributions of oceanic and continental AAM to interannual variation in ΔLOD with the detection of 2020–2021 La Nina event - Xue-Qing Xu; Yong-Hong Zhou; Peng-Shuo Duan; Ming Fang; Zhao-Yang Kong; Can-Can Xu; Xian-Ran An (Journal of Geodesy, 2022)
As a strong climate element on interannual scales, the El Nino-Southern Oscillation (ENSO) is a major component of global weather and climate change, and it is also closely related to the interannual atmospheric angular momentum (AAM) and length-of-day changes (ΔLOD). Here, we reprocess and compare the interannual variations of AAM, ΔLOD with ENSO indices, with AAM mass and motion terms calculated over land separately from those over the ocean. Three oscillatory components (at ~ 6, ~ 7, ~ 8 years), due to angular momentum changes in Earth's interior, are removed to obtain the interannual ΔLOD solely related to climatic variations. Our results show that the AAM motion term over the ocean contributes the most to interannual ΔLOD, and that the oceanic AAM has larger variability than that over land, especially during the periods of strong ENSO events. After subtracting contributions associated with interior processes, the interannual ΔLOD anomalies corresponding to extreme ENSO events (1982–1983 ~ 0.43, 1997–1998 ~ 0.36, 2015–2016 ~ 0.42 ms) are about half as strong as those found in previous studies (~ 0.91, ~ 0.76, ~ 0.81 ms). Furthermore, we detect an intermediate La Nina event that occurred from August 2020 to May 2021, forcing the interannual ΔLOD to a minimum value of approximately -0.21 ms.

Application of Principal Component Analysis (PCA) to the Evaluation and Screening of Multiactivity Fungi - Zonglin Yang; Yaqi Shi; Pinglin Li; Kanghong Pan; Guoqiang Li; Xianguo Li; Shuo Yao; Dahai Zhang (Journal of Ocean University of China, 2022)

Intelligent identification method and application of seismic faults based on a balanced classification network - Jing Yang; Ren-Wei Ding; Hui-Yong Wang; Nian-Tian Lin; Li-Hong Zhao; Shuo Zhao; Yu-Jie Zhang (Applied Geophysics, 2022)

Spinocerebellar Ataxia Type 10 with Atypical Clinical Manifestation in Han Chinese - Chengyuan Mao; Xinwei Li; Yun Su; Haiyang Luo; Liyuan Fan; Huimin Zheng; Yu Fan; Zhihua Yang; Shuo Zhang; Zhengwei Hu; Xiaoyan Hao; Changhe Shi; et al. (The Cerebellum, 2022)

Ocean Currents May Influence the Endolithic Bacterial Composition in Coral Skeletons - Po-Yu Liu; Sung-Yin Yang; Chih-Ying Lu; Naohisa Wada; Stéphane De Palmas; Shu-Shuo Yeh; Hideyuki Yamashiro; Sen-Lin Tang; Shan-Hua Yang (Frontiers in Marine Science, 2022)
Coral endolithic microbes can be an important nutrients support for hosts while under stresses. Previous studies have found that the endolithic microbial composition of a single coral species can be biogeographical diverse. However, the potential environmental factors, such as salinity, temperature, pH, and nutrient, that might influence the composition of the endolithic microbes remain unclear. In this study, we used both amplicon sequence variants (ASV) and a kmer-based taxonomic unit (KTU) to characterize the endolithic bacterial constitution of Isopora spp. located in the western Pacific Ocean—where it is subjected to the Kuroshio Current (in Okinawa, Japan and Green Island, Taiwan)—and the South China Sea (Dongsha Atoll). The endolithic bacterial community compositions showed a significant geographical difference, and we suggest that the ocean current and primary productivity are the most essential environmental factors influencing the bacterial communities in the skeleton of Isopora spp. In addition, our results showed that, technically, compared to ASV, bacterial composition based on KTU avoids extreme data, making it a suitable tool for explaining the associations between microbes and environmental factors.

Exogenous application of silicon alleviates boron toxicity in rice seedlings - Tian Tian; Shuo Wang; Mingzhe Zhao; Yaojing Wang; Dan Yang; Mingda Liu (Journal of Soils and Sediments, 2022)

Middle Triassic volcanic rocks from the Gangdese belt, southern Tibet: petrogenesis and implications for Tethys tectonic evolution - Jingui Wang; Fan Yang; M. Santosh; Xinquan Zhang; Wentong Wei; Shaopeng Zhuan; Juquan Zhang; Chao Chen; Shuo Wang; Xinpeng Yang; Fei Xue (International Geology Review, 2022)

O-GlcNAcylation in Ventral Tegmental Area Dopaminergic Neurons Regulates Motor Learning and the Response to Natural Reward - Ming-Shuo Shao; Xiao Yang; Chen-Chun Zhang; Chang-You Jiang; Ying Mao; Wen-Dong Xu; Lan Ma; Fei-Fei Wang (Neuroscience Bulletin, 2022)

Molecular characterization, expression, and function of Vitellogenin genes in Phytoseiulus persimilis - Wang Zhenhui; Cai Qi; Yan Shuo; Yang Shuoyu; Lu Qin; Wang Endong; Zhang Bo; Lv Jiale; Xu Xuenong (Experimental and Applied Acarology, 2022)

Migration and abiotic transformation of estrone (E1) and estrone-3-sulfate (E1-3S) during soil column transport - Banghao Du; Weiwei Yu; Lun Yang; Gongduan Fan; Shuo Yang; Hui Jiang; Shenglan Bi; Cheng Yu (Environmental Geochemistry and Health, 2022)

The Relationship of Morphological-Hemodynamic Characteristics, Inflammation, and Remodeling of Aneurysm Wall in Unruptured Intracranial Aneurysms - Qingyuan Liu; Yisen Zhang; Junhua Yang; Yi Yang; Maogui Li; Shanwen Chen; Pengjun Jiang; Nuochuan Wang; Yanan Zhang; Jia Liu; Jun Wu; Shuo Wang (Translational Stroke Research, 2022)

The statistical observation localized equivalent-weights particle filter in a simple nonlinear model - Yuxin Zhao; Shuo Yang; Renfeng Jia; Di Zhou; Xiong Deng; Chang Liu; Xinrong Wu (Acta Oceanologica Sinica, 2022)

Soil phosphorus determines the distinct assembly strategies for abundant and rare bacterial communities during successional reforestation - Ziheng Peng; Zhifeng Wang; Yu Liu; Tongyao Yang; Weimin Chen; Gehong Wei; Shuo Jiao (Soil Ecology Letters, 2021)

Assessing vegetation community distribution characteristics and succession stages in mountainous areas hosting coming Winter Olympics Games - Heng-shuo Zhang; Tong-gang Zha; Yang Yu; Xiao-dong Ji; Rodrigo-Comino Jesús (Journal of Mountain Science, 2021)

Mutation of the sixth amino acid of the Rep protein has no effect on porcine circovirus 2b but enhances porcine circovirus 2d replication in vitro - Xiaoyan Wu; Shuo Wang; Changxun Xin; Chen Li; Jianli Shi; Zhe Peng; Chang Liu; Hong Han; Ying Yang; Yao Tian; Jiaxin Li; Shaojian Xu; et al. (Archives of Virology, 2021)

The Improved Localized Equivalent-Weights Particle Filter with Statistical Observation in an Intermediate Coupled Model - Yuxin Zhao; Shuo Yang; Di Zhou; Xiong Deng; Mengbin Zhu (Journal of Marine Science and Engineering, 2021)
Data assimilation has been widely applied in atmospheric and oceanic forecasting systems and particle filters (PFs) have unique advantages in dealing with nonlinear data assimilation. They have been applied to many scientific fields, but their application in geoscientific systems is limited because of their inefficiency in standard settings systems. To address these issues, this paper further refines the statistical observation and localization scheme which used in the classic localized equivalent-weights particle filter with statistical observation (LEWPF-Sobs). The improved method retains the advantages of equivalent-weights particle filter (EWPF) and the localized particle filter (LPF), while further refinements incorporate the effect of time series on the reanalyzed data into the statistical observation calculations, in addition to incorporating the statistical observation proposal density into the localization scheme to further improve the assimilation accuracy under sparse observation conditions. In order to better simulate the geoscientific system, we choose an intermediate atmosphere-ocean-land coupled model (COAL-IC) as the experimental model and divide the experiment into two parts: standard observation and sparse observation, which are analyzed by the spatial distribution results and root mean square error (RMSE) histogram. In order to better analyze the characteristics of the improved method, this method was chosen to be analyzed in comparison with the localized weighted ensemble Kalman filter (LWEnKF), the LPF and classical LEWPF-Sobs. From the experimental results, it can be seen that the improved method is better than the LWEnKF and LPF methods for various observation conditions. The improved method reduces the RMSE by about 7% under standard observation conditions compared to the traditional method, while the advantage of the improved method is even more obvious under sparse observation conditions, where the RMSE is reduced by about 85% compared to the traditional method. In particular, this improved filter not only combine the advantage of the two algorithms, but also overcome the computing resources.

Development of a dual-labeled, hydrolysis probe-based, real-time quantitative PCR assay for detection of both genotypes of duck circovirus-1 (DuCV-1) and DuCV-2 - Lin Zhang; Wenming Jiang; Fuyou Zhang; Yang Li; Jinping Li; Shaobo Liang; Xiaohui Yu; Cheng Peng; Shuo Liu; Jingjing Wang; Shuhong Sun; Hualei Liu (Virus Genes, 2021)

Evaluation of coffee ecological adaptability using Fuzzy, AHP, and GIS in Yunnan Province, China - Shuo Zhang; Xiaogang Liu; Xinle Wang; Yanli Gao; Qiliang Yang (Arabian Journal of Geosciences, 2021)

The mechanism and application of high-pressure water jet technology to prevent compound dynamic disaster - Zeng-qiang Yang; Chang Liu; Feng-shuo Li; Lin-ming Dou; Gang-wei Li; Da-wei Wang (Arabian Journal of Geosciences, 2021)

Initial ingestion of CMV-infected plants reduces subsequent aphid performance - Xiao-bin Shi; Jun Deng; Zhuo Zhang; Shuo Yan; Li-min Zheng; Shu-e Sun; Yang Gao; Xu-guo Zhou; De-yong Zhang; Yong Liu (Arthropod-Plant Interactions, 2021)

Suitability assessment of urban land use in Dalian, China using PNN and GIS - Ziqian Kang; Shuo Wang; Ling Xu; Fenglin Yang; Shushen Zhang (Natural Hazards, 2021)

Stochastic processes shape the biogeographic variations in core bacterial communities between aerial and belowground compartments of common bean - Yang Liu; Da Li; Jiejun Qi; Ziheng Peng; Weimin Chen; Gehong Wei; Shuo Jiao (Environmental Microbiology, 2021)
Although studies of biogeography in soil bacterial communities have attracted considerable attention, the generality of these patterns along with assembly processes and underlying drivers is poorly understood in the inner tissues of plants. Plant tissues provide unique ecological habitats for microorganisms, which play an essential role in plant performance. Here, we compared core bacterial communities among five soil–plant associated compartments of common bean across five sampling sites in China. Neutral and null modelling consistently suggested that stochastic processes dominated the core community assembly processes and escalated from the belowground compartments to the inner tissues of aerial plant parts. The multiple distance‐decay relationships also varied and had flattened patterns in the stem endosphere, which were shaped by distinct environmental factors in each compartment. Coexistence patterns also varied in topological features, in addition with the sparsest networks in the stem endosphere resulted from the interaction with the stochastic processes. This study considerably expanded our understanding of various biogeographic patterns, assembly processes, and the underlying mechanisms of core bacterial communities between aerial and belowground compartments of common bean. That will provide a scientific basis for the reasonable regulation of core bacterial consortia to get better plant performance.

Sialic Acid Conjugate–Modified Liposomal Dexamethasone Palmitate Targeting Neutrophils for Rheumatoid Arthritis Therapy: Influence of Particle Size - Shuo Wang; Shuaishuai Yang; Xiaoxue Lai; Yanzhi Song; Ling Hu; Cong Li; Tao Shi; Xinrong Liu; Yihui Deng; Guoliang Chen (AAPS PharmSciTech, 2021)

Bisabolane sesquiterpenes from Clausena sanki with their potential anti-inflammatory activities - Shi Hu; Yan-Lei Ma; Jia-Ming Guo; Qing Wen; Gui Yan; Shuo Yang; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2020)

Soil potassium is correlated with root secondary metabolites and root-associated core bacteria in licorice of different ages - Yang Liu; Yanmei Li; Wen Luo; Shuang Liu; Weimin Chen; Chun Chen; Shuo Jiao; Gehong Wei (Plant and Soil, 2020)

Quantitative Angiographic Hemodynamic Evaluation After Revascularization Surgery for Moyamoya Disease - Yu Chen; Li Ma; Shuo Yang; Jan-Karl Burkhardt; Junlin Lu; Xun Ye; Weijian Jiang; Zeguang Ren; Rong Wang; Xiaolin Chen; Yuanli Zhao (Translational Stroke Research, 2020)
The corresponding hemodynamic changes of the internal carotid artery (ICA) after the revascularization surgery for moyamoya disease (MMD) remain unclear. The aim of this study was to analyze the hemodynamic changes of the ipsilateral ICA after the combined direct and indirect extracranial-intracranial (EC-IC) bypass. MMD patients undergoing combined EC-IC bypass were retrospectively reviewed. The mean transit time (MTT) of ICA was evaluated by color-coding angiography before revascularization and at follow-up. The MTT defined as the blood transit time between the end of cervical portion (C1) and the C7 segment of ICA. The clinical prognosis was assessed with Matsushima grading system, moyamoya vessel reduction system, and modified Rankin Scale (mRS). The correlation between hemodynamic parameter and prognosis was analyzed. Subgroup analysis was conducted between different presentations and different ages. Fifty-one patients were identified and the mean imaging follow-up interval was 5.5 months. The ICA-MTT was increased after the combined revascularization ( P < 0.001) compared with contralateral ICA. Faster preoperative ICA-MTT was significantly associated with improved mRS in the ischemic group ( P = 0.05). The increased ICA-MTT was significantly associated with favorable neoangiogenesis ( P = 0.04), moyamoya vessel reduction (> 50%) ( P = 0.023), and improved mRS score ( P = 0.008). In subgroup analysis, the correlation in the ischemic subgroup and adult subgroup remained significant. In this cohort, the ICA-MTT increased after the combined EC-IC bypass, and there was a positive correlation between the increased blood transit time and favorable outcomes. Color-coding DSA proved to be useful as a quantitative and serial method to monitor postoperative courses after revascularization in MMD.

Reduced cadmium accumulation in tobacco by sodium chloride priming - Jia-Shuo Yang; Yanjiao Dai; Yongjun Liu; Shuhui Duan; Yang-Yang Li; Risheng Hu; Zhicheng Zhou; Yi Shi; Haiwei Liu; Shusheng Wang (Environmental Science and Pollution Research, 2020)

The pressure compensation technology of deep-sea sampling based on the real gas state equation - Shuo Wang; Shijun Wu; Canjun Yang (Acta Oceanologica Sinica, 2020)

The underlying mechanism in gel formation and its mathematical simulation during anionic polyacrylamide solution ultrafiltration process - Xuesong Yi; Jiahui Li; Dexin Wang; Yong Wang; Shuo Wang; Fei Yang (Environmental Science and Pollution Research, 2020)

Bioactive Eudesmane sesquiterpenes from Artabotrys hongkongensis Hance - Qing Wen; Yan-Ping Liu; Gui Yan; Shuo Yang; Shi Hu; Jing Hua; Wen-Qing Yin; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2020)

Low-dose Roundup induces developmental toxicity in bovine preimplantation embryos in vitro - Wenyang Cai; Xiao Yang; Xiangchen Li; Hongtu Li; Shuo Wang; Zhengchao Wu; Mingxi Yu; Shiliang Ma; Shuang Tang (Environmental Science and Pollution Research, 2020)

AAV/BBB-Mediated Gene Transfer of CHIP Attenuates Brain Injury Following Experimental Intracerebral Hemorrhage - Shuo Zhang; Zheng-wei Hu; Hai-yang Luo; Cheng-yuan Mao; Mi-bo Tang; Yu-sheng Li; Bo Song; Yao-he Wang; Zhong-xian Zhang; Qi-meng Zhang; Li-yuan Fan; Yao Zhang; et al. (Translational Stroke Research, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Correction to: Reducing macrophage numbers alleviates temporomandibular joint ankylosis - Lu Zhao; E Xiao; Linhai He; Denghui Duan; Yang He; Shuo Chen; Yi Zhang; Yehua Gan (Cell and Tissue Research, 2020)

Cellular levels and molecular dynamics simulations of estragole DNA adducts point at inefficient repair resulting from limited distortion of the double-stranded DNA helix - Shuo Yang; Matthias Diem; Jakob D. H. Liu; Sebastiaan Wesseling; Jacques Vervoort; Chris Oostenbrink; Ivonne M. C. M. Rietjens (Archives of Toxicology, 2020)
Estragole, naturally occurring in a variety of herbs and spices, can form DNA adducts after bioactivation. Estragole DNA adduct formation and repair was studied in in vitro liver cell models, and a molecular dynamics simulation was used to investigate the conformation dependent (in)efficiency of N 2 -( trans -isoestragol-3′-yl)-2′-deoxyguanosine (E-3′- N 2 -dG) DNA adduct repair. HepG2, HepaRG cells, primary rat hepatocytes and CHO cells (including CHO wild-type and three NER-deficient mutants) were exposed to 50 μM estragole or 1′-hydroxyestragole and DNA adduct formation was quantified by LC–MS immediately following exposure and after a period of repair. Results obtained from CHO cell lines indicated that NER plays a role in repair of E-3′- N 2 -dG adducts, however, with limited efficiency since in the CHO wt cells 80% DNA adducts remained upon 24 h repair. Inefficiency of DNA repair was also found in HepaRG cells and primary rat hepatocytes. Changes in DNA structure resulting from E-3′- N 2 -dG adduct formation were investigated by molecular dynamics simulations. Results from molecular dynamics simulations revealed that conformational changes in double-stranded DNA by E-3′- N 2 -dG adduct formation are small, providing a possible explanation for the restrained repair, which may require larger distortions in the DNA structure. NER-mediated enzymatic repair of E-3′- N 2 -dG DNA adducts upon exposure to estragole will be limited, providing opportunities for accumulation of damage upon repeated daily exposure. The inability of this enzymatic repair is likely due to a limited distortion of the DNA double-stranded helix resulting in inefficient activation of nucleotide excision repair.

The class III peroxidase gene OsPrx24 is important for root Iron plaque formation and benefits phosphorus uptake in Rice plants under alternate wetting and drying irrigation - Xu-Jian Yang; You-Qiang Fu; Shuo Ma; Haihua Gan; Weifeng Xu; Hong Shen (Plant and Soil, 2020)

Dopamine D2 Receptor-Mediated Modulation of Rat Retinal Ganglion Cell Excitability - Ning Yin; Yu-Long Yang; Shuo Cheng; Hong-Ning Wang; Xin Hu; Yanying Miao; Fang Li; Zhongfeng Wang (Neuroscience Bulletin, 2020)

Characteristics and mechanism of dolomitization in the ooids of the Cambrian Zhangxia Formation, Xiaweidian, China - Qiheng Guo; Zhenkui Jin; Xiaoer Zhu; Shuting Shi; Junjie Wang; Jinyi Wang; Yang Li; Shuo Li (Carbonates and Evaporites, 2020)

Reducing macrophage numbers alleviates temporomandibular joint ankylosis - Lu Zhao; E Xiao; Linhai He; Denghui Duan; Yang He; Shuo Chen; Yi Zhang; Yehua Gan (Cell and Tissue Research, 2020)

Benzene homologues contaminants in a former herbicide factory site: distribution, attenuation, risk, and remediation implication - Shuo Yang; Xiulan Yan; Lirong Zhong; Xuejiao Tong (Environmental Geochemistry and Health, 2020)

Deep dewatering process of sludge by chemical conditioning and its potential influence on wastewater treatment plants - Shuo Wang; Cong Ma; Yin Zhu; Yangkun Yang; Guocheng Du; Ji Li (Environmental Science and Pollution Research, 2019)

Clerodane diterpenoids from Casearia kurzii and their cytotoxic activities - Yuan Shuo; Chenyue Zhang; Xueyuan Yang; Feng Liu; Qi Zhang; Annan Li; Jun Ma; Dongho Lee; Yasushi Ohizumi; Yuanqiang Guo (Journal of Natural Medicines, 2019)

Neferine inhibits LPS-ATP-induced endothelial cell pyroptosis via regulation of ROS/NLRP3/Caspase-1 signaling pathway - Yang-Shuo Tang; Yan-Hua Zhao; Yong Zhong; Xiao-Zhao Li; Jia-Xi Pu; Yan-Cheng Luo; Qiao-Ling Zhou (Inflammation Research, 2019)

Degradation of the phenolic β-ether lignin model dimer and dyes by dye-decolorizing peroxidase from Bacillus amyloliquefaciens - Juan Yang; Tongguo Gao; Yaru Zhang; Shuo Wang; Hongya Li; Shuna Li; Shuxiang Wang (Biotechnology Letters, 2019)

Selenium Attenuates Staphylococcus aureus Mastitis in Mice by Inhibiting the Activation of the NALP3 Inflammasome and NF-κB/MAPK Pathway - Junkun Ma; Shuo Zhu; Yingfang Guo; Meilin Hao; Yu Chen; Ying Wang; Mei Yang; Jianguo Chen; Mengyao Guo (Biological Trace Element Research, 2019)

Implementation of an Environmental Quality and Harmful Gases Monitoring System in Cloud - Chao-Tung Yang; Shuo-Tsung Chen; Chih-Hung Chang; Walter Den; Chia-Cheng Wu (Journal of Medical and Biological Engineering, 2019)

Skipping of an exon with a nonsense mutation in the DMD gene is induced by the conversion of a splicing enhancer to a splicing silencer - Yanrong Zhu; Huiting Deng; Xiangfa Chen; Hui Li; Cheng Yang; Shuo Li; Xiaoying Pan; Siqi Tian; Shuxin Feng; Xiaoyue Tan; Masafumi Matsuo; Zhujun Zhang (Human Genetics, 2019)

Long noncoding RNA UCA1 inhibits ischaemia/reperfusion injury induced cardiomyocytes apoptosis via suppression of endoplasmic reticulum stress - Jing Chen; Qi Hu; Bo-fang Zhang; Xiao-pei Liu; Shuo Yang; Hong Jiang (Genes & Genomics, 2019)

Integration of C-type natriuretic peptide gene-modified bone marrow mesenchymal stem cells with chitosan/silk fibroin scaffolds as a promising strategy for articular cartilage regeneration - Shuo Yang; Zhiyong Qian; Donghua Liu; Ning Wen; Juan Xu; Ximin Guo (Cell and Tissue Banking, 2019)

Chemical composition and health risk indices associated with size-resolved particulate matter in Pearl River Delta (PRD) region, China - Dongqing Fang; Wei Huang; Dagmara S. Antkiewicz; Yuqin Wang; Reza Bashiri Khuzestani; Yang Zhang; Jing Shang; Martin M. Shafer; Lingyan He; James J. Schauer; Yuanxun Zhang; Shuo Zhao (Environmental Science and Pollution Research, 2019)

Environmentally friendly methodology for fouling removal in pipeline based on leaky guided wave generated by quasi-axisymmetric excitation mode - Shuqing Li; Ri Fang; Zhigang Qu; Liqun Wu; Yang An; Ying Liu; Jie Yang; Shuo Jin; Wuliang Yin (Clean Technologies and Environmental Policy, 2019)

Rac1 Modulates Excitatory Synaptic Transmission in Mouse Retinal Ganglion Cells - Ling-Zhu Li; Ning Yin; Xue-Yan Li; Yanying Miao; Shuo Cheng; Fang Li; Guo-Li Zhao; Shu-Min Zhong; Xin Wang; Xiong-Li Yang; Zhongfeng Wang (Neuroscience Bulletin, 2019)

Rickettsia raoultii and Rickettsia sibirica in ticks from the long-tailed ground squirrel near the China–Kazakhstan border - Shuo Zhao; Meihua Yang; Mengmeng Jiang; Bin Yan; Shanshan Zhao; Wumei Yuan; Baoju Wang; Sándor Hornok; Yuanzhi Wang (Experimental and Applied Acarology, 2019)

6-mT 0–120-Hz magnetic fields differentially affect cellular ATP levels - Dongmei Wang; Lei Zhang; Guangze Shao; Shuo Yang; Shengwei Tao; Kun Fang; Xin Zhang (Environmental Science and Pollution Research, 2018)

Electroacupuncture Alleviated Neuronal Apoptosis Following Ischemic Stroke in Rats via Midkine and ERK/JNK/p38 Signaling Pathway - Ying Xing; Si-Dong Yang; Man-Man Wang; Fang Dong; Ya-Shuo Feng; Feng Zhang (Journal of Molecular Neuroscience, 2018)

Application of CRISPR/Cas9 technologies combined with iPSCs in the study and treatment of retinal degenerative diseases - Bincui Cai; Shuo Sun; Zhiqing Li; Xiaomin Zhang; Yifeng Ke; Jin Yang; Xiaorong Li (Human Genetics, 2018)

Simultaneous removal of NO and SO2 from flue gas using vaporized H2O2 catalyzed by nanoscale zero-valent iron - Yi Zhao; Bo Yuan; Yao Shen; Runlong Hao; Shuo Yang (Environmental Science and Pollution Research, 2018)

Investigation on pseudorabies prevalence in Chinese swine breeding farms in 2013–2016 - Yingyi Liu; Shuo Zhang; Qi Xu; Jiajun Wu; Xinyan Zhai; Shuo Li; Jing Wang; Jianqiang Ni; Lin Yuan; Xiaohui Song; Bolin Zhao; Zhi Zhou; et al. (Tropical Animal Health and Production, 2018)

Downregulation of microRNA-17-5p improves cardiac function after myocardial infarction via attenuation of apoptosis in endothelial cells - Shuo Yang; Tao Fan; Qi Hu; Weipan Xu; Jian Yang; Changwu Xu; Bofang Zhang; Jing Chen; Hong Jiang (Molecular Genetics and Genomics, 2018)

Molecular characterization of microtubule-associated protein 1-light chain 3B in Megalobrama amblycephala fed with high fat/berberine diets - Wei-Na Xu; Dan-Hong Chen; Wen-Bin Liu; Jian-Xiong Xu; Shuo-Shuo Yang (Journal of Applied Genetics, 2018)

Climate zones determine where substantial increases of maize yields can be attained in Northeast China - Zhijuan Liu; Xiaoguang Yang; Xiaomao Lin; Prasanna Gowda; Shuo Lv; Jing Wang (Climatic Change, 2018)

River habitat assessment for ecological restoration of Wei River Basin, China - Tao Yang; Shuo Wang; Xiaoping Li; Ting Wu; Li Li; Jia Chen (Environmental Science and Pollution Research, 2018)

LncRNA MEG3 inhibit endometrial carcinoma tumorigenesis and progression through PI3K pathway - Kai-Xuan Sun; Dan-Dan Wu; Shuo Chen; Yang Zhao; Zhi-Hong Zong (Apoptosis, 2017)

Tumor necrosis factor α accelerates Hep-2 cells proliferation by suppressing TRPP2 expression - Jing Wu; Jizheng Guo; Yunyun Yang; Feifei Jiang; Shuo Chen; Kaile Wu; Bing Shen; Yehai Liu; Juan Du (Science China Life Sciences, 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Rearrangement of potassium ions and Kv1.1/Kv1.2 potassium channels in regenerating axons following end-to-end neurorrhaphy: ionic images from TOF-SIMS - Chiung-Hui Liu; Hung-Ming Chang; Tsung-Huan Wu; Li‑You Chen; Yin-Shuo Yang; To-Jung Tseng; Wen-Chieh Liao (Histochemistry and Cell Biology, 2017)

Purinergic P2X7 receptor functional genetic polymorphisms are associated with the susceptibility to osteoporosis in Chinese postmenopausal women - Hong Xu; Chengxin Gong; Luling He; Shenqiang Rao; Xingzi Liu; Yijun Nie; Changle Liu; Tao Li; Lu Ding; Yunming Tu; Yuping Yang; Fangfang Hu; et al. (Purinergic Signalling, 2017)

The complete chloroplast genome of Cupressus chengiana - Zi-long Zhang; Li-ying Ma; Hongbin Yao; Xin Yang; Ji-huai Luo; Xue Gong; Shuo-yue Wei; Quan-fang Li; Wei Wang; Hong-bin Sun (Conservation Genetics Resources, 2017)

Formation and evolution of Emeishan basalt saprolite in vadose zones of Touzhai landslide source rockmass - Ji-qing Yang; Ze-min Xu; Rui Zhang; Ji-pu Chen; Zhe Ren; Rong-zhang Luo; Xiu-shuo Zhang (Journal of Mountain Science, 2017)

Characterization of the complete chloroplast genome of Carpinus tientaiensis - Yongzhi Yang; Mingcheng Wang; Zhiqiang Lu; Xiuyue Xie; Shuo Feng (Conservation Genetics Resources, 2017)

Characterization of the complete chloroplast genome of Carpinus putoensis - Shuo Feng; Xiuyue Xie; Mingcheng Wang; Yongzhi Yang (Conservation Genetics Resources, 2017)

Two cultivated legume plants reveal the enrichment process of the microbiome in the rhizocompartments - Xiao Xiao; Weimin Chen; Le Zong; Jun Yang; Shuo Jiao; Yanbing Lin; Entao Wang; Gehong Wei (Molecular Ecology, 2017)
The microbiomes of rhizocompartments (nodule endophytes, root endophytes, rhizosphere and root zone) in soya bean and alfalfa were analysed using high‐throughput sequencing to investigate the interactions among legume species, microorganisms and soil types. A clear hierarchical filtration of microbiota by plants was observed in the four rhizocompartments – the nodule endosphere, root endosphere, rhizosphere and root zone – as demonstrated by significant variations in the composition of the microbial community in the different compartments. The rhizosphere and root zone microbial communities were largely influenced by soil type, and the nodule and root endophytes were primarily determined by plant species. Diverse microbes inhabited the root nodule endosphere, and the corresponding dominant symbiotic rhizobia belonged to Ensifer for alfalfa and Ensifer – Bradyrhizobium for soya bean. The nonsymbiotic nodule endophytes were mainly Proteobacteria, Actinobacteria, Firmicutes and Bacteroidetes. The variation in root microbial communities was also affected by the plant growth stage. In summary, this study demonstrated that the enrichment process of nodule endophytes follows a hierarchical filtration and that the bacterial communities in nodule endophytes vary according to the plant species.

Sinomenine attenuates chronic inflammatory pain in mice - Shuo Li; Jing Han; Dong-sheng Wang; Qi Yang; Bin Feng; Wen-bo Kang; Le Yang; Gang Liu; Ming-gao Zhao (Metabolic Brain Disease, 2017)

Investigation of selenium pretreatment in the attenuation of lung injury in rats induced by fine particulate matters - Jie Liu; Yingying Yang; Xuejiao Zeng; Liang Bo; Shuo Jiang; Xihao Du; Yuquan Xie; Rongfang Jiang; Jinzhuo Zhao; Weimin Song (Environmental Science and Pollution Research, 2017)

Temporal dynamics of microbial communities in microcosms in response to pollutants - Shuo Jiao; Zhengqing Zhang; Fan Yang; Yanbing Lin; Weimin Chen; Gehong Wei (Molecular Ecology, 2017)
Elucidating the mechanisms underlying microbial succession is a major goal of microbial ecology research. Given the increasing human pressure on the environment and natural resources, responses to the repeated introduction of organic and inorganic pollutants are of particular interest. To investigate the temporal dynamics of microbial communities in response to pollutants, we analysed the microbial community structure in batch microcosms that were inoculated with soil bacteria following exposure to individual or combined pollutants (phenanthrene, n ‐octadecane, phenanthrene + n ‐octadecane and phenanthrene + n ‐octadecane + CdCl 2 ). Subculturing was performed at 10‐day intervals, followed by high‐throughput sequencing of 16S r RNA genes. The dynamics of microbial communities in response to different pollutants alone and in combination displayed similar patterns during enrichment. Specifically, the repression and induction of microbial taxa were dominant, and the fluctuation was not significant. The rate of appearance for new taxa and the temporal turnover within microbial communities were higher than the rates reported in other studies of microbial communities in air, water and soil samples. In addition, conditionally rare taxa that were specific to the treatments exhibited higher betweenness centrality values in the co‐occurrence network, indicating a strong influence on other interactions in the community. These results suggest that the repeated introduction of pollutants could accelerate microbial succession in microcosms, resulting in the rapid re‐equilibration of microbial communities.

Mosaic Expression of Thyroid Hormone Regulatory Genes Defines Cell Type-Specific Dependency in the Developing Chicken Cerebellum - Joke Delbaere; Stijn L. J. Van Herck; Nele M. A. Bourgeois; Pieter Vancamp; Shuo Yang; Richard J. T. Wingate; Veerle M. Darras (The Cerebellum, 2016)

Simulation of Deformation and Aggregation of Two Red Blood Cells in a Stenosed Microvessel by Dissipative Particle Dynamics - Lanlan Xiao; Yang Liu; Shuo Chen; Bingmei Fu (Cell Biochemistry and Biophysics, 2016)

Complete chloroplast genome of Caragana intermedia (Fabaceae), an endangered shrub endemic to china - Zi-long Zhang; Li-ying Ma; Hong-bin Yao; Xin Yang; Ji-huai Luo; Xue Gong; Shuo-yue Wei; Quan-fang Li; Wei Wang; Hong-bin Sun (Conservation Genetics Resources, 2016)

A new furanosteroid from Talaromyces sp. lgt-4, a fungal endophyte isolated from Tripterygium wilfordii - Kang-Kang Zhi; Zhong-Duo Yang; Shuang-Yan Zhou; Xiao-Jun Yao; Shuo Li; Fei Zhang (Natural Product Research, 2016)

A storm surge projection and disaster risk assessment model for China coastal areas - Shuo Yang; Xin Liu; Qiang Liu (Natural Hazards, 2016)

Small nuclear ribonucleoprotein polypeptide N (Sm51) promotes osteogenic differentiation of bone marrow mesenchymal stem cells by regulating Runx2 - Fanbiao Meng; Liangliang Xu; Shuo Huang; Yang Liu; Yonghui Hou; Kuixing Wang; Xiaohua Jiang; Gang Li (Cell and Tissue Research, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Optimization of the Expression Conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by Response Surface Methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Expression of KCNA5 Protein in Human Mammary Epithelial Cell Line Associated with Caveolin-1 - Jia Liu; Chao Qu; Hongyan Li; Yejun Zhang; Jia Sun; Shuo Yang; Jing Liu; Lijia An; Wei Zou (The Journal of Membrane Biology, 2016)

How much information can soil solute profiles reveal about groundwater recharge? - Tianming Huang; Shuo Yang; Jilai Liu; Zhi Li (Geosciences Journal, 2016)

Variations in the potential climatic suitability distribution patterns and grain yields for spring maize in Northeast China under climate change - Jin Zhao; Xiaoguang Yang; Zhijuan Liu; Shuo Lv; Jing Wang; Shuwei Dai (Climatic Change, 2016)

Echinocystic acid reduces reserpine-induced pain/depression dyad in mice - Shuo Li; Jing Han; Dong-sheng Wang; Bin Feng; Ya-ting Deng; Xin-shang Wang; Qi Yang; Ming-gao Zhao (Metabolic Brain Disease, 2016)

Water resources management under dual uncertainties: a factorial fuzzy two-stage stochastic programming approach - Yang Zhou; Gordon Huang; Shuo Wang; Yuanyuan Zhai; Xiaying Xin (Stochastic Environmental Research and Risk Assessment, 2016)

Effects of changing climate and cultivar on the phenology and yield of winter wheat in the North China Plain - Kenan Li; Xiaoguang Yang; Hanqin Tian; Shufen Pan; Zhijuan Liu; Shuo Lu (International Journal of Biometeorology, 2016)

Sox4 enhances chondrogenic differentiation and proliferation of human synovium-derived stem cell via activation of long noncoding RNA DANCR - Lei Zhang; Shuo Chen; Nirong Bao; Chao Yang; Yunfan Ti; Liwu Zhou; Jianning Zhao (Journal of Molecular Histology, 2015)

Sassarandainol: a new neolignan and anti-inflammatory constituents from the stem of Sassafras randaiense - Ya-Ling Hou; Hsun-Shuo Chang; Hui-Chun Wang; Sheng-Yang Wang; Tze-Ying Chen; Chu-Hung Lin; Ih-Sheng Chen (Natural Product Research, 2015)

Susceptibility and REF1 Gene Polymorphism Towards Colorectal Cancer - Shibin Yang; Yuanhui Lai; Longbin Xiao; Fanghai Han; Wenhui Wu; Shuo Long; Wenfeng Li; Yulong He (Cell Biochemistry and Biophysics, 2015)

Optimization of the expression conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by response surface methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2015)

BpGH3.5, an early auxin-response gene, regulates root elongation in Betula platyphylla × Betula pendula - Guang Yang; Su Chen; Shuo Wang; Guifeng Liu; Huiyu Li; Haijiao Huang; Jing Jiang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Depression of Focal Adhesion Kinase Induces Apoptosis in Rat Osteosarcoma OSR-6 Cells in a Caspase-Dependent Pathway - Shuo Yang; Liming Wang; Qingbo Kong (Cell Biochemistry and Biophysics, 2014)

Amphipol-Trapped ExbB–ExbD Membrane Protein Complex from Escherichia coli: A Biochemical and Structural Case Study - Aleksandr Sverzhinsky; Shuo Qian; Lin Yang; Marc Allaire; Isabel Moraes; Dewang Ma; Jacqueline W. Chung; Manuela Zoonens; Jean-Luc Popot; James W. Coulton (The Journal of Membrane Biology, 2014)

Visceral and somatic hypersensitivity, autonomic cardiovascular dysfunction and low-grade inflammation in a subset of irritable bowel syndrome patients - Liang Liu; Bei-ni Liu; Shuo Chen; Miao Wang; Yang Liu; Yan-li Zhang; Shu-kun Yao (Journal of Zhejiang University-SCIENCE B, 2014)

Tert-Butylhydroquinone as a Phenolic Activator of Nrf2 Antagonizes Arsenic-Induced Oxidative Cytotoxicity but Promotes Arsenic Methylation and Detoxication in Human Hepatocyte Cell Line - Xiaoxu Duan; Dan Liu; Xiaoyue Xing; Jinlong Li; Shuo Zhao; Huifang Nie; Yang Zhang; Guifan Sun; Bing Li (Biological Trace Element Research, 2014)

Release Behaviour of Single Pellets and Internal Fine 3D Structural Features Co-define the In Vitro Drug Release Profile - Shuo Yang; Xianzhen Yin; Caifen Wang; Haiyan Li; You He; Tiqiao Xiao; Lixin Sun; Jiasheng Li; Peter York; Jun He; Jiwen Zhang (The AAPS Journal, 2014)

Increased globulin and its association with hemorrhagic transformation in patients receiving intra-arterial thrombolysis therapy - Yingqi Xing; Zhen-Ni Guo; Shuo Yan; Hang Jin; Shouchun Wang; Yi Yang (Neuroscience Bulletin, 2014)

Complete nucleotide sequence of a norovirus GII.4 genotype: evidence for the spread of the newly emerged pandemic Sydney 2012 strain to China - Yuqi Huo; Ailing Cai; Hui Yang; Mingli Zhou; Jiaxin Yan; Dingxiang Liu; Shuo Shen (Virus Genes, 2014)

The distribution and ultrastructure of the forming blood capillaries and the effect of apoptosis on vascularization in mouse embryonic molar mesenchyme - Guohua Yuan; Li Zhang; Guobin Yang; Jingwen Yang; Chunyan Wan; Lu Zhang; Guangtai Song; Shuo Chen; Zhi Chen (Cell and Tissue Research, 2014)

Serum lipocalin-2, cathepsin S and chemerin levels and nonalcoholic fatty liver disease - Zi Ye; Suijun Wang; Zhen Yang; Min He; Shuo Zhang; Weiwei Zhang; Jie Wen; Qin Li; Ying Huang; Xuanchun Wang; Bin Lu; Zhaoyun Zhang; et al. (Molecular Biology Reports, 2014)

Autoantibodies Isolated from Preeclamptic Patients Induce Endothelial Dysfunction via Interaction with the Angiotensin II AT1 Receptor - Xiaoli Yang; Feng Wang; Wayne Bond Lau; Suli Zhang; Shuo Zhang; Huirong Liu; Xin-Liang Ma (Cardiovascular Toxicology, 2014)

Biocompatibility of nano-hydroxyapatite/Mg-Zn-Ca alloy composite scaffolds to human umbilical cord mesenchymal stem cells from Wharton’s jelly in vitro - FangXia Guan; ShanShan Ma; XinYi Shi; Xun Ma; LianKai Chi; Shuo Liang; YuanBo Cui; ZhiBin Wang; Ning Yao; ShaoKang Guan; Bo Yang (Science China Life Sciences, 2014)

Variability of available climate resources and disaster risks for different maturity types of spring maize in Northeast China - Jin Zhao; Xiaoguang Yang; Shuo Lv; Zhijuan Liu; Jing Wang (Regional Environmental Change, 2014)

A novel point mutation of acetylcholinesterase in a trichlorfon-resistant strain of the oriental fruit fly Bactrocera dorsalis (Diptera: Tephritidae) - Jian-jun Jiang; Kang Zhou; Guang-wen Liang; Ling Zeng; Shuo-yang Wen (Applied Entomology and Zoology, 2014)

Human umbilical cord mesenchymal stem cells inhibit C6 glioma growth via secretion of dickkopf-1 (DKK1) - Shanshan Ma; Shuo Liang; Hongliang Jiao; Liankai Chi; Xinyi Shi; Yi Tian; Bo Yang; Fangxia Guan (Molecular and Cellular Biochemistry, 2014)

Effects of culture and transplantation on follicle activation and early follicular growth in neonatal mouse ovaries - Shuo Wang; Shuhong Yang; Zhiwen Lai; Ting Ding; Wei Shen; Liangyan Shi; Jingjing Jiang; Lanfang Ma; Yong Tian; Xiaofang Du; Aiyue Luo; Shixuan Wang (Cell and Tissue Research, 2013)

Hemoglobin-Induced Nitric Oxide Synthase Overexpression and Nitric Oxide Production Contribute to Blood–Brain Barrier Disruption in the Rat - Shuo Yang; Yizhao Chen; Xinqing Deng; Weiping Jiang; Bing Li; Zhenghao Fu; Mouxuan Du; Rui Ding (Journal of Molecular Neuroscience, 2013)

Immortalized mouse dental papilla mesenchymal cells preserve odontoblastic phenotype and respond to bone morphogenetic protein 2 - Feng Wang; Li-An Wu; Wentong Li; Yuan Yang; Feng Guo; Qingping Gao; Hui-Hsiu Chuang; Lisa Shoff; Wei Wang; Shuo Chen (In Vitro Cellular & Developmental Biology - Animal, 2013)

Novel POMGnT1 mutations cause muscle-eye-brain disease in Chinese patients - Hui Jiao; Hiroshi Manya; Shuo Wang; Yanzhi Zhang; Xiaoqing Li; Jiangxi Xiao; Yanling Yang; Kazuhiro Kobayashi; Tatsushi Toda; Tamao Endo; Xiru Wu; Hui Xiong (Molecular Genetics and Genomics, 2013)

Immunohistochemical localization of the NH2-terminal and COOH-terminal fragments of dentin sialoprotein in mouse teeth - Guohua Yuan; Guobin Yang; Guangtai Song; Zhi Chen; Shuo Chen (Cell and Tissue Research, 2012)

Acetylcholinesterase inhibitory activity of the total alkaloid from traditional Chinese herbal medicine for treating Alzheimer’s disease - Zhongduo Yang; Dongbo Zhang; Jin Ren; Mingjun Yang; Shuo Li (Medicinal Chemistry Research, 2012)

Cooperative folding of tau peptide by coordination of group IIB metal cations during heparin-induced aggregation - Dan-Jing Yang; Shuo Shi; Tian-Ming Yao; Liang-Nian Ji (BioMetals, 2012)

An aporphine alkaloid from Nelumbo nucifera as an acetylcholinesterase inhibitor and the primary investigation for structure–activity correlations - Zhong-duo Yang; Xu Zhang; Juan Du; Zhao-jian Ma; Feng Guo; Shuo Li; Xiao-jun Yao (Natural Product Research, 2012)

Geissoschizine methyl ether, a corynanthean-type indole alkaloid from Uncaria rhynchophylla as a potential acetylcholinesterase inhibitor - Zhong-duo Yang; Dong-zhu Duan; Juan Du; Ming-jun Yang; Shuo Li; Xiao-jun Yao (Natural Product Research, 2012)

Cloning and characterization of a Verticillium wilt resistance gene from Gossypium barbadense and functional analysis in Arabidopsis thaliana - Yan Zhang; Xingfen Wang; Shuo Yang; Jina Chi; Guiyin Zhang; Zhiying Ma (Plant Cell Reports, 2011)

A Single Camera Photogrammetry System for Multi-angle Fast Localization of EEG Electrodes - Shuo Qian; Yang Sheng (Annals of Biomedical Engineering, 2011)

Twenty-three microsatellite loci for Styrax confusus and Styrax japonicus (Styracaceae) - Xiao-Yan Wang; Shuo Yu; Min Liu; Qing-Song Yang; Xiao-Yong Chen (Conservation Genetics Resources, 2010)

Inhibition of human lung adenocarcinoma growth using survivint34a by low-dose systematic administration - Yan Shan; Chunting Wang; Li Yang; Li Juan Chen; Hong Xin Deng; Han Shuo Yang; Zhimian Li; Zhiyong Li; Li Pan; Fei Leng; Yuquan Wei (Journal of Biosciences, 2010)

Climate change and global warming - Wenxin Shi; Shuo Wang; Qianqian Yang (Reviews in Environmental Science and Bio/Technology, 2010)

A fractionation procedure for identifying novel proteins induced by chill stress in Arabidopsis thaliana - Liwen Sun; Shichen Wang; Jinghui Xi; Shuo Yang; Xiangguo Liu; Xin Chai; Hongbao Xin; Baiyi An; Dongyun Hao (Biotechnology Letters, 2009)

Molecular Cloning and Evolutionary Analysis of Hemoglobin α-Chain Genes in Bats - Yang Liu; Dong Dong; Nai-Jian Han; Hua-Bin Zhao; Jin-Shuo Zhang; Gang Li; Paul A. Racey; Shu-Yi Zhang (Biochemical Genetics, 2009)

An in silico strategy identified the target gene candidates regulated by dehydration responsive element binding proteins (DREBs) in Arabidopsis genome - Shichen Wang; Shuo Yang; Yuejia Yin; Xiaosen Guo; Shan Wang; Dongyun Hao (Plant Molecular Biology, 2009)

Strong Purifying Selection on the Odysseus Gene in Two Clades of Sibling Species of the Drosophila montium Species Subgroup - Shuo-Yang Wen; Kimio Shimada; Kuniko Kawai; Masanori J. Toda (Journal of Molecular Evolution, 2006)

Protein and mRNA characterization in high and low metastasis adenoid cystic carcinoma cell lines - Jie-lin Yang; Nai-shuo Zhu; Ying Wang; Xiao-feng Guan; Zhao-xin Zheng (Molecular Biology Reports, 2005)